An environmental-friendly reagent system for the flotation separation of fluorite from calcite or quartz - Wen-Yu Li; Ping Zhu; Biao Chen; Zhen-Jiang Wang; Jia-Lu Li; Yong-Chun Luo (Minerals Engineering, 2026)

Endometriosis-derived exosomal MicroRNA-125b-5p downregulates phosphatidylinositol 3-Kinase/Protein Kinase B signaling pathways via vascular endothelial growth factor to decelerate endometriosis progression - Lei Zhang; Litong Zhu; Huangjin Luo; Xiaolin Chen; Guiyuan Yu; Qiuxia Li; Mo Chen; Ping Jin; Qiuling Shi (Molecular Biology Reports, 2026)

Lignin-first depolymerization of softwood over a NiCu/TiO2 catalyst for the sustainable production of dihydroconiferyl alcohol - Peng Zhu; Yu-Xin Zhang; Qiang Wang; Guo-Hui Cheng; Jun-Li Ren; Ling-Ping Xiao; Run-Cang Sun (Bioresource Technology, 2026)

Breaking the channel barrier: same-fluorescence, different-Tm probe strategy enables seven-target respiratory virus detection on a six-channel PCR platform within 20 minutes - Yang Li; Yi-Nuo Zhao; Xiang Li; Ting Sun; Lin-wei Zhu; Miao-jin Zhu; Li-Guo Liang; Hang-ping Yao (Analytica Chimica Acta, 2026)

Aspergthones A and B, hybrids of dehydrosterigmatocystin with phenolic derivatives, isolated from the endophytic fungus Aspergillus versicolor VDL117 - Shan Hu; Mei Yang; Zhi-Yu Zhang; Yun-Xian Li; Xiao-Qin Yang; Wei-Hua Wang; Ying-Jun Zhang; Ping Zhao; Guo-Lei Zhu (Phytochemistry Letters, 2026)

Integrated analysis of lipid remodeling and volatile evolution during refining of Antarctic krill oil - Xinya Huang; Meiyu Zheng; Jin Zhang; Jinglun Zhou; Qingyang Zhang; Zhengting Zhu; Ping Kong; Shu Wang; Bin Li; Zhigang Hu; Kangyu Zhao; Dongping He; et al. (Food Chemistry, 2026)

A non-complex-algorithmic and manually calculable fragment-resolved isotope framework ratios for geographic authentication of refined sugar - ShuoCong Li; ZhenPeng Zhen; XiaoFeng Xie; RongWei Fu; DeJin Kong; Zhu Lin; ZhaoHua Ping; GuiHua Wang; YuFeng Gao (Food Chemistry, 2026)

Selective enrichment and metabolic characterization of caproate-producing microbes from Baijiu Huangshui - Guida Zhu; Zhangyi Wei; Zhiye Li; Jing Yu; Qiuxiang Tang; Ping Song (Food Bioscience, 2026)

Unlocking multiscale structure-property relationships in epoxy thermosets: A machine learning-driven approach to superior multi-objective performance - Gaoming Li; Yeping Wu; Yujie Xie; Chunhua Zhu; Song Yao; Zhongtao Chen; Ping Zhang; Zixuan Luo; Xiuli Zhao; Sixun Zheng; Yinyu Zhang (Chemical Engineering Journal, 2026)

Prenatal dexamethasone exposure programs male offspring subfertility via GR/HDAC6/CTSL-mediated spermatogonial autophagic flux blockade - Shan Jin; Yixue Yao; Lu Zhu; Xiaoqi Zhao; Mengyuan Li; Ping Jiang; Ziyu Kong; Yi Liu; Ying Ao; Hui Wang (Chemico-Biological Interactions, 2026)

Ammonia nitrogen recovery from biogas slurry via integrated electrochemical ammonia stripping with calcium-based absorption and its product application potential - Haorui Zhang; Li Yang; Keda Jin; Tangjuan Zhang; Yanze Zhu; Ping Ai (Bioresource Technology, 2026)

Clinical Characteristics, Diagnosis, and Treatment of Central Nervous System Candidiasis: A Systematic Review of 418 Cases - Guilherme Diogo Silva; Mariane Taborda; Wdson Luis Lima Kruschewsky; Leonardo Torioni; Mariane Cappellini Stricagnolo; Bernardo Ferreira Camilo; Isadora Campos de Sousa Abreu; Isabela Cristina Oliveira Silva; Nadine Correia Silva Santos; Gabriel Diniz Resende; Marcello Mihailenko Chaves Magri; Adriana Satie Gonçalves Kono Magri; et al. (Mycopathologia, 2026)
Background Central nervous system (CNS) candidiasis is a rare but life-threatening complication of invasive candidiasis. However, current knowledge derives mainly from isolated case reports, and no comprehensive synthesis has been previously performed. Methods We conducted a systematic review of published cases of CNS candidiasis. PubMed and Embase were searched without language or date restrictions. Eligible cases required microbiological or histopathological confirmation of Candida spp. and evidence of CNS involvement on cerebrospinal fluid (CSF) analysis or neuroimaging. Demographic, clinical, radiological, laboratory, therapeutic, and outcome data were extracted. We compared mortality and non-mortality groups, paediatric and adult patients, and diagnostic periods. Results We identified 418 patients reported between 1945 and 2024 (median age, 21 years [IQR 0–46]; 62% male). Prior antibiotic use (53%), intravascular catheterization (31%), and neurosurgery (22%) were common risk factors. Neuroimaging was abnormal in 87% of cases, and cerebrospinal fluid was abnormal in 96%, typically showing neutrophilic or lymphocytic pleocytosis and low glucose. Nearly half of cases were pediatric (41% of very-low-birth-weight neonates), who more often had healthcare-associated risk factors and less often immunosuppressive conditions. Overall mortality was 35%, mostly within 30 days; older age was associated with higher mortality, whereas combination antifungal therapy and more recent diagnostic periods were associated with lower mortality in multivariate analysis. Over time, immunosuppression, non-albicans Candida species, and antifungal use increased, while autopsy-based diagnoses and mortality declined. Conclusion CNS candidiasis is a rare but severe infection with challenging diagnosis and high mortality, emphasizing the importance of early recognition and appropriate antifungal therapy.

Landscaping neurodevelopment of attention-deficit hyperactivity disorder - Ningning Liu; Yin-Shan Wang; Zi-Xuan Zhou; Peng Gao; Chongjing Luo; Xinyi Zhang; Ziqing Zhu; Yuan Gao; Fei Ren; Yan Zhu; Li-Zhen Chen; Haimei Li; et al. (Science Bulletin, 2026)

Isodonoids A–L: Ent-kauranoid diterpenoid-flavanone conjugates from Isodon rubescens - Can-Can Wang; Meng-Yu Bao; Hui-Ying Li; Hao-Ming Xiong; Kei-Fong Ng; Li-Ping Bai; Wei Zhang; Zhi-Hong Jiang; Guo-Yuan Zhu (Phytochemistry, 2026)

Ecotoxicological impacts of TNT and its key transformation intermediates in freshwater microcosms and their effective remediation by a bicarbonate-activated peroxide system - Xu Yang; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo; Yong-bing Zhu; San-ping Zhao (Journal of Water Process Engineering, 2026)

Toward understanding tidal flat regime shifts: Contrasting hydro-sediment dynamics revealed by paired observations of two tidal flats - Shibing Zhu; Ya Ping Wang; Yuan Li; Qingguang Zhu; Fei Xing; Mingliang Li; Chao Gao; Shucun Sun (Journal of Hydrology, 2026)

Rare earth elements as emerging contaminants: Multi-source release, geochemical tracing, and implications for environmental monitoring and management - Yong-He Han; Ming-Zhu Zou; Dong-Xing Guan; Yi-Xi Li; Ping Xiang; Yong Zhang; Hong Zhang; Zhibiao Chen (Journal of Environmental Management, 2026)

Hydrolysis-modified secondary aluminum dross as an additive for supersulfated cement: Early-age strength enhancement and leaching evaluation - Wei Wang; Yuan Xu; Ziming Wang; Xi Xu; Bingqian Li; Ping Duan; Yingcan Zhu; Zuhua Zhang; Zhi Xu; Zuobin Li (Environmental Research, 2026)

From serpentinization to carbonation: Petrological and geochemical constraints from an ophiolitic reaction profile - Hong-Da Zheng; Qing Xiong; Xiang Zhou; Biao Chang; Hong-Kun Dai; Hong-Zhu Cai; Li Wang; Yi-Cong Li; Long-Fei Xue; Ming Chen; Jian-Ping Zheng (Chemical Geology, 2026)

Soil reinforcement by Robinia pseudoacacia roots and its stabilization mechanism for shallow root-soil composite slopes - Xing Chen; Yanjun Shen; Ping Ni; Zijian Li; Jinyu Zhu; Yibing Ning; Haitao Wang (Bulletin of Engineering Geology and the Environment, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Discovery of spiroindolediketopiperazine alkaloids from Penicillium sp. KYS-32 as dual inhibitors of ABCB1 and ABCG2 to reverse multidrug resistance - Yu-Lei Zhu; Ying Li; Xiang-Yu Liu; Yan-Ping Zhu; Jian-Min Yue; Jin-Hai Yu (Phytochemistry, 2026)

Long-range transported dust enhances ice nucleating particle abundance in the North China Plain - Yue Sun; Yujiao Zhu; Hengde Liu; Lanxiadi Chen; Hongyong Li; Yujian Bi; Di Wu; Xiangkun Yin; Can Cui; Ping Liu; Yu Yang; Jisheng Zhang; et al. (Journal of Environmental Sciences, 2026)

Environmental factors drive rutin accumulation through a synergistic network promoting flavonoid biosynthesis and suppressing hydrolysis in tea plants (Camellia sinensis) - Ping Xiang; Puzhen Xu; Yuanyuan Li; Marat Tukhvatshin; Qiufang Zhu; Huaxiu Gong; Yingying Wei; Jinliang Li; Qiliang Peng; Xuan Zhao; Jianghong Liu; Jinke Lin (Food Chemistry, 2026)

Rapid detection of raw meat freshness using deep learning and colorimetric/fluorescent array - Feiran Xu; Le Wang; Ping Li; Yang Wang; Xin Zhu; Yao Rao; Xingguang Chen; Chaofeng Li; Baocai Xu; Xuefeng Wang (Food Chemistry, 2026)

Regulating interfacial electronic structure in Fe2O3/g-C3N4 heterogeneous fenton catalyst for efficient low-temperature flue gas denitrification - Huidong Tang; Chen Liu; Donggou Sun; Wenbo Zhang; Xiaohua Zhu; Yixing Ma; Jiacheng Bao; Kai Li; Xin Sun; Ping Ning (Chemical Engineering Journal, 2026)

High-capacity and rechargeable zeolite-templated carbon for direct air capture of CO2 - Kaijie Xuan; Yifan Zhang; Jie Wu; Yongfa Li; Xifeng Zhu; Yi Xiao; Jiaxin Wang; Ali Nabeeh Shakhs; George P. Lithoxoos; Rashid M.Othman; Faiz Almansour; Ahmed Ameen; et al. (Chemical Engineering Journal, 2026)

ERBB2 as a Prognostic Biomarker in Prostate Cancer: Integration of Single-Cell Transcriptomics, Deep Learning, and Immunohistochemical Validation - Chen Wang; Li-Jing Zhu; Wei-Bo Mao; Ting Chen; Teng-Fei Gu; Sheng-Ping Hu; Yong-Tao Pan; Guo-Lin Yan; Yun-Peng Dong; Jie Li (Biochemical Genetics, 2026)

Acute Myeloid Leukemia Patients with High-Risk Karyotypes Benefit from Decitabine in Combination with Modified CAG - Ping Liu; Chuanyang Lu; Qian Sun; Yu Zhu; Xiaoli Zhao; Jianyong Li; Sixuan Qian; Ming Hong; Wenjie Liu (Biochemical Genetics, 2026)

Synthesis and biological evaluation of Phorbazole D analogues identify IO-5a as a promoter of hUC-MSC chondrogenic differentiation - Ai-zhu Wang; Xiao-mei Liu; Li-ming Zhang; Lu-lu Fu; Ping Li; Jie-ping Zhang; Hua Han (Molecular Diversity, 2026)

Exploring contributions and responses of microbial quantity and diversity to coastal seasonal hypoxia - Guihao Li; Jiarong Hu; Pengfei Zheng; Ping Zhu; Yaping Wang; Songbao Zou; Xiaoli Zhang; Eleni Gentekaki; Song Sun; Aolin Zhu; Jun Gong (Marine Pollution Bulletin, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Hierarchically porous copper for sulfamethoxazole degradation through peroxymonosulfate activation: Role of atomic step and evolution of Cu(III) - Ping Liang; Jie Wang; Jingyu Zhu; Zhenhan Li; Shufen Li; Jiapeng Yang; Chi Zhang; Zhonghua Zhang (Journal of Hazardous Materials, 2026)

Unravelling flavor formation in Chinese steamed bread made with fermented glutinous rice wine dough: insights from microbial succession, metabolomics, and volatile profiling - Jia-Xuan Li; Feng-Ping Qin; Meng-Ting Chen; Yu-Yu Liu; Xiao-Na Guo; Ke-Xue Zhu; Fei Gao; Jun-Jie Xing (Food Research International, 2026)

Synergistic effects of sequential ultrasound and autoclaving treatments on the structure, functionality, and digestibility of chestnut starch varieties - Yuan-Yuan Zhang; Can Xu; Ming-Xue Tu; Yin-Ping Zhang; Cong-Hu Li; Liang-Liang Zhu; Ting Hu (Food Chemistry, 2026)

Market mechanism design and trading decision model incorporating renewable energy alliances for the future electricity capacity market of China - Ying-zhu Han; Xing-ping Zhang; Li Liu; Jia-lin Li; Qin-liang Tan; Yuan-fei Li; Yi Du (Energy Policy, 2026)

Evolution of trade-offs and synergies of ecohydrological services under vegetation restoration - Ping Li; Zhan Xie; Wenqian Liu; Zhipeng Zhu (Ecological Engineering, 2026)

Integrating microbial functional traits to evaluate responses of soil quality to organic amendments in newly reclaimed farmland - Luotong Wang; Hanqin Yin; Chunlei Huang; Guifang Li; Cheng Zhu; Ping Li (Plant and Soil, 2026)

Unraveling the age-dependent water use strategy and its drivers in fast-growing balsa wood (Ochroma lagopus) plantations - Xia Yuan; Bin Yang; Xiai Zhu; Ping Zhang; Lang Wei; Wenjie Liu; Xiangzhong Li; Junen Wu; Yajun Chen (Agricultural and Forest Meteorology, 2026)

Structural and dynamic insights into SPDT for phosphorus allocation in rice - Haitao He; Yan Liu; Jie Zhang; Xiaofeng Zheng; Lihuan Jiang; Zhangmeng Du; Jiaqi Zuo; Shuo Cao; Xuemei Peng; Zhiwen Zheng; Kun Li; Cuicui Shen; et al. (Science China Life Sciences, 2026)

Ankyrin-repeat transmembrane protein WAI-1 confers multiple disease resistance in wheat by activating autoimmunity - Qiuhong Wu; Wenling Li; Yongxing Chen; Huaizhi Zhang; Delin Li; Zhan Li; Fei Xiong; Guanghao Guo; Lei Dong; Xuejia Cui; Jingzhong Xie; Ping Lu; et al. (Science China Life Sciences, 2026)

Cerebellar Contributions to Cognitive Affective Function and Postural Tremor in Neurological Wilson’s Disease - Ping Jin; Dong-xu Yin; Yu-xie Huang; Zi-wen Li; Xin-feng Ma; Kang Lin; Ya-yun Xu; Wei-ming Gao; Qun-rong Ye; Yong-zhu Han; Gong-qiang Wang (The Cerebellum, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Coupling between mobile genetic elements and potential sulfur cycling microorganisms is associated with antibiotic resistance gene distribution in coastal sediments - Li Chen; Diantao Ping; Danyu Zheng; Shan Zhou; Chaoyue Zhang; Qi Chen; Xiaohui Wang; Xuri Dong; Lixin Zhu (Journal of Environmental Chemical Engineering, 2026)

Biochar derived from shell waste: Adsorption of phosphorus from aqueous solutions and potential application as slow-release fertilizer - Shanshan Zhu; Yuting Lu; Tao Li; Yine Li; Pengfei Liu; Jiangfeng Teng; Chao Huang; Yuxin Jiang; Ping Wang (Journal of Environmental Chemical Engineering, 2026)

Apparent resistivity evaluation method of slurry diffusion-solidification and grouting effect of water-bearing fractured rock mass - Hao Xu; Zhen-zhong Xing; Sheng-quan He; Lian-zhi Yang; Yi Zhu; Da-zhao Song; Yu Zhang; Jin-tao Dang; Qiang Liu; Li-ming Qiu; Ping Wang (Journal of Applied Geophysics, 2026)

Establishment of a screening method for potential allergens and assessment of the allergenicity of Chlorella variabilis - Shanshan Zhang; Mengting Zhu; Xiaoqian Xu; Li Guo; Hao Wang; Ping Tong; Hongbing Chen; Jinyan Gao (Food Chemistry, 2026)

Single-atom Fe on N-doped carbon drives 100% electron transfer process for organic pollutant degradation: Role of carrier structure in peroxymonosulfate activation - Zhen Xiao; Shangru Zhai; Yuye Li; Ling-Ping Xiao; Kairuo Zhu (Environmental Research, 2026)

Configurational entropy triggering excellent thermoelectric performance of Fe2VAl-based full-Heusler alloys - Dong Liang; Jian Yu; Xianfeng Ye; Mengyang Li; Tiantian Chen; Shaoqiu Ke; Wanting Zhu; Xiaolei Nie; Ping Wei; Wenyu Zhao; Qingjie Zhang (Chemical Engineering Journal, 2026)

Several small reservoir islands consistently support higher taxonomic, phylogenetic, functional, and interaction diversity than few large ones across multiple taxa - Yao Shen; Yuhao Zhao; Federico Riva; Wande Li; Chen Zhu; Xue Zhang; Ping Ding; Xingfeng Si (Biological Conservation, 2026)

Sedative effects and stress-alleviating capabilities of four dietary plant-derived compounds on Procambarus clarkii - Zihao Li; Xinyi Xie; Ziqian Sun; Zhaoxuan Zhu; Shuang Zhang; Xiaoyan Liang; Mengyu Teng; Haitang Wang; Xiuhong Liu; Ping Yang; Xingxing Fang (Veterinary Research Communications, 2026)

Hematopoiesis could be improved by correcting aberrant bone marrow macrophages polarization in aplastic anemia patients - Chen-Yuan Li; Dan-Dan Chen; Xin-Yan Zhang; Shu-Qian Tang; Meng-Zhu Shen; Ya-Ting Yu; Zhi-Wei Zhang; Zheng-Li Xu; Yuan-Yuan Zhang; Jin-Song Jia; Lan-Ping Xu; Yu Wang; et al. (Science China Life Sciences, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

New 14,15-dinor- neo -clerodane and neo -clerodane diterpenoids from Ajuga macrosperma Wall. ex benth - Yi-huan Li; Yi-hang Ba; Jian-fen Xiao; Shuai Chen; Tian-qing Zhu; Kai-xiang Liu; Hong-ping He; Hua-yi Jiang; Rui Yang (Natural Product Research, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Dual-emitting persistent luminescence-based Ratiometric Aptasensor without complementary-strand and in-situ excitation for accurate detection of bioactive Lactoferrin - Yan-Jun Jin; Jing-Xuan Guo; Zhu-Ying Yan; Li-Jian Chen; Xiu-Ping Yan; Xu Zhao (Food Chemistry, 2026)

Engineering of Azotobacter chroococcum enables potential replacement of synthetic nitrogen fertilizer and mitigation of nitrogen pollutants release under medium-fertility field conditions - Ping Tian; Jun-Feng Wang; Dao-Yuan Wang; Yu-Dian Xun; Xiao-Hui Shi; Ming-Zhu Chen; Yun-Ying Liang; Mei-Ting Yang; Qu-Sheng Li (Bioresource Technology, 2026)

Application of Magnetic-Seismic Geophysical Prospecting Technology in Identifying the Carboniferous Volcanic Rocks in the Chepaizi, West Margin of Junggar Basin - Guo-hua Jiao; Wei-ping Zhang; Jin-ke Zhou; Fu-gang Sun; Hai-tao Yang; Man Li; Zhu-qiang Li (Applied Geophysics, 2026)

Impacts of rainfall runoff on algal community in a humid region reservoir riverine zone - Cunli Li; Miao Yang; Aiju You; Guangwei Zhu; Ping Zhang; Qiaoxi Zheng; Mengyuan Zhu; Linxing Tu; Hongqing Zhang; Lei Fu; Bin Wang; Jinwen Hu; et al. (Journal of Environmental Chemical Engineering, 2026)

Synergistic optimization of yield, quality, and nitrogen use efficiency in indica rice: Influence of nitrogen management and C-N metabolism linkages - Hongjin Li; Tao Li; Jianghui Yu; Tianyu Du; Ping Zhang; Jingjing Cui; Zheshu Xu; Ying Zhu; Fangfu Xu; Qun Hu; Guodong Liu; Guangyan Li; et al. (Field Crops Research, 2026)

Liquid metal-enhanced interfacial polarization in electroactive polymer for high-performance self-sensing artificial muscles - Tianyun Dong; Zhu Ban; Shujia Chen; Hongwei Li; Jie Xia; Jianfeng Ping (Chemical Engineering Journal, 2026)

Synergistic promotion of diabetic wound healing by glucose-responsive functional chitosan-based composite nanohydrogels - Runze Yang; Jiale Sun; Guanglan Peng; Mingcai Wu; Chengen Guan; Jianping Yang; Zeyuan Wang; Wanzhen Li; Longbao Zhu; Jun Wang; Zuchun Zhao; WeiWei Zhang; et al. (Carbohydrate Polymers, 2026)

MnO2/CNT-Modified Anode Microbial Fuel Cells for Removing Varying Amounts of Cu2+ from Wastewater - Jiahui Zhu; Lingling Li; Jun Zhou; Nasha Dou; Lei Gong; Mingjing Li; Hui Tan; Ping Yang; Wenfeng Wang (Water, Air, & Soil Pollution, 2026)

‘1347B’ module confers durable stripe rust resistance in wheat - Hongkui Fu; Delin Li; Huaizhi Zhang; Yongxing Chen; Ping Lu; Miaomiao Li; Gaojie Wang; Keyu Zhu; Lei Dong; Jian Yang; Chunhuan Chen; Bin Bai; et al. (Theoretical and Applied Genetics, 2026)

Histomorphological analysis of the relationship between Helicobacter pylori infection of the gastric mucosa and host immunity strength - Yang-kun Wang; Quan-wei Guo; Hai-ying He; Ying-ying Li; Chao-ya Zhu; Ping Li; Bo Jiang; Su-nan Wang; Si-liang Xu (Journal of Molecular Histology, 2026)

General Biogeographic Rules and Lineage‐Specific History Shape the Assembly of Asian Tropical Megadiversity - Hao Wu; Bing‐Yue Zhu; Jing Yang; Qiang Zhang; Zhen‐Ping Shi; Yan‐Jing Shi; Xiao‐Chen Zhao; Pei‐Yi Yang; Ke‐Xin Fan; Guang‐Shun Li; Si‐Qi Hu; Yee Wen Low; et al. (Journal of Biogeography, 2026)
Aim Tropical Asia's extraordinary plant diversity is thought to be intrinsically linked to its dynamic geological history. However, quantifying the precise evolutionary processes that assembled this diversity across the archipelago remains challenging. A recently proposed biogeographic framework classifies the functional roles of different regions as “radiators,” “incubators,” “corridors” or “accumulators,” offering a useful framework to analyse this complexity. Here, we aim to provide a critical, independent test of this framework using the megadiverse tree genus Syzygium as a model system. Syzygium originated on the Sahul Shelf, contrasting with the Indochinese origin of rattan palms used in the original framework validation. Location Tropical Asia, Pacific Islands and Africa. Methods We analysed the complete chloroplast genome of 200 species of the genus Syzygium and performed phylogenetic analysis to estimate divergence times, ancestral region reconstruction, and estimated diversification and extinction rates. We then analysed the relationship between regional area and the dispersal of species and examined speciation and dispersal patterns in relation to the geographical environment. Results Our comprehensive chloroplast phylogenomic analysis indicates rapid diversification of Syzygium commencing ~12 million years ago, coinciding with shelf collision. Biogeographic reconstructions indicate that while the framework's general principles hold – continental shelf act as “radiators” and isolated islands as “incubators” – the specific geographic roles vary depend on lineage history . Main Conclusions Our study validates the radiator‐incubator model as a general feature of tropical Asian evolution but refines it by demonstrating that historical contingency is key to understanding the assembly of Earth's richest biota. Tropical Asian plant diversity reflects a unique geological history of continental shelf collision and dynamic island geography, offering insights into biodiversity evolution in other geologically active regions worldwide, highlighting the importance of maintaining large, connected natural areas and dispersal corridors for preserving the evolutionary processes that generate Earth's botanical richness.

Clonal hematopoiesis mutation is associated with risk of incident lung cancer and death - Ying Zhu; Chen Zhu; Ping Li; Ruiqi Ma; Dan Zhou; Kai Li; Jianzheng Zhang; Qiang Tong (GeroScience, 2026)

Efficient generation of highly reactive FeIVO2+ via the Fe(II)/Cl2 reaction for water purification - Shaoxiong He; Yuxin Wu; Wenlei Qin; Shenzhou Li; Wanting Cheng; Ping Li; Shizhong Wang; Gangfeng Ouyang; Mingshan Zhu; Jingyun Fang (Water Research, 2026)

Biodegradable mulch films divergently regulate soil carbon cycle by reshaping microbial communities and functional genes - Haiyun Zhang; Shutong Yu; Weiguang Lv; Xilong Wang; Ping Lu; Hanlin Zhang; Juanqin Zhang; Naling Bai; Chenglong Xu; Xianpu Zhu; Shuangxi Li (Journal of Hazardous Materials, 2026)

Polystyrene-nanoplastics-induced unfolded protein response in monocyte-derived macrophages mediates pulmonary fibrosis via oxidative-stress-dependent IL-6 secretion - Yangxuan Wei; Yulin Wu; Delin Zhu; Jiayu Zhang; Xiaojuan Li; Mingzhu Wang; Xiaohui Cui; Yutong Wu; Di Wen; Jing Zuo; Ping Lv; Haitao Shen (Journal of Hazardous Materials, 2026)

Rice quality recognition method based on multimodal model - Yuan Zhang; Xiao Xing; Lei Zhu; Xin Li; Xiao Yan Xue; Chong Tao Sun; Chen Hao Duan; Yan Ping Du (Food Control, 2026)

Isolation and identification of spoilage bacteria from kiwifruit and analysis of the antagonistic activity of three Bacillus strains against these bacteria - Ang Liu; Wen-xin Li; Yi Liu; Xing-lin Ran; Bo-yu Dong; Qiu-ping Yao; De-quan Zhu (Food Control, 2026)

Oligosaccharide mapping analysis through UPLC-Orbitrap-HRMS and enzymatic hydrolysis from Polygonatum odoratum (Mill.) Druce - Qing-Hua Liu; Liu Yang; Yue Wang; Hao-Ming Xiong; Cai-Yun Wang; Guo-Yuan Zhu; Li-ping Bai; Zhi-Hong Jiang; Wei Zhang (Carbohydrate Polymers, 2026)

Metabolomic analysis of coloration mechanism of bamboo sheaths in different cultivars of Chimonobambusa utilis - Yan Lan; Xiao Zhu; Guang-Qian Gou; Ai-Juan Tan; Zhao-Xia Dai; Shi-Ping Huang; Gui-Li Yang (Physiology and Molecular Biology of Plants, 2026)

Rhizosphere fungal community and microbial networks shape N2O emissions and crop yield in a rice-rapeseed rotation system under varying nitrogen levels: A case study from Southwest China - Jin-meng Li; Rong Zhao; Tian-yang Ye; Cong-hua Zhu; Jin Chen; Ping Huang; Xue-qing Yang (Agriculture, Ecosystems & Environment, 2026)

Histone H3.3 phosphorylation facilitates H3K9me3-heterochromatin formation during retrotransposon silencing and X-chromosome inactivation via H3.3K27me3–CBX7–KAP1 axis - Jun Chen; Jiyu Chen; Zhouliang Yu; Liwei Zhang; Yanchao Liu; Xuan Ouyang; Juan Yu; Menghan Wang; Shangqiang Xie; Ming Wang; Tiantian Zhang; Zhaohui Jin; et al. (Science Bulletin, 2026)

Multi-scale rough structure membrane with switchable wettability for highly efficient oil-water separation - Meng Zhu; Xiang Li; Ying Wang; Ping Zhang; Ailin Xie; Xiaobo Gong; Yong Liu (Process Safety and Environmental Protection, 2026)

Suspensaditerpenes A–Q, anti-inflammatory labdane and nor-labdane diterpenoids from the seeds of Forsythia suspensa - Hui-Ying Li; Meng-Yu Bao; Hao-Ming Xiong; Can-Can Wang; Li-Ping Bai; Wei Zhang; Cheng-Yu Chen; Zhi-Hong Jiang; Guo-Yuan Zhu (Phytochemistry, 2026)

Iron: A double-edged sword of female reproductive health - Rui Mao; Dan Yin; Wenbo Lv; Die Wang; Ying Ouyang; Cuilan Zhou; Jun Liu; Suyun Li; Yunhua Zhu; Ping Yu; Hongqing Liao; Cuiying Peng (Journal of Trace Elements in Medicine and Biology, 2026)

Process parameter optimization for greenhouse gas mitigation during green-waste composting and mechanistic insights from microbe–environment networks in treatments with contrasting outcomes - Xiaowen Li; Min Cao; Wenyuxin Huang; Hao Mei; Pan Luo; Ping Ma; Junhao Zhang; Weiqin Zhu; Miaomiao He; Ying Ding (Journal of Cleaner Production, 2026)

Breaking the HCl/SO2 selectivity barrier: Intrinsic basic properties of MDEA/SBA-15 for HCl removal - Xingguang Hao; Ying Zhu; Lei Shi; Fei Wang; Xin Sun; Ping Ning; Kai Li (Fuel, 2026)

Inverted conical pore array construction by one-step electrodeposition for 3D self-supported electrode to boost mass transfer in hydrogen evolution reaction - Linghan Lan; Yaxing Zhu; Juchao Liang; Shaolong Wang; Yanan Zou; Zhuo Li; Yang Yang; Ping Zhang (Fuel, 2026)

Sulfur-doped carbon for enhanced flue gas desulfurization: Synergistic experimental and DFT insights - Jun Li; Xiang Wang; Xiao Zhu; Yuke Li; Min Yan; Yang Ma; Ping Cui; Jingcai Chang; Liqiang Zhang; Tao Wang; Chunyuan Ma; Zhanlong Song (Fuel, 2026)

Molecularly engineered interfaces drive nano-entanglement architectures for synergistic mechanical amplification in silicone rubber composites - Longjin Huang; Xiaomin Song; Yang Yang; Zihao Song; Sisi Shang; Zheyu Yang; Zihan Wang; Ping Zhang; Shichun Li; Xueyan Zhao; Sheng Cui; Chunhua Zhu; et al. (Chemical Engineering Journal, 2026)

Mesoporous catechin nanocarriers potentiate curcumin to treat osteoarthritis via synergistic antioxidant and macrophage repolarization - Xinyu Zhang; Junyan Li; Ye Zhu; Huilin Hu; Ping Gong; Hui Xu; Ningli Guo; Quanzhou Wu; Chao Lou; Minghao Chao; Zhang Chen; Minjiang Chen; et al. (Chemical Engineering Journal, 2026)

Hydrological inundation legacy and seasonal variation jointly regulate soil respiration by shaping microbial community assembly in reservoir riparian zones - Kai Zhu; Fei Ye; Jiaqing Liu; Wenliu Zhang; Weitao Jia; Songlin Zhang; Jinlin Li; Shengjun Wu; Kang Dan; Yulin Wang; Ping Huang (CATENA, 2026)

Virgibacillus aidingensis sp. nov., a bacterium isolated from a hypersaline sediment in Xinjiang Province, North-west China - Li Yang; Hua-Wei Huang; Juan Wang; Cui-Ping Miao; Yi-Qing Li; Xiang-Tao Cen; Li-Xing Zhao; Wen-Yong Zhu; Shu-Kun Tang (Antonie van Leeuwenhoek, 2026)

Brachymonas moutaii sp. nov., a floc-forming bacterium isolated from a distillery wastewater treatment plant - Yaqi Liu; Hui Wang; Ansi Jiang; Junmei Wu; Bi Chen; Yong Zhang; Siliang Yuan; Yan Huang; Haiyan Zeng; Xin Wang; Dian Jiao; Wei Li; et al. (Antonie van Leeuwenhoek, 2026)

Enhancing oil-water separation via droplet coalescence regulated by particle self-rotation in swirling fields - Wei Zhao; Ao-song Wei; Shu Zhu; Tong Zhang; Peng-bo Fu; Jian-ping Li; Xue-jing Yang; Hua-lin Wang (Water Research, 2026)

Multi-phase distribution and predictive modeling of polycyclic aromatic hydrocarbons in the East China marginal seas - Zishan Diao; Yiteng Sun; Minggang Zheng; Xue Zhang; Wenpeng Li; Xianyin Ping; Bin Hui; Fanping Zhu; Jing Wang; Shuguang Wang; Xiaohan Zhang; Xianzheng Yuan (Water Research, 2026)

Spatiotemporal changes in dissolved organic matter chemodiversity and its interaction with microbial composition in heavy-metal polluted river - Chun Liu; Rujie Li; Yuheng Zhang; Lijie Zhang; Zhaoling Liu; Ping Li; Guanghui Fan; Yingjie Zhu; Yue Zuo; Xule Liu; Zhiyong Fu; Xiufeng Zhang (Water Research, 2026)

Experimental and numerical study of a novel slope-type sliding isolation system for seismic protection of electrical equipment - Wanchen Meng; Yanhui Liu; Wenzhi Zheng; Ping Tan; Hao Li; Dengjie Zhu; Fubao Guo (Soil Dynamics and Earthquake Engineering, 2026)

Long-term chemical fertilizer application enhances ammonia oxidizers-mediated soil carbon neutrality - Xueru Huang; Zhuo Zhang; Taoyi Ren; Song Li; Ping Zhu; Jingjing Ma; Zhongjun Jia; Jingkuan Wang; Marcela Hernández (Soil Biology and Biochemistry, 2026)

Responses of mesozooplankton to extreme positive Indian Ocean Dipole (pIOD) and cold-core eddy in the eastern Equatorial Indian Ocean and southern Bay of Bengal during 2019/2020 winter - Ping Du; Xiao Ma; Yuanli Zhu; Ruijie Ye; Shenran Zhang; WNC Priyadarshani; P.A.K.N. Dissanayake; Haifeng Zhang; Yibo Liao; Yanbin Tang; Zhibing Jiang; Hongliang Li; et al. (Progress in Oceanography, 2026)

Late Cretaceous-Early Eocene rapid exhumation in the Basu, eastern Tibet: Implications for the growth of the proto-Tibetan Plateau - Xunzhang Zhu; Dongliang Liu; Haibing Li; Jinjiang Zhang; Marie-Luce Chevalier; Jiawei Pan; Zhongbao Zhao; Shenqiang Chen; Yihu Zhang; Ping Wang; Chao Li; Fucai Liu; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Differential associations of PFAS in follicular fluid and serum with reproductive hormones: Insights from a Chinese IVF cohort GIVES - Kun Zhao; Chu Chu; Michael S. Bloom; Jian-Ping Cong; Marjut Roponen; Pasi Jalava; Mo Yang; Wan-Ting He; Yun-Ting Zhang; Ming-Kun Sun; Jing-Wen Huang; Li-Xia Liang; et al. (Environmental Research, 2026)

Amino-functionalized covalent organic framework-carboxylated carbon nanotubes via covalent bonding for sensitive Tau electrochemical immunosensing - Ping He; Wen-Tao Li; A-Min Zhu; Si-Yuan An; Jun-Ping Ma; She-Ying Dong; Yuan-Zhen Zhou; Jun-Jie Zhu (Chemical Engineering Journal, 2026)

Deciphering mechanisms of stress-induced metabolic shifts in Corynebacterium glutamicum by transcriptomics and contextualised modelling - Xiaomeng Ni; Ning Gao; Wenjing Hu; Xuan Guo; Jiao Liu; Jiuzhou Chen; Ningyun Cai; Xiaojia Zhao; Jibin Sun; Yu Li; Yan Zhu; Ping Zheng (Bioresource Technology, 2026)

Preparation of composite material sodium dodecyl sulfonate/2-methylimidazole zinc MOF/ palygorskite and its high- efficiency adsorption for tetracycline - Xin Li; Wen Chen; Jin-Long Jiang; Xia-ping Zhu; Ping Zhao (Applied Clay Science, 2026)

Toonamonoids A and B: two new limonoids from Toona ciliata var . yunnanensis (C.DC.) C.Y.Wu and their cytotoxic activity - Mingwang Luo; Shengyun Wei; Weihua Wang; Wei Yang; Lu Li; Yujie Li; Qiangxin Zhang; Sida Xie; Xiaoqin Yang; Ping Zhao; Guolei Zhu (Natural Product Research, 2025)

Tropical tree-mycorrhizal types show divergent phosphorus adaptive strategies after 12-year simulated acid rain - Yuanliu Hu; Ji Chen; Dafeng Hui; Ying-Ping Wang; Xiaolin Huang; Minghui Hu; Yiren Zhu; Yonghui Li; Jianling Li; Deqiang Zhang; Qi Deng (Soil Biology and Biochemistry, 2025)

Integrated probabilistic forecasting framework for long-term reservoir outflow through dynamic coupling of meteorological–hydrological–engineering processes - Jiaying Tan; Bin Xu; Jian Zhu; Ping-an Zhong; Ran Mo; Jiangyuan Li; Yuanheng Dong; Xinman Qin; Jiayi Jiang; Huili Wang; Lingwei Zhu (Journal of Hydrology, 2025)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

Recovery of V2O5 from spent catalysts for NH3 and humidity sensors - Yan Li; Ping Hu; Miaomiao Liu; Bo Ran; Yuqing Zhu; Junxi Cheng; Jun Sun; Zhaofeng Wu (Journal of Environmental Chemical Engineering, 2025)

Fe2O3@diatomite heterogeneous fenton system for enhancing phosphorus bioavailability in dredged sediment - Wenmin Li; Jian Zhu; Pei Wu; Hongchun Huang; Xindeng Huang; Mengyan Wu; Ying Zhang; Kangrong Xiang; Jiangfeng Teng; Chang Sun; Ao Tan; Mingjing Lei; et al. (Journal of Environmental Chemical Engineering, 2025)

Synergistic photothermal-magnetic nanoplatform: Recyclable TEG-SPIONs for ultra-efficient pathogen elimination in medical wastewater - Fei Ge; Yimei Wang; Jun Ge; Guoqiang Yang; Xinxin Liu; Shuxian Hou; Xuechao Shi; Yao Xiao; Shujie Li; Weiwei Zhang; Wanzhen Li; Ping Song; et al. (Journal of Environmental Chemical Engineering, 2025)

Biocontrol potential of Bacillus subtilis Sjb3 against Rosa chinensis and apple diseases - Xiyan Lou; ManYu Chen; Ping Li; Yixue Cui; Chunhua Zhu; Dongdong Yu; Muhammad Anwar; Dongli Pei (Fungal Biology, 2025)

Microenvironment-programmed self-activating cascaded chemodynamic antibacterial packaging film with NIR-regulated catalytic activity for prolonged food preservation - Yiya Ping; Liang Zhang; Mengyi Wang; Bingzhi Li; Linpin Luo; Wenze Wang; Yuechun Li; Wentao Zhang; Mingqiang Zhu; Jianlong Wang (Food Packaging and Shelf Life, 2025)

Bioinspired mortise-tenon interlocking HKUST-1/CuOH micro-nano architectures on stainless steel mesh for oil-water separation membranes - Xiang Li; Ping Zhang; Rui Wang; Meng Zhu; Xiaobo Gong; Yucheng Liu (Environmental Research, 2025)

Self-adaptive auditory perceptual system for voice instruction recognition powered by triboelectric acoustic sensor - Si Yuan Zhou; Shi Han Wang; Jing Zhang; Lin Feng Wu; Wei Sheng Wang; Bei Chen Gong; Jia Kang Di; Xiang Mei Duan; Hua Ping Wu; Li Qiang Zhu (Chemical Engineering Journal, 2025)

Effect of Accelerators on Hydrothermal Anaerobic Digestion of Platanus Orientalis Linn Fallen Leaves - Hui Tan; Hongyu Huo; Jun Zhou; Mingjing Li; Jiahui Zhu; Lei Gong; Wenfeng Wang; Ping Yang (Water, Air, & Soil Pollution, 2025)

DPP4, a potential tumor biomarker, and tumor therapeutic target: review - Lu Sun; Yuhui Ma; Chenchen Geng; Xiaoqian Gao; Xinbing Li; Qi Ru; Shuzhen Zhu; Ping Zhang (Molecular Biology Reports, 2025)

Genome-wide survey and expression analysis of JAZ genes in watermelon (Citrullus lanatus) - Yan-Ge Li; Jing Zhang; Xiu-Xiu Cai; Le-Ping Fan; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Molecular Biology Reports, 2025)

Prognostic and therapeutic implications related to glycosylation profiles of cancer-associated fibroblasts in colorectal cancer: insights from single-cell and bulk transcriptomics - Keji Chen; Huixia Huang; Zijuan Hu; Yifei Zhu; Yanxi Yao; Yaxian Wang; Jiayu Chen; Yuxue Li; Dawei Li; Ping Wei (Functional & Integrative Genomics, 2025)

Soil and enzymatic C:N:P stoichiometry response to carbon and nutrient input: evidence from long-term fertilization experiments - Qiong Xiao; Yaping Huang; Guoping Chen; Kailou Liu; Yu Jiang; Boku Zhou; Ping Zhu; Xiaori Han; Junyong Ma; Shutang Liu; Shaomin Huang; Aijun Zhang; et al. (Plant and Soil, 2025)

Metagenome-assembled genomes reveal Pseudogracilibacillus amylolyticus sp. nov., a functional uncultured microorganism in high-temperature Daqu - Ai-Ping Lv; Ying-Han; Bao-Zhu Fang; Guo-Zheng Wang; Man-Chun Liu; Bing-Ru Bian; Zhuo-Huan Zheng; Kai Li; Bing-Yu Li; Jian-Yu Jiao; Lan Liu; Lei Dong; et al. (Systematic and Applied Microbiology, 2025)

Occurrence, distribution, and ecological risks of organic pollutants in global mangrove sediments - Yejiao Sun; Jiangwei Miao; Renjun Huang; Wangqing Tang; Sai Wang; Ping Li; Wei Qian; Jae-Seong Lee; Tuantuan Wang; Xiaoshan Zhu (Journal of Hazardous Materials, 2025)

Effect of fish skin gelatin on gluten proteins during freeze-thaw cycles - Mengjuan Li; Shangyuan Sang; Chin Ping Tan; Lijie Zhu; Xiaojuan Tang; Xin Zhang; Zixuan Yang; Xueming Xu (Journal of Cereal Science, 2025)

Boosting 2,5-furandicarboxylic acid production from crude 5-hydroxymethylfurfural over MgMn-mixed spinel supported Ru catalysts - Yimeng Guo; Xiaoying Tian; Xixi Liu; Hang Lv; Ping Hu; Hui Li; Fengyi Lu; Changwei Hu; Liangfang Zhu (Fuel, 2025)

Elucidating flavor compounds in Chinese steamed bread via glutinous rice wine-fermented dough technique: A triangulated analysis combining electronic tongue, SPME-GC-MS, and quantitative descriptive analysis - Jia-Xuan Li; Feng-Ping Qin; Meng-Ting Chen; Yu-Yu Liu; Xiao-Na Guo; Ke-Xue Zhu; Fei Gao; Jun-Jie Xing (Food Bioscience, 2025)

Corrigendum to “NIR- and pH-responsive injectable nanocomposite alginate-graft-dopamine hydrogel for melanoma suppression and wound repair” [Carbohydrate Polymers 314(2023)120899] - Ping Li; Yang Li; Rongzhan Fu; Zhiguang Duan; Chenhui Zhu; Daidi Fan (Carbohydrate Polymers, 2025)

Organoids in Genetic Disorders: from Disease Modeling to Translational Applications - Yuanhang Zhu; Nanshan Lin; Juan Li; Haoqian Zhang; Ping Zhang; Xin Cheng; Qian Yang; Ling Liu (Stem Cell Reviews and Reports, 2025)

The dietary supplementation with probiotic Bacillus cereus G1-11 improved the growth parameters, immune performances, intestinal histomorphology, and disease resistance of hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) - Ming-Qing Zhang; Zhong-Xuan Zhong; Qian-Ping Du; Wen Li; Ya-Ting Zhu; Guang-Ting Xie; Feng-Ying Yan; Jin-Lin Yang; Shui-Sheng Li; Hu Shu (Animal Feed Science and Technology, 2025)

Furofuran and tetrahydrofuran lignans from Lancea tibetica - Wenbo Li; Fuhua Zhu; Lu Tang; Jun Xu; Xiaoying Zhang; Zhicheng Duan; Wei Zhang; Ping Hai; Yongbiao Zheng; Haiqing Liu; Xia Li; Yanfang Su (Phytochemistry, 2025)

Mature stands of exotic tree species consume less water while sequester comparable carbon as those of native tree species: A 4-year monitoring study in South China - Yanqiong Li; Liwei Zhu; Huiying Ye; Ping Zhao (Journal of Hydrology, 2025)

Modeling the cumulative impact of minor impoundments on watershed hydrology: Enhancements to the Xin’anjiang model - Yiwen Wang; Weifeng Liu; Feilin Zhu; Bin Xu; Weiyu Li; Jianjie Tong; Ping-an Zhong (Journal of Hydrology, 2025)

Ferrous sulfate and low aeration improve carbon component quality in chicken manure compost by regulating the tricarboxylic acid cycle and promoting humification - Chaonan Pan; Yue Zhao; Nina Zhu; Ping Ren; Sainan Li; Yue Li; Zimin Wei (Journal of Environmental Management, 2025)

Rational design of CdS/Ce-UiO-66 heterostructure for high-efficiency photocatalytic oxidation of amines to imines - Huan Zhang; Cai-Yong Zhu; Wen-Qi Jin; Zi-Yu Li; Peng Li; Wei Gao; Ping Zhang; Xiu-Mei Zhang (Journal of Environmental Chemical Engineering, 2025)

Efficient catalytic removal of H2S over Cu/K-co-modified MnCAC: Revealing dual-site synergism mediated by superoxide radicals and basic sites - Li Yuan; Xiang Li; Yu Pu; Yiran Xiong; Langlang Wang; Ping Ning; Boyu Zhu; Xueqian Wang (Chemical Engineering Journal, 2025)

Lactiplantibacillus plantarum RS20D Alleviates Male Reproductive Toxicity Induced by Pubertal Exposure to Di-n-butyl Phthalate and Mono-n-butyl Phthalate - Yuan-ting Zhu; Xing-jie Wang; Shu-liang Liu; Jing-hui Lai; Jian-long Li; Qin Li; Kai-di Hu; Ai-ping Liu; Yong Yang; Li He; Shu-juan Chen; Xiao-lin Ao; et al. (Probiotics and Antimicrobial Proteins, 2025)

Upregulation of PD-1 on Peripheral T cells Subsets is Associated with Parkinson's Disease - Zhi-Ling Zhang; Pang-Hai Ye; Wei-Xin Kong; Jin Li; Si Zhu; Yu-Wan Lin; Ping-Yi Xu; Wen-Yuan Guo (Molecular Neurobiology, 2025)

2-Arylbenzofurans from the stems and leaves of Artocarpus tonkinensis and their potential antiproliferative activities - Jia-Ming Guo; Lin-Xuan Li; Xin-Yi Li; Tian-Yu Wang; En-Ning Zhu; An-Jiao Wu; Shu-Ri Li; Hui- Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2025)

Quantifying high-temperature-induced reproductive growth imbalance in citrus at anthesis: Insights from the CF-ASPM model - Xia Qiu; Feiyu Zhu; Ping Huang; Hongwen Chen; YaLi Li; Changbing Pu; Zongnan Li; Dan Zhong; Chao Xiang; Jin Chen; Si Wang (Computers and Electronics in Agriculture, 2025)

Fragments of ancient continental lithospheric mantle in the Mogok metamorphic Belt, Northern Myanmar: Re–Os isotope and platinum group element constraints - Qing-Hua Zhang; Bin Su; Yi Chen; Victoria Pease; Tou-Ping Peng; Zhu-Yin Chu; Yi-Bing Li; Kai-Hui Shi; Si Chen (Precambrian Research, 2025)

Oxidative damage induced by daily exposure to primary and emerging aromatic amines: Insights from large scale biomonitoring and cell-based high-throughput PCR array analysis - Shaohan Zhang; Zijun Zhou; Pingping Wang; Yanan Yao; Yuhao Cao; Jialan Liu; Ping Li; Tao Zhang; Hongkai Zhu; Lei Wang; Hongwen Sun; Zhipeng Cheng (Journal of Hazardous Materials, 2025)

Efficient recovery of spent catalysts in PAO production via annular drainage hydrocyclone: a sustainable approach for fluorinated waste reduction - Wei Zhao; Jian-ping Li; Tong Zhang; Shu Zhu; Ao-song Wei; Dan-hui Yang; Xue-jing Yang; Hua-lin Wang (Journal of Cleaner Production, 2025)

The migration and transformation behavior of mercury and sulfur during coal pyrolysis - Caixia Yue; Yaning Zhu; Huijun Chen; Yahui Wang; Lunjing Yan; Ping Li; Xingjun Wang; Meijun Wang; Liping Chang; Weiren Bao; Jiancheng Wang (Fuel, 2025)

Multi-step ahead probabilistic runoff forecasting with SHAP interpretability: a GPR-enhanced deep learning ensemble approach integrating teleconnection factors - Feilin Zhu; Tiantian Hou; Ou Zhu; Yitong Sun; Weifeng Liu; Lingqi Zhao; Xuning Guo; Min Li; Ping-an Zhong (Environmental Modelling & Software, 2025)

Internal encapsulation for enhancing perovskite solar cell stability based on moisture-triggered in situ polymerization - Jingwei Zhu; Jianting Huang; Ping Hu; Wei Yue; Mingdeng Wei; Ying Zhang; Yafeng Li (Chemical Engineering Journal, 2025)

Nanoparticles co-delivering double-stranded RNA and insecticide enhance control efficacy and overcome pest resistance - Chao Hu; Chang Yu; Jiaqing Li; Yuxi Liu; Qinghong Zeng; Hu Wan; Shun He; Yuting Li; Ping Gao; Yuntong Lv; Kunyan Zhu; Subba Reddy Palli; et al. (Chemical Engineering Journal, 2025)

Chalcogen heteroatom engineering of non-halogenated volatile solid additives based on phthalic anhydride enables high-performance polymer solar cells - Tao Li; Yu Zhu; Xiujie Peng; Heng Li; Linglong Ye; Qingyuan Wang; Zhi-Guo Zhang; Ping Shen; Chao Weng (Chemical Engineering Journal, 2025)

Interfacial electron accumulation of Ir-Co3O4 toward efficient acidic oxygen evolution reaction - Aiying Song; Chao Cai; Ming Jiang; Pengcheng Li; Ping Liao; Yue Huang; Lang Chen; Xuming Yang; Yuanmin Zhu (Chemical Engineering Journal, 2025)

Sulfide-based autotrophic denitrification process with efficient nitrogen removal under high salinity stress: Threshold behaviors and recovery enhanced via glutamate supplementation - Kaiyu Zhang; Qaisar Mahmood; Jiayi Lv; Na Liang; Xiaopeng Zhu; Jinye Li; Jing Cai; Ping Zheng (Bioresource Technology, 2025)

Spatiotemporal dynamics of migratory birds reshape seed dispersal and conservation implications on fragmented islands - Wande Li; Ingo Grass; Chen Zhu; Thomas Hiller; Marit Kinga Kasten; David Becker; Sara Tassoni; Ping Ding; Xingfeng Si (Biological Conservation, 2025)

Long-Term Fertilization Effects on Forms and Availability of Phosphorus Associated with Humic Substance Fractions in a Mollisol in Northeast China - Jinjing Zhang; Yuanhong Sun; Yuhan Yuan; Hongbin Ma; Yanhui Feng; Zhihan Zhang; Jiayi Tang; Cuilan Li; Mo Zhu; Ping Zhu (Journal of Soil Science and Plant Nutrition, 2025)

Influences of Long-Term Fertilization on Phosphorus Forms and Availability Within Particle-Size Fractions in a Mollisol - Jinjing Zhang; Yuanhong Sun; Jiayi Tang; Cuilan Li; Mo Zhu; Ping Zhu (Journal of Soil Science and Plant Nutrition, 2025)

A prospective study on the regulation of osteoarthritis risk through inflammatory pathways in clonal hematopoiesis - Ping Li; Zijian Kang; Ruiqi Ma; Chen Zhu; Ying Zhu; Iris Tang; Jianzheng Zhang; Kai Li; Qiang Tong (GeroScience, 2025)

Chinese Tuina ameliorates muscle damage by regulating endoplasmic reticulum stress and autophagy in a rat model of skeletal muscle contusion - Hai-chao Liu; Hao-ming Zhu; Ming Li; Bo-rui Chen; Zheng-yu Yang; Yu Wang; Shi-zhong Wang; Shao-qing Chen; Jian-ping Lin (Tissue and Cell, 2025)

Corrigendum to “Rat-to-human PBPK model of U-47700: Unveiling pharmacokinetic risks of a synthetic opioid through interspecies extrapolation” [Toxicology and Applied Pharmacology, 499 (2025) 117352] - Lina Zhong; Longjie Li; Qingfeng He; Xiao Zhu; Ping Xiang; Xiaoqiang Xiang; Hui Yan (Toxicology and Applied Pharmacology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

A symbiotic bacterium regulates the detoxification metabolism of deltamethrin in Aedes albopictus - Si-jia Deng; Lei Tu; Lin Li; Ju-ping Hu; Ju-lin Li; Jian-xia Tang; Mei-chun Zhang; Guo-ding Zhu; Jun Cao (Pesticide Biochemistry and Physiology, 2025)

Isolation of pentasaccharide resin glycosides from the whole plants of Ipomoea biflora and their cytotoxic activities - Jin-Ping Gu; Tian-Zi Qi; Dong-Rong Zhu; Xu-Jia He; Su-Peng Guo; Xin Lan; Hong Gu; Jia-Lie Luo; Min Yang; Yu-Cheng Gu; Wen-Li Wang; Guang-Tong Chen; et al. (Phytochemistry, 2025)

Agronomic characteristics, objective quantitative, metabolome and transcriptome analysis reveal the influence of fertilization treatments on fresh leaf characteristics and finished tea quality - Liyue Yang; Xizhe Zhu; Ziming Yu; Bicheng Hu; Ping Liu; Fenglan Zhang; Ming Chen; Jinjin Wang; Youyi Huang; Haibo Yuan; Yeyun Li; Jinjie Hua (Food Chemistry, 2025)

Revealing the Oxidative Stress-Related Molecular Characteristics and Potential Therapeutic Targets of Schizophrenia through Integrated Gene Expression Data Analysis - Xiu-Mei Zhu; Ji Chen; Hua-Jie Ba; Chun Yang; Jian-Wei Liu; Rui Guo; Shi-Lin Li; Ping Huang; Cheng-Tao Li; Su-Hua Zhang (Molecular Neurobiology, 2025)

Leaf and Root Traits Show Contrasting Resource Exploitation Strategies, but Converge Along Elevation in the Hengduan Mountain Forests - Jie Song; Sebastian Seibold; Liang‐Liang Ma; Jia‐Yun Zou; Jie Liu; Ming‐Shu Zhu; Wei Zheng; Zhi‐Qiong Mo; Sheng‐Ping Ming; Jin Li; Kun Xu; De‐Zhu Li; et al. (Journal of Biogeography, 2025)
Aim The variations of leaf and root traits in communities are associated with above‐ and below‐ground resource exploitation strategies and are used to infer community assembly processes along environmental gradients. However, little is known about variations in leaf and root traits and their drivers along elevations in mountain forests. Location Yulong Mountain, southeastern Hengduan Mountains, Southwest China. Taxon Seed plants. Methods We measured six leaf traits and seven root traits across 47 woody species and collected environmental variables from forest plots along a 1200 m elevational gradient. We employed linear mixed models to examine how resource exploitation strategies (community‐weighted mean, CWM) and functional diversity (standardised effect size of RaoQ, SES.RaoQ) associated with leaf and root traits varied along elevations. Furthermore, we determined the relative effects of environmental variables on these metrics. Results We observed that the resource exploitation strategy of leaves shifted from an acquisitive to a conservative strategy (higher leaf carbon concentration) with increasing elevation. Conversely, root trait variation exhibited an opposite trend, shifting from a conservative to an acquisitive strategy (higher root branching intensity but lower root diameter and root tissue density) along elevations, potentially influenced by mycorrhizal interactions. We detected functional convergence for leaf and root traits across elevations, with a greater degree of functional convergence at high elevations. Leaf trait convergence was closely linked to soil nitrogen conditions, whereas root trait convergence was associated with soil organic carbon levels. Main Conclusions Our results highlight that the patterns of resource exploitation strategies along elevational gradients are decoupled for leaf and root traits, with distinct environmental factors shaping the convergence of root and leaf traits. We argue that forest communities in mountain ecosystems may modify their resource exploitation strategies and functional diversity through varying combinations of leaf and root traits to improve resilience to future global change.

A Dual-Functional NIR Fluorescent Probe for Detection SO2 Derivatives and Colorimetric Sensing pH as well as its Applications in Food Monitoring and Hepatoma Cells Imaging - Yu Zhu Yang; Lei Ao; Xiao Ping Mao; Gui Yong Li; Xiao Ye Luo; Huan Li Liu; Nan Jun Huang (Journal of Fluorescence, 2025)

A preliminary investigation of pore development mechanisms in highly matured solid bitumen: Implications from the Ediacaran Dengying Formation solid bitumen in the central Sichuan Basin, Southwest China - Lianqiang Zhu; Hui Tian; Peng Cheng; Haifeng Gai; Tengfei Li; Qin Zhou; Wei Wu; Chao Luo; Ping'an Peng (Marine and Petroleum Geology, 2025)

Selective and controllable mechanism of the temperature field in skin tissue under radiofrequency heating: finite element analysis and ex-vivo pig skin experiments - Ping Zhu; Chuanqi Xie; Kai Li; Fangjie Shu; Liqiang Li; Zhaodi Su; Yue Xue (Journal of Thermal Biology, 2025)

Avermectin induces photoreceptor functional impairment and color vision deficits in zebrafish (Danio rerio) - Wei-Guo Wang; Ming-Jun Yang; Zhu-Bo Sheng; Li-Ming Tao; Wen-Ping Xu; Yang Zhang (Journal of Hazardous Materials, 2025)

Effects of exogenous mineral silicon on physiological characteristics and arsenic uptake and transport in rice - Jing Han; Qihao He; Mingjing Lei; Ke Li; Yufei Zhou; Wenmin Li; Ying Xiao; Fan Zhang; Chang Sun; Jieying Wang; Jian Zhu; Zhiming Liu; et al. (Journal of Hazardous Materials, 2025)

Effects of pore structures of carbon paper on water management capability of a proton exchange membrane fuel cell - Yu-Ting Liu; Guo-Bao Huang; Xiao-Fang Zhang; Ting-Ting Yao; Li-Xia Cheng; Hong Zhu; Gang-Ping Wu (Fuel, 2025)

Catalytic-difference elucidating of hesperidin and naringin by Rhamnosidase and prunin production enhancing through enzyme mutation - Xinpeng Li; Ping Chen; Lin Chen; Sheng Gao; Zhendong Wang; Siming Zhu (Food Bioscience, 2025)

Mechanism study of the effects of astragaloside IV and quercetin on idiopathic pulmonary fibrosis - Ye Luo; Chang-jun Xu; Xing-hui Ai; Yu-ping Li; Xing Zhu; Chang-fu Yang (Journal of Natural Medicines, 2025)

Genetic diversity assessment and disease resistance gene identification of Yunnan rice landraces - Mei Li; Rongping Li; Yunxiu Yang; Xiaoqiao Zhu; Huiling Zhang; Yun-Yue Wang; Ping He; Guangyu Han (European Journal of Plant Pathology, 2025)

Rat-to-human PBPK model of U-47700: Unveiling pharmacokinetic risks of a synthetic opioid through interspecies extrapolation - Lina Zhong; Longjie Li; Qingfeng He; Xiao Zhu; Ping Xiang; Xiaoqiang Xiang; Hui Yan (Toxicology and Applied Pharmacology, 2025)

High-value use of whole plants of Eupatorium Adenophora Spreng for aluminium in hydrochloric acid anti-corrosion - Yun Gao; Ping Zhu; Xianghong Li; Liqing Tang; Yongqiang Chen; Yi Zhang; Juan Xu (Sustainable Chemistry and Pharmacy, 2025)

Great Oxidation Event was caused by Neoarchean global cratonization: opportunity and challenge from rock and sedimentary records in China - Li-Gang Zhou; Jun-Ping Liu; Jing Li; Zai-Bo Sun; Lu Xiang; Yan-Yan Zhou; Hao-Shu Tang; Yan-Bin Zhang; Xi-Yan Zhu; Hai-Long He; Ming-Guo Zhai (Science Bulletin, 2025)

Long-term effects of cropping regimes on soil organic carbon and aggregate stability in a Mollisol of Northeast China - Cuilan LI; Zhiyuan CAO; Mo ZHU; Hongjun GAO; Xiuzhi ZHANG; Ping ZHU; Jinjing ZHANG (Pedosphere, 2025)

Effects of early-life F-53B exposure on thyroid function in juvenile rats: The role of the cAMP signaling pathway - Shen-Pan Li; Wen-Hui Zhao; Jing Zhang; Wen-Ting Jiang; Jia-Yi Zhu; Yi-Xin Luo; Ping Xiang; Michael Bloom; Pasi Jalava; Guang-Hui Dong; Xiao-Wen Zeng (Journal of Hazardous Materials, 2025)

Highly efficient sulfur production in hydrogen sulfide conversion over Fe3O4 with {111} crystal facets: Unveiling the promotion of oxygen vacancies and basic sites - Li Yuan; Xiang Li; Langlang Wang; Ping Ning; Yuhang Xiao; Boyu Zhu; Yu Pu; Xueqian Wang (Journal of Hazardous Materials, 2025)

Impact of fermentation duration in fermented glutinous rice wine dough procedure on the staling of Chinese steamed bread - Jia-Xuan Shang; Jia-Xuan Li; Feng-Ping Qin; Yi-Peng Bai; Xiao-Na Guo; Ke-Xue Zhu; Jun-Jie Xing (Food Bioscience, 2025)

Transcriptome analysis reveals the mechanism of cortisol through GR regulating the expression of inflammatory cytokines in Siberian sturgeon (Acipenser baerii) after LPS treatment in vitro - Peng Tang; Yinqiu Chen; Defang Chen; Hao Zhu; Shaotong Dai; Jiawen Zhou; Xin Zhang; Xiaoli Huang; Ping Ouyang; Yi Geng; Zhiqiong Li (Fish & Shellfish Immunology, 2025)

Flexural behaviors of GFRP-reinforced Engineered Cementitious Composite (ECC)-concrete composite beams - Li-Hui Wang; Wen-Hao Shi; Lan-Ping Qian; Yu-Lei Bai; Shi-Zhu Liu; Zhan-Qun Yang (Engineering Structures, 2025)

Olaparib reverses prostate cancer resistance to Rapamycin by promoting macrophage polarization towards the M1 phenotype - Kai Ye; Gang Shi; Jian Xu; Kunyan Qiao; Qinghai Dai; Zhixiao Huo; Yu Cao; Wei Liu; Yue Hu; Lihua Yan; Yu Zhu; Ping Li; et al. (Molecular and Cellular Biochemistry, 2025)

Mass deposition of microbes from wildfire smoke to the sea surface microlayer - Siyao Yue; Yafang Cheng; Lishan Zheng; Senchao Lai; Shan Wang; Tianli Song; Linjie Li; Ping Li; Jialei Zhu; Meng Li; Lianfang Wei; Chaoqun Ma; et al. (Limnology and Oceanography, 2025)
Microbes in the sea surface microlayer (SML) are key to connecting the ocean and the atmosphere, affecting the exchange of matter, momentum, and heat at the interface. However, their sources have never been quantified systematically. Seawater has long been deemed their major source, whereas atmospheric deposition is regarded as trivial or merely providing additional nutrients. Here, combining atmospheric observations and quantitative budget analyses, we show that during the Indonesian peatland wildfire events the smoke can directly deposit abundant microbes into the SML, which can be comparable to the estimated supply from seawater and potentially diversify the microbial community of the SML. This land–air–ocean interaction is relevant for global climate, as it may induce previously unknown effects on the air–sea interactions, especially in an increasingly warming future with more intensifying wildfires.

ROS-responsive dextran-benzeneboronic acid pinacol ester micelles encapsulating edaravone for the treatment and mechanism of cerebral ischemia-reperfusion injury - Hexiang Zhao; Ping Yang; Mou Zhang; Wenshu Zheng; Renli Qi; Xiaofeng Zhu; Jinghui Li; Shipeng Li (Metabolic Brain Disease, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

PdRh bimetallic-loaded α-Fe2O3 nanospindles with Ppb-limit of 3-hydroxy-2-butanone biomarker detection: Particle dimension regulation and oxygen spillover effect - Xing-Yu Wang; Ping-Ping Liu; Hai-Jie Cai; Miao-Miao Li; Chun-Hui Deng; Yong Zhao; Zhao-Huan Zhang; Yong-Heng Zhu (Chemical Engineering Journal, 2025)

Validation of Interaction Between Sugarcane miR167d and Predicted Target Gene ScPUM1 and Analysis of Their Expression Under Cold Stress: A Novel Mechanism of miR167d - Qiqi Song; Pengjin Zhu; Jiahui Li; Qin Cheng; Qinliang Tan; Quanguang Zhou; Ping Lv; Zemei Nong (Journal of Plant Growth Regulation, 2025)

Penicipyrrolidines A−N, pyrrolidine derivatives with inhibitory effects on EMT and fibroblast activation from the mangrove-derived fungus Penicillium sp. DM27 - Li-Ming He; Xuan Deng; Li-Hua Ni; Shi-Qi Cai; Jinhu Chen; Zejin Liao; Mengke Zhang; Hua Shui; Kong-Kai Zhu; Song Wu; Ping Gao; Ariel M. Sarotti; et al. (Marine Life Science & Technology, 2025)

A Novel Multiplex Fluorescent PCR Assay for the Simultaneous Detection of Seven Aminoglycoside Resistance Genes - Peiyan He; Ping Li; Yong Yan; Guoying Zhu; Zhongwen Chen (Journal of Fluorescence, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

A new species of Pseudotsuga (Pinaceae) from the lower Miocene of Lesvos, Greece, and its palaeogeographical and palaeoclimatic implications - Yan-Bin Zhu; Ya Li; Jian-Ping Zhang; Yong-Dong Wang; Nikolaos Zouros (Palaeoworld, 2025)

Graph-based pangenome provides insights into structural variations and genetic basis of metabolic traits in potato - Xiaoling Zhu; Rui Yang; Qiqi Liang; Yuye Yu; Tingting Wang; Li Meng; Ping Wang; Shaoyang Wang; Xianping Li; Qiongfen Yang; Huachun Guo; Qijun Sui; et al. (Molecular Plant, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Urinary biomarkers of drinking water disinfection byproducts in relation to blood-based liver function parameters among reproductive-aged Chinese women - Ping-Ping Gui; Yan-Ling Deng; Min Zhang; Yu Miao; Peng-Hui Liu; Jia-Yue Zeng; Yang Wu; Cheng-Ru Li; Xiao-Ying Liu; Yang-Juan Li; Jin-Qin Zhu; A-Xue Liu; et al. (Science of The Total Environment, 2025)

Retraction notice to “Scorpion peptide LqhIT2 activates phenylpropanoid pathways via jasmonate to increase rice resistance to rice leafrollers” [Plant Sci. 230 (2015) 1–11] - Xiuzi Tianpei; Dong Li; Ping Qiu; Jie Luo; Yingguo Zhu; Shaoqing Li (Plant Science, 2025)

Experimental investigation on ammonia‑nitrogen adsorption performance of ZSM-5 molecular sieve prepared from coal gangue and fly ash - Qing-Wei Li; Ye-Rui Zhu; Li-Feng Ren; Wen-Ting Xu; Yu-Xin Miao; Yang Xiao; Cai-Ping Wang (Journal of Water Process Engineering, 2025)

Interactions between riverine sediment organic matter molecular structure and microbial community as regulated by heavy metals - Ping Li; Chun Liu; Lijie Zhang; Zhaoling Liu; Zhiyong Fu; Guanghui Fan; Yingjie Zhu; Yue Zuo; Liqiong Li; Lisha Zhang (Journal of Hazardous Materials, 2025)

Liubao insect tea polyphenols ameliorate DSS-induced experimental colitis by protecting intestinal barrier and regulating intestinal microbiota - Xinyu Feng; Yanwen Chen; Lina Luo; Zhoutao Fang; Shicheng Ma; Zhongxia Li; Jing Huang; Yani Pan; Helin Lv; Shuying Gong; Xiaodong Zheng; Fangyuan Fan; et al. (Food Chemistry, 2025)

Integrating three-primary-color and white long-lasting afterglows in triphenylene-doped polymers for time/space-resolved applications - Qian Wang; Xiao-Lei Xu; Meng-Yuan Zhu; Ya-Ping Du; Yu-Juan Ma; Jin-Hua Li; Guo-Ming Wang (Chemical Engineering Journal, 2025)

Underlying the early signaling and gene expression of Pleurotus ostreatus mycelia during injury response - Jiachun Zhu; Jiaqi Sun; Huiping Li; Ping Xu; Lin Ma; Qiang Wang; Keping Chen; Shaoxuan Qu (World Journal of Microbiology and Biotechnology, 2025)

Sex-biased juvenile hormone and gene expression underlie sex difference of stress resistance in the American cockroach - Fangfang Liu; Shudian Zhang; Ping Chen; Wei Tang; Xiaoyi Chen; Yingting Wu; Sishi Xia; Diqi Peng; Zhengyi Shao; Qin Li; Yuqing Liu; Xiaoshuai Zhang; et al. (Journal of Pest Science, 2025)

Evaluation of Enrichment Approaches for the Study of the Viromes in Mollusk Species - Tongling Chen; Tiantian Wu; Yunyi Hu; Zifeng Zhu; Ji Wu; Datao Lin; Xi Sun; Zhongdao Wu; Yi-Ping Li (Food and Environmental Virology, 2025)

Therapeutic Potential of TUBB6 Inhibition for Hematoma Reduction, Microtubule Stabilization, and Neurological Recovery in an In Vivo Model of Intracerebral Hemorrhage - Jun-Yao Huang; Qiang Ma; Ya-Jie Qi; Zhi-Yao Wang; Xiao-Guang Liu; Yi-Ming Zhu; Yu-Ping Li (NeuroMolecular Medicine, 2025)

Genome-wide identification and gene expression pattern reveal dominant digestive enzyme genes contributing to major enzyme activities during the molting cycle of the Chinese mitten crab, Eriocheir sinensis - Boxiang Zhu; Min Zhang; Mingjie Li; Kewu Pan; Ping Yao; Xin Zhang; Xugan Wu (Aquaculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

High Ca2+ concentrations enhance Microcystis colony formation through upregulating polysaccharide-, energy metabolism-, and transmembrane transport-related pathways - Ping Zhang; Yazhi Zhu; Chao Xiong; Yan Xiao; Kai Li; Han Wang (Harmful Algae, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

Inhibition of odor generation during the composting process of fecal sludge from rural toilets by decomposed compost backfilling - Lin Lin; Xingfeng Yang; Yilin Shen; Ping Zhu; Shiyu Niu; Shakib Alghashm; Guoji Ding; Deli Wu; Xiaowei Li (Bioresource Technology Reports, 2025)

High glucose induces renal tubular epithelial cell senescence by inhibiting autophagic flux - Ying Zhang; Yu Zhao; Yu-Qiu Liu; Ya-Ping Fang; Li Sun; Shan-Zhai Wei; Xiao-Dong Zhu; Xiao-Liang Zhang (Human Cell, 2025)

Effect of cortisol through GR regulated inflammatory cytokine expression and apoptosis of Siberian sturgeon (Acipenser baerii) after LPS treatment - Peng Tang; Hao Zhu; Defang Chen; Yinqiu Chen; Shuhuang Chen; Youlian Liu; Xin Zhang; Xiaoli Huang; Zhiqiong Li; Ping Ouyang; Yi Geng (Aquaculture, 2025)

NAGK regulates the onset of puberty in female mice - Wei Zhang; Ping Qin; Mengxian Li; Zhihao Pan; Zhuoya Wu; Yanyun Zhu; Ya Liu; Yunsheng Li; Fugui Fang (Theriogenology, 2025)

Penicipyrrolizidinones A−C, three pyrrolizidinone alkaloids with unprecedented skeletons from the mangrove-derived fungus Penicillium sp. DM27 - Zhenling Chen; Jing-Jing Zhang; Cheng-Yun Huang; Wei-Chen Chen; Li-Ming He; Qing-Qing Tang; Kong-Kai Zhu; Jing Li; Ping Gao; Meng-Ke Zhang; You-Sheng Cai (Phytochemistry, 2025)

Developed metabolomics approach reveals the non-volatile color-contributing metabolites during Keemun congou black tea processing - Mingchun Wen; Wei Hu; Lu Li; Piaopiao Long; Zisheng Han; Jia-Ping Ke; Zhiyang Deng; Mengting Zhu; Liang Zhang (Food Chemistry, 2025)

Investigating the application of multiple-stage fermented glutinous rice procedure in dough preparation for Chinese steamed bread - Jia-Xuan Li; Jia-Xuan Shang; Feng-Ping Qin; Xiao-Na Guo; Ke-Xue Zhu; Jun-Jie Xing (Food Bioscience, 2025)

Responses of microbial communities to the addition of different types of microplastics in agricultural soils - Ke Li; Qihao He; Jian Zhu; Jieying Wang; Chang Sun; Ao Tan; Xiaoqi Zhao; Yuanhao Peng; Chao Huang; Jingju Cai; Ping Wang; Zhiming Liu (Environmental Pollution, 2025)

Mechanochemical capture of organic bromine from hexabromocyclododecane (HBCD) and simultaneous selective lithium extraction from NCM cathode based on e-waste - Ping Zhu; Weidong Li; Haoran Jiang; Lingen Zhang (Chemical Engineering Journal, 2025)

Study on high-efficiency vanadium removement using sulfate radical-based AOPs and its oxidation mechanism of landfilled metallurgical residues - Jun Wang; Haoyu Li; Chunhua Hu; Xinyi He; Shihong Tian; Xuejun Zhu; Xuehua Mao; Yijia Zhang; Ping Liu (Chemical Engineering Journal, 2025)

Ultrahigh energy storage density and efficiency of antiferroelectric AgNbO3-based MLCCs via reducing the off-center cations displacement - Ting Tang; Dong Liu; Long Wang; Jiaze Li; Zheng Zhang; Lei Zhao; Bo-Ping Zhang; Li-Feng Zhu (Chemical Engineering Journal, 2025)

The complex interplay of flooding intensity and land use on soil microbial communities in riparian zones: Insights for ecological restoration - Kai Zhu; Fei Ye; Yu Mei; Weitao Jia; Xiai Zhu; Shuzhen Li; Shengjun Wu; Songlin Zhang; Ping Huang (CATENA, 2025)

Experimental Study of Starting Pressure Gradient in Carbonate Gas Reservoirs - Yao Zhu; Xiao-Ping Li; Li Liao; Da-Qiang Feng; Yu-Kun Mao; Jue-Qi Li; Ke-Jie Ye; Hao Zhang (Geotechnical and Geological Engineering, 2025)

A novel blood spot with oil sealing for antioxidation and completeness preservation of erythrocytes and hemoglobin - Genhan Zha; Xuan Xiao; Youli Tian; Hengying Zhu; Qiang Zhang; Changjie Yu; Honggen Li; Yuxing Wang; Chengxi Cao; Ping Chen (Analytica Chimica Acta, 2025)

Combined effect of polystyrene nanoparticles and chlorpyrifos to Daphnia magna - Yu-Hang Zhang; Rong-Yao Gao; Few Zhu; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2024)

Pollution status and assessment of seven heavy metals in the seawater and sediments of Hangzhou Bay, China - Rong Zhu; Yan-Yan Zeng; Li-Min Liu; Lu Yin; Kai-Ping Xu; Wei-Feng Chen; Shang-Chun Li; Xiao-Feng Zhou (Marine Pollution Bulletin, 2024)

Effects of nitrite exposure on the oxidative stress, immune response and intestine microbiota of Procambarus clarkii - Dan-Dan Bian; Yan-Xia Shi; Xi-Rong Zhu; Xiao-Li Sun; Xuan Xu; Lu Ding; Dai-Zhen Zhang; Qiu-Ning Liu; Bo-Ping Tang; Bao-Jian Zhu (Aquaculture, 2024)

The influence of steep faults at various avoidance distances on the stability of hard rock caverns: Physical model experiments and DEM simulations - Huai-sheng Xu; Shao-jun Li; Ding-ping Xu; Shi-jie Chen; Guang-liang Feng; Quan Jiang; Xin-hao Zhu; Shu-qian Duan (Tunnelling and Underground Space Technology, 2024)

Application of botulinum toxin A in tissue repair and regeneration - Xuan-Zhu Guo; Ya-Nan Niu; Xuan Zhou; Qiao Wei; Meng Li; Jia-Ning Xia; Yu-Qi Cui; Chao-Xin Chai; Yi-Ming Wang; Li-Ping Chen (Toxicon, 2024)

Conserved responses of water use to evaporative demand in mixed forest across seasons in low subtropical China - Li-Wei Zhu; Long-Wei Lu; Ping Zhao (Science of The Total Environment, 2024)

The SNARE protein CfSnc1 of Colletotrichum fructicola is a key regulator in fungal pathogenicity and responses to hypovirulence-associated mycovirus infection - Jun Zi Zhu; Ping Li; Xiao Gang Li; Jie Zhong (Postharvest Biology and Technology, 2024)

LncRNA MEG3 suppresses erastin-induced ferroptosis of chondrocytes via regulating miR-885-5p/SLC7A11 axis - Chongtao Zhu; Bin Chen; Xu He; Weiyuan Li; Shengyu Wang; Xun Zhu; Yan Li; Ping Wan; Xiaolu Li (Molecular Biology Reports, 2024)

Rapamycin protects mouse skin from ultraviolet B-induced photodamage by modulating Hspb2-mediated autophagy and apoptosis - Ang Li; Ai-Jun Chen; Jing Xu; Zhu-Yuan Wen; Gen-Long Bai; Zi-Yue Wang; Yu-Xin Jiang; Ping Wang (Molecular Biology Reports, 2024)

Microcolumn and coelution hydration of oil seal blood spot for efficient screening of newborn α-thalassemia via chip isoelectric focusing - Genhan Zha; Xuan Xiao; Youli Tian; Hengying Zhu; Ping Chen; Qiang Zhang; Changjie Yu; Honggen Li; Yuxing Wang; Chengxi Cao (Analytica Chimica Acta, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Comprehensive determination of fatty acids in real samples without derivatization by DMU-SPME-GC methods - Yun-Jiao Ma; Ping Li; Bei-Wei Zhu; Ming Du; Xian-Bing Xu (Food Research International, 2024)

Atomic modulation of FeN4 sites on hollow carbon nanospheres by neighboring Mn atoms for ultra-stable Zn-air batteries - Zhaowei Ji; Chenglong Qiu; Ping Li; Yifan Li; Jing Shi; Jingyi Wu; Yue Zhu; Wei Hu; Zhi Li; Huanlei Wang (Chemical Engineering Journal, 2024)

Short-term usage of proton pump inhibitors during admission was associated with increased risk of rehospitalization in critically ill patients with myocardial infarction: a cohort study - Jia-De Zhu; Li-Juan Yang; Jian-Nan Zhao; Ping Wang; Yi-Hua Li; Xue-Sha Zhang; Jian-Mei Pan; Meng-Han Jiang; Hai-Ying Yang; Sun-Jun Yin; Gong-Hao He (European Journal of Clinical Pharmacology, 2024)

Divergent chemical compositions of soil organic matter size fractions under long-term amendments across a climate gradient - Fanbo Song; Ning Hu; Yilai Lou; Huimin Zhang; Ping Zhu; Dongchu Li; Hongjun Gao; Shuiqing Zhang; Yidong Wang (Soil and Tillage Research, 2024)

Quorum sensing mediated response mechanism of anammox consortia to anionic surfactant: Molecular simulation and molecular evidence - Xue-Ping Wang; Na-Na Han; Zi-Yan Xu; Yu-Hui Zhu; Gui-Feng Li; Nian-Si Fan; Ren-Cun Jin (Science of The Total Environment, 2024)

Vitamin D receptor attenuates carbon tetrachloride-induced liver fibrosis via downregulation of YAP - Ping Wang; Jie Li; Mintao Ji; Jinjing Pan; Yanmei Cao; Yulin Kong; Li Zhu; Jiafu Li; Bingyan Li; Lei Chang; Zengli Zhang (Journal of Hazardous Materials, 2024)

Discovery of anti-melanogenic components in persimmon (Diospyros kaki) leaf using LC-MS/MS-MN, AlphaFold2-enabled virtual screening and biological validation - Jiazheng Liu; Ting Xu; Jianjun Ding; Haoyue Wen; Jieru Meng; Qing Liu; Xiaomei Liu; Wei Zhang; Guo-Yuan Zhu; Zhi-Hong Jiang; Jin Gao; Li-Ping Bai (Food Chemistry, 2024)

Multi-scenario application of chitosan emulsions as fat replacers: Based on the regulation of chitosan hydrophobicity and emulsion rheological properties - Cheng-Zhen Nie; Yao Li; Xu-Hui Huang; Hao-Peng Wang; Xu-Song Wang; Xiu-Ping Dong; Bei-Wei Zhu; Lei Qin (Food Hydrocolloids, 2024)

Characteristics and assembly mechanisms of bacterial and fungal communities in soils from Chinese forests across different climatic zones - Ming Sheng; Wei Hu; Cong-Qiang Liu; Mutong Niu; Rui Jin; Junjun Deng; Libin Wu; Ping Li; Zhifeng Yan; Yong-Guan Zhu; Pingqing Fu (CATENA, 2024)

Sensitivity of cloud microphysics to aerosol is highly associated with cloud water content: Implications for indirect radiative forcing - Yuan Wang; Hailing Jia; Ping Zhang; Fang Fang; Jiayi Li; Lei Zhu; Yang Wang; Tianshu Wang; Jiming Li (Atmospheric Research, 2024)

Plasma Zinc Levels in Patients with Diabetic Nephropathy: Is there a Relationship with NLRP3 Inflammasome Activation and Renal Prognosis? - Yuexin Zhu; Dedong Kang; Xiaoying Bai; Ping Luo; Bing Du; Bing Li (Biological Trace Element Research, 2024)

Simulating liquefaction-induced resuspension flux in a sediment transport model - Zichen Zhu; Xing Du; Bingchen Liang; Linfeng Wang; Yupeng Song; Ping Li; Yaoshen Fan; Shuhua Bian; Yongzhi Wang; Yongqiang Zhang; Bing Li (Water Research, 2024)

Mercury sources, transport, and transformation in rainfall-runoff processes: Mercury isotope approach - Ruolan Li; Junyao Yan; Chuan Wang; Shaochen Yang; Lin Zhang; Tao Peng; Wei Zhu; Ping Li; Leiming Zhang; Xinbin Feng (Water Research, 2024)

A citrullinated antigenic vaccine in treatment of autoimmune arthritis - Xu Jin; Tianya Dong; Qian Wang; Yang Xie; Xiangyu Fang; Chaonan Wei; Shuyan Liu; Xi Zheng; Ping Wang; Danxue Zhu; Lulu Cao; Suwei Dong; et al. (Science Bulletin, 2024)

Preparation of biomass artificial humic acid/hydrothermal carbon composite and its high-efficiency adsorption of norfloxacin - Wen Chen; Xin Li; Ping Zhao; Xiaping Zhu; Xiang Deng (Journal of Water Process Engineering, 2024)

The role of hydrogen-rich water in delaying the pulp breakdown of litchi fruit during postharvest storage - Huijun Gao; Feiyan Li; Xi Chen; Ziming You; Lei Wei; Yuanlong Liu; Ping Liu; Mingyang He; Min Hong; Hong Zhu; Xuewu Duan; Yueming Jiang; et al. (Food Chemistry, 2024)

Ionomer distribution control for improving the performance of proton exchange membrane fuel cells: Insights into structure–property relationships - Jingnan Song; Wutong Zhao; Haibo Wang; Hongjie Meng; Shukai Zhang; Wenkai Zhong; Xuefei Wu; Min Li; Panpan Guan; Ming Zhang; Lei Zhu; Ping He; et al. (Chemical Engineering Journal, 2024)

Local microenvironment modulation of zirconium-porphyrinic frameworks for CO2 reduction - Xue Zhao; Chang-Yan Zhu; Heng Rao; Dong-Ying Du; Min Zhang; Ping She; Li Li; Jun-Sheng Qin (Chemical Engineering Journal, 2024)

Microbial metabolic capacity regulates the accrual of mineral-associated organic carbon in subtropical paddy soils - Zhe Li; Xun Duan; Xiaobin Guo; Wei Gao; Yan Li; Ping Zhou; Qihong Zhu; Anthony G. O'Donnell; Ke Dai; Jinshui Wu (Soil Biology and Biochemistry, 2024)

Evaluation and obstacle analysis of sustainable development in small towns based on multi-source big data: A case study of 782 top small towns in China - Mingman Chen; Chen Chen; Chi Jin; Bo Li; Yingqing Zhang; Ping Zhu (Journal of Environmental Management, 2024)

Boosting the catalytic efficiency of sulfonated crosslinked-polyaniline organocatalyst for producing 5-hydroxymethylfurfural from fructose - Zhidan Xue; Ping Hu; Hui Li; Di Wu; Yimeng Guo; Hang Lv; Changwei Hu; Liangfang Zhu (Fuel, 2024)

Screening and verification of outer membrane proteins of Cronobacter sakazakii with potential adhesion capability to human ileocecal adenocarcinoma cells - Chumin Zhao; Ping Li; Yufei Fan; Dongdong Zhu; Jingbo Jiao; Yue Li; Zehui Xiao; Xinjun Du; Shuo Wang (Food Bioscience, 2024)

Cyanidin prevents cardiomyocyte apoptosis in mice after myocardial infarction - Deng Gang; Ouyang Qing; Yongzheng Yang; Muqaddas Masood; Yu-Hong Wang; Jiang Linhui; Su Haotao; Ge Li; Chi Liu; Moussa Ide Nasser; Ping Zhu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Efficacy and safety of dabigatran and rivaroxaban in atrial fibrillation patients with impaired liver function: a multicenter retrospective cohort study - Xinhai Huang; Wenlin Xu; Guilan Wu; Ruijuan Li; Ping Gu; Qiaowei Zheng; Xiumei Liu; Hengfen Dai; Xiangsheng Lin; Yuxin Liu; Xiaoming Du; Jun Su; et al. (European Journal of Clinical Pharmacology, 2024)

IGFBP2 induces podocyte apoptosis promoted by mitochondrial damage via integrin α5/FAK in diabetic kidney disease - Xiaochen Wang; Yifan Zhang; Kun Chi; Yuwei Ji; Keying Zhang; Ping Li; Zhangning Fu; Xu Wang; Shaoyuan Cui; Wanjun Shen; Guangyan Cai; Xiangmei Chen; et al. (Apoptosis, 2024)

Role of ginsenoside Rb1 in attenuating depression-like symptoms through astrocytic and microglial complement C3 pathway - Cheng-Fu Li; Qiu-Ping Zhang; Jie Cheng; Guang-Hui Xu; Ji-Xiao Zhu; Li-Tao Yi (Metabolic Brain Disease, 2024)

Energy-saving design of underground metro vertical alignment with deep reinforcement learning - Shuangting Xu; Tianci Gao; Dongying Yang; Xiaoyun Feng; Paul Schonfeld; Huailong Li; Ying Zhu; Ping Wang; Qing He (Tunnelling and Underground Space Technology, 2024)

Dynamic modulation of nodulation factor receptor levels by phosphorylation-mediated functional switch of a RING-type E3 ligase during legume nodulation - Hao Li; Yajuan Ou; Jidan Zhang; Kui Huang; Ping Wu; Xiaoli Guo; Hui Zhu; Yangrong Cao (Molecular Plant, 2024)

Efficient capture performance and mechanism of thiadiazole-functionalized covalent organic framework for Pb(II) ion - Dawei Xiang; Hao Wang; Shixing Wang; Manying Zhu; Yuefeng Chen; Xiang Liu; Ping Li; Likang Fu (Journal of Water Process Engineering, 2024)

Evolution of physicochemical and leaching characteristics of municipal solid waste incineration fly ash in China under ultra-low emission standard - Guangyuan Yao; Rongbin Xu; Zhu Liang; Ping Li; Ya Xu; Yuqiang Liu; Can Qian; Qifei Huang (Journal of Environmental Management, 2024)

Impact of soil density on biomineralization using EICP and MICP techniques for earthen sites consolidation - Jie Li; Feiqing Zhu; Fasi Wu; Yuxin Chen; Jenny Richards; Tianxiao Li; Ping Li; Dongjuan Shang; Jing Yu; Heather Viles; Qinglin Guo (Journal of Environmental Management, 2024)

Autonomous, temperature-enhanced oxidase-mimic multimodal antimicrobial film for prolonged preservation of perishable products - Liang Zhang; Wen He; Yiya Ping; Wenze Wang; Puyuan Hu; Bingzhi Li; Wenxin Zhu; Jing Sun; Yanwei Ji; Jianlong Wang (Chemical Engineering Journal, 2024)

Potential Plausible Role of Stem Cell for Treating Depressive Disorder: a Retrospective Review - Zhuo Chang; Qing-yi Wang; Lu-hao Li; Bei Jiang; Xue-ming Zhou; Hui Zhu; Yan-ping Sun; Xue Pan; Xu-xu Tu; Wei Wang; Chen-yue Liu; Hai-xue Kuang (Molecular Neurobiology, 2024)

Microstrip isoelectric focusing with deep learning for simultaneous screening of diabetes, anemia, and thalassemia - Haodong Fu; Youli Tian; Genhan Zha; Xuan Xiao; Hengying Zhu; Qiang Zhang; Changjie Yu; Wei Sun; Chang Ming Li; Li Wei; Ping Chen; Chengxi Cao (Analytica Chimica Acta, 2024)

Moniezia benedeni infection increases IgE+ cells in sheep (Ovis aries) small intestine - Jing Pan; Wan-Ling Yao; Li-Ping Liu; Bao-Shan Wang; Wen-Zhu Chai; Zhen Huang; Xi-Ping Fan; Wan-Hong He; Wen-Hui Wang; Wang-Dong Zhang (Veterinary Parasitology, 2024)

Developing novel ensemble models for predicting soil hydraulic properties in China’s arid region - Liantao Niu; Xiaoxu Jia; Xiangdong Li; Chunlei Zhao; Lidong Ren; Wei Hu; Ping Zhu; Danfeng Li; Baoqing Zhang; Ming'an Shao (Journal of Hydrology, 2024)

Investigating the multiscale associations between urban landscape patterns and PM1 pollution in China using a new combined framework - Huimin Zhu; Ping Zhang; Ning Wang; Fengqian Zhang; Wenjie Ma; Feng Wen; Mingyao Li; Yong Wang; Xin Fan; Kang Hou; Yuanyuan Han (Journal of Cleaner Production, 2024)

High-frequency monitoring during rainstorm events reveals nitrogen sources and transport in a rural catchment - Xuan Huang; Yi Zhu; Han Lin; Dongli She; Ping Li; Man Lang; Yongqiu Xia (Journal of Environmental Management, 2024)

Storm-tide and wave interaction at Puerto Rico during Hurricanes Irma and Maria - Qiang Chen; Yuepeng Li; David M. Kelly; Ping Zhu; Jamie Rhome; Cody Fritz (Continental Shelf Research, 2024)

Kidney-targeted antioxidant salvianolic acid B nanoparticles restoring lysosome homeostasis for acute kidney injury therapy - Jian-Li Chen; Xiao-Hui Jia; Xuan Wu; Ming-Heng Yuan; Xinyue Xia; Dan Yin; Xu Chen; Ze-Yun Gu; Jia-Zheng Liu; Li-Ping Bai; Kathy Qian Luo; Jianfang Wang; et al. (Chemical Engineering Journal, 2024)

Implantation of Adipose-Derived Mesenchymal Stromal Cells (ADSCs)-Lining Prosthetic Graft Promotes Vascular Regeneration in Monkeys and Pigs - Xiao Zuo; Pengfei Han; Ding Yuan; Ying Xiao; Yushi Huang; Rui Li; Xia Jiang; Li Feng; Yijun Li; Yaya Zhang; Ping Zhu; Hongge Wang; et al. (Tissue Engineering and Regenerative Medicine, 2024)
Background: Current replacement procedures for stenosis or occluded arteries using prosthetic grafts have serious limitations in clinical applications, particularly, endothelialization of the luminal surface is a long-standing unresolved problem. Method: We produced a cell-based hybrid vascular graft using a bioink engulfing adipose-derived mesenchymal stromal cells (ADSCs) and a 3D bioprinting process lining the ADSCs on the luminal surface of GORE-Tex grafts. The hybrid graft was implanted as an interposition conduit to replace a 3-cm-long segment of the infrarenal abdominal aorta in Rhesus monkeys. Results: Complete endothelium layer and smooth muscle layer were fully developed within 21 days post-implantation, along with normalized collagen deposition and crosslinking in the regenerated vasculature in all monkeys. The regenerated blood vessels showed normal functionality for the longest observation of more than 1650 days. The same procedure was also conducted in miniature pigs for the interposition replacement of a 10-cm-long right iliac artery and showed the same long-term effective and safe outcome. Conclusion: This cell-based vascular graft is ready to undergo clinical trials for human patients.

Soil warming alters tree water use and canopy stomatal conductance in a mixed subtropical forest - Weiting Hu; Christoph Bachofen; Yanqiong Li; Liwei Zhu; Ping Zhao; Charlotte Grossiord (Agricultural and Forest Meteorology, 2024)

Binding properties of chemosensory protein 4 in Riptortus pedestris to aggregation pheromones - Jin-Bu Li; Qiang Liu; Sai Ma; Yue-Ying Wang; Xing-Zhou Liu; Chao-Wei Wang; Da-Jiang Wang; Zhuang-Zhuang Hu; Jia-Wen Gan; Xiu-Yun Zhu; Bao-Ping Li; Mao-Zhu Yin; et al. (Pesticide Biochemistry and Physiology, 2024)

Microbial mechanisms of C/N/S geochemical cycling during low-water-level sediment remediation in urban rivers - Wen-Long Chen; Min Zhang; Jian-Guo Wang; Wei-Jie Huang; Qiong Wu; Xiao-Ping Zhu; Ning Li; Qian Wu; Wei Guo; Jun Chen (Journal of Environmental Management, 2024)

Three-dimensional multi-channel structure NiCo alloy used for boosting efficient overall water splitting - Fan Yang; Zelin Li; Fei Zhu; Xiaolong Chen; Songwei Ge; Fei Yin; Fairy Fan Yang; Rui Yang; Yanjing Liu; Lili Gao; Qiang Wang; Rui Feng; et al. (Fuel, 2024)

Maintenance of callus-associated endophyte balance to mitigate oxidative browning in plant tissue culture practices - Yu-Tao Wang; Chun-Xiao Chen; Ping Zhou; Chun-Xi Lu; Yun Wen; Yu Li; Xiao-Xia Pan; Shu-Sheng Zhu; Ming-Zhi Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Cevanine-type alkaloids from the bulbs of Fritillaria unibracteata var. wabuensis and their antifibrotic activities in vitro - Lu Fu; Wenyue Tian; Meng-Yu Bao; Zhiyan Liu; Wen-Jing Ren; Jiazheng Liu; Wei Zhang; Zhifeng Zhang; Jin Gao; Li-Ping Bai; Zhi-Hong Jiang; Guo-Yuan Zhu (Phytochemistry, 2024)

Association between exposure to outdoor artificial light at night during pregnancy and glucose homeostasis: A prospective cohort study - Lei Zhang; Haixia Wang; Ping Zu; Xinyu Li; Shuangshuang Ma; Yuanyuan Zhu; Tianqin Xie; Fangbiao Tao; Dao-min Zhu; Peng Zhu (Environmental Research, 2024)

Reasonable multi-functionality of cotton fabric with superior flame retardancy and antibacterial ability using ammonium diphosphate as cross-linker - Ruitong Qin; Lei Du; Hongyan Li; Zhu-Bao Shao; Zhiming Jiang; Ping Zhu (Chemical Engineering Journal, 2024)

An untargeted metabolomics analysis of the components of heartwood and sapwood in 4 fast-growing Chinese fir (Cunninghamia lanceolata (Lamb.) Hook) clones - Xiaoqin Yang; Liping Li; Xiaorui Yu; Yun Liu; Sida Xie; Guolei Zhu; Junming Xu; Ping Zhao (Trees, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

In Vitro and In Vivo Supplementation with Curcumin Promotes Hippocampal Neuronal Synapses Development in Rats by Inhibiting GSK-3β and Activating β-catenin - Yinhong Zhang; Jinghui Yang; Yanling Gong; Shan He; Ping Wen; Yan Jiang; Jing He; Baosheng Zhu; Li Li (Molecular Neurobiology, 2024)

Remote effects of Tibetan Plateau spring land temperature on global subseasonal to seasonal precipitation prediction and comparison with effects of sea surface temperature: the GEWEX/LS4P Phase I experiment - Yongkang Xue; Ismaila Diallo; Aaron A. Boone; Yang Zhang; Xubin Zeng; William K. M. Lau; J. David Neelin; Tandong Yao; Qi Tang; Tomonori Sato; Myung-Seo Koo; Frederic Vitart; et al. (Climate Dynamics, 2024)
The prediction skill for precipitation anomalies in late spring and summer months—a significant component of extreme climate events—has remained stubbornly low for years. This paper presents a new idea that utilizes information on boreal spring land surface temperature/subsurface temperature (LST/SUBT) anomalies over the Tibetan Plateau (TP) to improve prediction of subsequent summer droughts/floods over several regions over the world, East Asia and North America in particular. The work was performed in the framework of the GEWEX/LS4P Phase I (LS4P-I) experiment, which focused on whether the TP LST/SUBT provides an additional source for subseasonal-to-seasonal (S2S) predictability. The summer 2003, when there were severe drought/flood over the southern/northern part of the Yangtze River basin, respectively, has been selected as the focus case. With the newly developed LST/SUBT initialization method, the observed surface temperature anomaly over the TP has been partially produced by the LS4P-I model ensemble mean, and 8 hotspot regions in the world were identified where June precipitation is significantly associated with anomalies of May TP land temperature. Consideration of the TP LST/SUBT effect has produced about 25–50% of observed precipitation anomalies in most hotspot regions. The multiple models have shown more consistency in the hotspot regions along the Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train. The mechanisms for the LST/SUBT effect on the 2003 drought over the southern part of the Yangtze River Basin are discussed. For comparison, the global SST effect has also been tested and 6 regions with significant SST effects were identified in the 2003 case, explaining about 25–50% of precipitation anomalies over most of these regions. This study suggests that the TP LST/SUBT effect is a first-order source of S2S precipitation predictability, and hence it is comparable to that of the SST effect. With the completion of the LS4P-I, the LS4P-II has been launched and the LS4P-II protocol is briefly presented.

Induced Mesenchymal Stem Cells-Small Extracellular Vesicles Alleviate Post-stroke Cognitive Impairment by Rejuvenating Senescence of Neural Stem Cells - Jiayuan Liu; Li Peng; Lingwei He; Tianyue Yin; Yuhao Du; Mengmeng Yang; Ping Wu; Jun Li; Jiangbing Cao; Hongrui Zhu; Sheng Wang (Journal of Molecular Neuroscience, 2024)

Real-time detection and counting of wheat ears based on improved YOLOv7 - Zanpeng Li; Yanjun Zhu; Shunshun Sui; Yonghao Zhao; Ping Liu; Xiang Li (Computers and Electronics in Agriculture, 2024)

Hepatotoxic of polystyrene microplastics in aged mice: Focus on the role of gastrointestinal transformation and AMPK/FoxO pathway - Pengfei Xie; Pengcheng Li; Xiaoshan Zhu; Deshan Chen; Mohammad Mehdi Ommati; Hongwei Wang; Lei Han; Shixiao Xu; Ping Sun (Science of The Total Environment, 2024)

Insight into using hydrochar to alleviate ammonia nitrogen inhibition during anaerobic digestion of waste activated sludge: Performance, metagenomic and metabolomic signatures - Lin Wang; Yunpeng He; Yuting Zhu; Qian Ping; Yongmei Li (Science of The Total Environment, 2024)

Evolution of groundwater hydrochemical characteristics and formation mechanism during groundwater recharge: A case study in the Hutuo River alluvial–pluvial fan, North China Plain - Ping Wang; Wei Zhang; Yuchen Zhu; Yaci Liu; Yasong Li; Shengwei Cao; Qichen Hao; Shenghua Liu; Xiangke Kong; Zhantao Han; Binghua Li (Science of The Total Environment, 2024)

Decoding silkworm spinning programmed by pH and metal ions - Kai Song; Yejing Wang; Wenjie Dong; Zhenzhen Li; Qingyou Xia; Ping Zhu; Huawei He (Science Bulletin, 2024)

Enhanced NOx absorption in flue gas by wet oxidation of red mud and phosphorus sludge - Bin Li; Shuai Liu; Hengxi Zhu; Wenmin Qian; Pan Wang; Ruihao Yang; Jin Zhang; Qihong Cen; Zewei Liu; Ping Ning (Journal of Hazardous Materials, 2024)

Identification, characterization and the inflammatory regulating effect of NOD1/2 in sturgeon - Defang Chen; Hao Zhu; Lu Lu; Yinqiu Chen; Xin Zhang; Xiaoli Huang; Ping Ouyang; Yi Geng; Zhiqiong Li (Fish & Shellfish Immunology, 2024)

Unraveling the critical roles of surface chemical states on anion exchange of halide perovskites - Fanghao Ye; Mengyao Tian; Xi Lan; Junzi Li; Ming Wang; Siyang Liu; Mingchao Zhu; Zhiqing Zhang; Hang Zhou; Tingchao He; Ping Xu; Guijun Li (Chemical Engineering Journal, 2024)

Long-term Fertilizer Application Induces Changes in Carbon Storage and Distribution, and the Consequent Color of Black soil - Jichao Gao; Lichun Wang; Jiafa Luo; Hongjun Gao; Weiwen Qiu; Qiang Li; Xiuzhi Zhang; Ping Zhu; Chang Peng; Yunfei Jiao; Lingying Xu (Journal of Soil Science and Plant Nutrition, 2024)

Heat shock induces HuR-dependent MKP-1 posttranslational regulation through the p38 MAPK signaling cascade - Xiao-juan Ma; Zhan Sun; Yi-ping Wang; Xue-ping Yao; Ting-ting Luo; Ya-li Bao; Dina Ainiwaer; Tian Zhang; Hengyi Zhu; Yan Zhang; Fei-ming Hu; Wen-yan Yu (Tissue and Cell, 2024)

Iridoid and lignan glycosides from Lancea tibetica - Yi Zhu; Junlin Wang; Lu Tang; Yuxin Shang; Weiyi Zhao; Wei Zhang; Ping Hai; Yongbiao Zheng; Wenbo Li; Yanfang Su (Phytochemistry Letters, 2024)

Oxygen vacancy-enriched Cu/CeO2–ZrO2 catalyst with highly dispersed Cu0 towards plasma catalytic advanced CO2 utilization - Zhiyuan Ning; Leicheng Wen; Ruoran Li; Kai Xin; Pan Liu; Li Liu; Yinan Sun; Yiming Zhu; Ping Ning (Journal of Cleaner Production, 2024)

Efficient recovery of iron from anaerobic roasted cyanide tailings using advanced oxidation technology - Ping Dong; Yonghui Song; Lei Wu; Jin Bao; Ning Yin; Rongyan Zhu; Yifan Li; Hefu Li (Hydrometallurgy, 2024)

Effects of mixed normative feedback strategies on residents' energy conservation in shared spaces - Jiaolan Zhu; Jie Li; Ping Liu; Yongtao Shang; Zhikun Ding; Md Morshed Alam (Energy and Buildings, 2024)

Synergistic enhanced kinetics and dual active sites in PANI@V2O5 nanoflower for superior Ca2+ ion storage - Ping Luo; Dongyao Zhu; Chunli Zuo; Wenwei Zhang; Ming Li; Feiyang Chao; Gongtao Yu; Wenhui Zhong; Qinyou An (Chemical Engineering Journal, 2024)

Superfast hydrous-molten salt erosion to fabricate large-size self-supported electrodes for industrial-level current OER - Jie Deng; Zhichao Wang; Hao Yang; Rui Jian; Yufeng Zhang; Ping Xia; Wei Liu; Olivier Fontaine; Yachao Zhu; Luming Li; Si Chen (Chemical Engineering Journal, 2024)

Fluorogenic RNA aptamer output sensors via transcription activated by recombinase polymerase amplification for nucleic acid testing - Jiajie Liang; Xin Liu; Wei Xiao; Peijun Teng; Ping Guan; Wanli Liang; Liangshan Hu; Guanbo He; Haorong He; Gan Li; Siyi Zou; Cheng Lu; et al. (Chemical Engineering Journal, 2024)

Fabrication of robust mechanical NiCo nanocubes for lithium metal anode with superior high rate performance - Yi-Han Song; Yan-Fei Li; Jian Lin; Guo-Duo Yang; Xing-Long Wu; Jing-Ping Zhang; Hai-Zhu Sun; Liang Zhao (Chemical Engineering Journal, 2024)

Soil erosion sensitivity and prediction for hilly areas of Hubei Province, China, using combined RUSLE and LSTM models - Yaodong Ping; Pei Tian; Li Luo; Yahui Guo; Yuwei Gong; Zhanliang Zhu; Yongsheng Cui; Lin Chen (Journal of Soils and Sediments, 2024)

Generalist and topologically central avian frugivores promote plant invasion unequally across land‐bridge islands - Chen Zhu; Bo Dalsgaard; Wande Li; Fernando Gonçalves; Maximilian G. R. Vollstädt; Peng Ren; Xue Zhang; Junjie Shao; Ping Ding; Xingfeng Si (Ecology, 2024)
Seed dispersal by frugivorous birds facilitates plant invasions, but it is poorly known how invasive plants integrate into native communities in fragmented landscapes. We surveyed plant–frugivore interactions, including an invasive plant ( Phytolacca americana ), on 22 artificial land‐bridge islands (fragmented forests) in the Thousand Island Lake, China. Focusing on frugivory interactions that may lead to seed dispersal, we built ecological networks of studied islands both at the local island (community) and at landscape (metacommunity) levels. On islands with P. americana , we found that P. americana impacted local avian frugivory networks more on islands with species‐poor plant communities and on isolated islands. Moreover, as P. americana interacted mainly with local core birds (generalists), this indicates reduced seed dispersal of native plants on invaded islands. At the landscape level, P. americana had established strong interactions with generalist birds that largely maintain seed‐dispersal functions across islands, as revealed by their topologically central roles both in the regional plant–bird trophic network and in the spatial metanetwork. This indicates that generalist frugivorous birds may have facilitated the dispersal of P. americana across islands, making P. americana well integrated into the plant–frugivore mutualistic metacommunity. Taken together, our study demonstrates that the impact of plant invasion is context‐dependent and that generalist native frugivores with high dispersal potential may accelerate plant invasion in fragmented landscapes. These findings highlight the importance of taking the functional roles of animal mutualists and habitat fragmentation into account when managing plant invasions and their impact on native communities.

Blue carbon development in China: realistic foundation, internal demands, and the construction of blue carbon market trading mode - Ping Li; Dahai Liu; Chao Liu; Xiaoxuan Li; Zhenhang Liu; Yanjing Zhu; Bo Peng (Frontiers in Marine Science, 2024)
Promoting the inclusion of blue carbon in market trading is crucial for recognizing its value and protecting the marine ecological environment. However, China currently does not have an internationally influential blue carbon market trading platform, which hampers the transmission of supply and demand in the blue carbon market and prevents the realization of blue carbon value. In this study, we analyze the feasibility and necessity of establishing a trading mode for the blue carbon market in China. The introduction of futures trading in the blue carbon market’s trading mode allows for the use of futures pricing methods and multiple financial instruments to address the challenges of income cost mismatch in blue carbon project development. The paper also discusses key strategies for the development of China’s blue carbon market, including the creation of a blue carbon trading methodology, the improvement of preservation and appreciation mechanisms, and the establishment of a unified trading platform. These strategies aim to provide intellectual support and decision-making reference for the construction of the market.

Adaptive evolution in asymptomatic host confers MDR Salmonella with enhanced environmental persistence and virulence - Bing He; Ting-ting Zhu; Yin Liang; Hai-jing Wei; Zi-lei Huang; Li-jie Liang; Jia-hao Zhong; Yang Luo; Xin-lei Lian; Dong-hao Zhao; Xiao-ping Liao; Ya-hong Liu; et al. (Science of The Total Environment, 2024)

Whole-cell bioreporter application for rapid evaluation of hazardous metal bioavailability and toxicity in bioprocess - Xiaokai Zhang; Yi Zhu; Evrim Elçin; Lizhi He; Boling Li; Mengyuan Jiang; Xing Yang; Xiu-Ping Yan; Xu Zhao; Zhenyu Wang; Fang Wang; Sabry M. Shaheen; et al. (Journal of Hazardous Materials, 2024)

Multidentate anchoring strategy for synergistically modulating crystallization and stability towards efficient perovskite solar cells - Ping Hu; Wenbo Zhou; Junliang Chen; Xin Xie; Jingwei Zhu; Yuxin Zheng; Yafeng Li; Junming Li; Mingdeng Wei (Chemical Engineering Journal, 2024)

Achieving ultrahigh energy storage density and efficiency above 90% via reducing defect concentrations for AgNbO3-based multilayer capacitors - Dekai Shi; Dong Liu; Lei Zhao; Qi Wang; Ting Tang; Xinyue Long; Liqin Yan; Bo-Ping Zhang; He Qi; Li-Feng Zhu (Chemical Engineering Journal, 2024)

Rosmarinic acid against cognitive impairment via RACK1/HIF-1α regulated microglial polarization in sepsis-surviving mice - Dan-yang Liu; Yao Wu; Zi-qi Feng; Yang Yu; Hua-wei Cai; Shi-ping Liao; Tao Zeng; Ling Zhu; Xia Wang; Li-hong Wan (Chemico-Biological Interactions, 2024)

The effects of Spinosad on zebrafish larvae and THP-1 cells: Associated with immune cell damage and NF-kappa B signaling pathway activation - Wei-Guo Wang; Shou-Qian Xiong; Jin Lu; Lian-Hua Zhu; Cheng Zhang; Jia-Gao Cheng; Zhong Li; Wen-Ping Xu; Li-Ming Tao; Yang Zhang (Chemosphere, 2023)

Clarification of the phosphorus release mechanism for recovering phosphorus from biofilm sludge in alternating aerobic/anaerobic biofilm system - Hao Zhang; Shuang-Shuang Zhang; Wei Zhang; Wu-Cheng Ma; Yang Pan; Lin Chen; Liang Zhu; Yi-Ping Li; Jing-Ru Li (Science of The Total Environment, 2023)

The MPK6-LTF1L1 module regulates lignin biosynthesis in rice through a distinct mechanism from Populus LTF1 - Ping Zhu; Yu Zhong; Laifu Luo; Junhui Shen; Jiayan Sun; Laigeng Li; Longjun Cheng; Jinshan Gui (Plant Science, 2023)

Enhanced resuscitation of anammox granular sludge by adding folate: A perspective from the growth factor - Chao Pan; Leiyan Guo; Yang Yu; Wenji Li; Dongdong Xu; Wenda Chen; Lin Zhu; Baolan Hu; Ping Zheng; Meng Zhang (Chemical Engineering Journal, 2023)

Streamflow forecasting method with a hybrid physical process-mathematical statistic - Sen Wang; Ping-an Zhong; Feilin Zhu; Bin Xu; Jieyu Li; Xinyuan Qian; Bin Wang (Stochastic Environmental Research and Risk Assessment, 2023)

Comparative metabolomics analysis investigating the impact of melatonin-enriched diet on energy metabolism in the crayfish, Cherax destructor - Ying Yang; Jiangtao Tian; Wenyue Xu; Cuobaima Ping; Xinglin Du; Yucong Ye; Bihong Zhu; Yizhou Huang; Yiming Li; Qichen Jiang; Yunlong Zhao (Journal of Comparative Physiology B, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Lindenane sesquiterpenoid dimers from Chloranthus holostegius with anti-neuroinflammatory activities in BV-2 microglia - Zhao-Chun Zhan; Yi-Ping Xia; Qing Tang; Hui-Hui Zhu; Jing-Yi Du; Jun-Xing Cai; Yan-Jun Chen; Zhong-Nan Wu; Yao-Lan Li; Neng-Hua Chen; Guo-Cai Wang; Yu-Bo Zhang (Phytochemistry, 2023)

Genetic variations of CYP3A4 on the metabolism of itraconazole in vitro - Sai-li Xie; Xiayan Zhu; Nanyong Gao; Qianmeng Lin; Chaojie Chen; Yun-jun Yang; Jian-ping Cai; Guo-xin Hu; Ren-ai Xu (Food and Chemical Toxicology, 2023)

Regulation of renal lipid deposition in diabetic nephropathy on morroniside via inhibition of NF-KB/TNF-a/SREBP1c signaling pathway - Wenhui Zhu; Ming Chen; Yang Wang; Yao Chen; Yonggang Zhang; Yan Wang; Peng Liu; Ping Li (Chemico-Biological Interactions, 2023)

The effects of boundary layer vertical turbulent diffusivity on the tropical cyclone intensity - Lei Ye; Yubin Li; Ping Zhu; Zhiqiu Gao (Atmospheric Research, 2023)

Arbuscular mycorrhiza changes plant facilitation patterns and increases resource use efficiency in intercropped annual plants - Shuang-Guo Zhu; Hai-Xia Duan; Hong-Yan Tao; Li Zhu; Rui Zhou; Yu-Miao Yang; Xiao-Lin Zhang; Wen-Ying Wang; Hao Zhu; Wei Zhang; Ren-Qing Wang; Xiu-Ping Tao; et al. (Applied Soil Ecology, 2023)

Regulation of microbial metabolism on the formation of characteristic flavor and quality formation in the traditional fish sauce during fermentation: a review - Jiarun Han; Tao Kong; Qi Wang; Jialan Jiang; Qingqing Zhou; Ping Li; Beiwei Zhu; Qing Gu (Critical Reviews in Food Science and Nutrition, 2023)

Systematic evaluation of ramie (Boehmeria nivea L.) for phytoremediation of cadmium contaminated soil and the mechanism of microbial regulation - Kunmei Chen; Yulan Li; Chunming Yu; Ping Chen; Jikang Chen; Gang Gao; Xiaofei Wang; Heping Xiong; Aiguo Zhu (Chemosphere, 2023)

Effects of interspecific interactions on soil carbon emission and efficiency in the semiarid intercropping systems - Wei Wang; Meng-Ying Li; Rui Zhou; Shuang-Guo Zhu; Hong-Yan Tao; Aziz Khan; Aimee Grace Uzamurera; Bao-Zhong Wang; Jun-Ming Jin; Yue Ma; Wen-Bo Li; Xiu-Ping Tao; et al. (Soil and Tillage Research, 2023)

Spatial and molecular variations in forest topsoil dissolved organic matter as revealed by FT-ICR mass spectrometry - Ming Sheng; Shuang Chen; Cong-Qiang Liu; Qinglong Fu; Donghuan Zhang; Wei Hu; Junjun Deng; Libin Wu; Ping Li; Zhifeng Yan; Yong-Guan Zhu; Pingqing Fu (Science of The Total Environment, 2023)

Innovative pyrite-based constructed wetland-microbial fuel cell for enhancing nutrients removal and bioelectricity generation - Zhi-Wei Zhu; Pei Xu; Li Yu; Xian-Huai Huang; Hou-Yun Yang; Wei-Hua Li; Ping Zhang; Jian Chen; Ling-Tao Kong (Journal of Water Process Engineering, 2023)

Recovering phosphorus and lithium separately from wastewater and brine using a novel coupled biofilm-precipitation system - Hao Zhang; Shuang-Shuang Zhang; Wei Zhang; Wu-Cheng Ma; Yi-Ping Li; Lin Chen; Liang Zhu; Yang Pan (Journal of Water Process Engineering, 2023)

Defluorination and directional conversion to light fuel by lithium synergistic vacuum catalytic co-pyrolysis for electrolyte and polyvinylidene fluoride in spent lithium-ion batteries - Yu Zhang; Xiaoqiao Zhang; Ping Zhu; Weidong Li; Lingen Zhang (Journal of Hazardous Materials, 2023)

Fabrication of multi-morphological Bi2O2(OH)NO3-BiVO4 Z-Scheme heterojunction for enhanced photocatalytic antibiotic removal performance - Jinhai Li; Chenyu Wang; Jianhai Zhou; Zhang Ping; Guopei Huang; Yuanhui Wu; Shuxing Luo; Dongmei Bao; Zhu Wen; Pili Lu (Journal of Environmental Chemical Engineering, 2023)

Purification mechanism of fluoride-containing sludge from different sources by hydrometallurgy - Ping Zhu; Yuan Li; Bin Xia; Bilal; Yunfeng Xu; Qianzhi Zhang; Qiang Liu (Journal of Environmental Chemical Engineering, 2023)

Leaf senescence, nitrogen remobilization, and productivity of maize in two semiarid intercropping systems - Wei Wang; Meng-Ying Li; Rui Zhou; Fei Mo; Aziz Khan; Asfa Batool; Wei Zhang; Jun-Sheng Lu; Ying Zhu; Bao-Zhong Wang; Yu-Miao Yang; Jing Wang; et al. (European Journal of Agronomy, 2023)

Widespread arboreal foraging behavior in ground-dwelling birds and the urgency of life-history studies - Wande Li; Chen Zhu; Ingo Grass; Peng Han; Yao Shen; Ping Ding; Xingfeng Si (Biological Conservation, 2023)

Ambient black carbon variations and emission characteristics of typical Chinese vessels in the Yangtze River Delta, China - Puzhen Zhang; Chen Guo; Yongjie Wei; Zhanshan Wang; Zhigang Li; Yan Qian; Xiaoqian Li; Xiaojing Zhu; Ping Xu; Jun Shen; Wenchao Xue; Jun Hu (Environmental Science and Pollution Research, 2023)

A self-assembled nanoparticle vaccine based on pseudorabies virus glycoprotein D induces potent protective immunity against pseudorabies virus infection - Xujiao Ren; Nan Cao; Linxing Tian; Wenqiang Liu; Hechao Zhu; Zhenxiang Rong; Manman Yao; Xiangmin Li; Ping Qian (Veterinary Microbiology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Temporal framework for the Yanliao Biota and timing of the origin of crown mammals - Zhiqiang Yu; Haibing Wang; Chi Zhang; Liping Dong; Magdalena H. Huyskens; Zexian Cui; Paige Cary; Yankun Di; Yuri Amelin; Gang Li; Qiuli Li; Xiao-Ping Xia; et al. (Earth and Planetary Science Letters, 2023)

In situ deposition of double Fe-based Fenton catalysts on the porous membrane for the development of multi-defense against various foulants toward highly efficient water purification - Yu-Ling Yang; Gang Wang; Ping Zhu; Lei Tang; Zhi-Xiang Zeng; Li-Jing Zhu (Chemical Engineering Journal, 2023)

Plant facilitation improves carbon production efficiency while reducing nitrogen input in semiarid agroecosystem - Wei Wang; Meng-Ying Li; Shuang-Guo Zhu; Aziz Khan; Xiu-Ping Tao; Guang-Fu Huang; Hai-Ying Liu; Wei Zhang; Hong-Yan Tao; Dong-Shan Gong; Chao Song; You-Cai Xiong (CATENA, 2023)

Simultaneous phosphorus recovery from wastewater and sludge by a novel denitrifying phosphorus removal system - Hao Zhang; Wei Zhang; Shuang-Shuang Zhang; Wu-Cheng Ma; Liang Zhu; Yi-Ping Li; Yang Pan; Lin Chen (Bioresource Technology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Quantitative evaluation for the sources and aging processes of organic aerosols in urban Guangzhou: Insights from a comprehensive method of dual‑carbon isotopes and macro tracers - Fan Jiang; Junwen Liu; Zhineng Cheng; Ping Ding; Sanyuan Zhu; Xin Yuan; Wei Chen; Zhisheng Zhang; Zheng Zong; Chongguo Tian; Weiwei Hu; Junyu Zheng; et al. (Science of The Total Environment, 2023)

NIR- and pH-responsive injectable nanocomposite alginate-graft-dopamine hydrogel for melanoma suppression and wound repair - Ping Li; Yang Li; Rongzhan Fu; Zhiguang Duan; Chenhui Zhu; Daidi Fan (Carbohydrate Polymers, 2023)

Compound-specific radiocarbon analysis of benzene polycarboxylic acids for source apportionment of polyaromatic organic matter in ambient aerosols - Xin Yi; Xiaofei Geng; Yangzhi Mo; Guangcai Zhong; Jiao Tang; Sanyuan Zhu; Zhineng Cheng; Shizhen Zhao; Jun Li; Örjan Gustafsson; Ping'an Peng; Gan Zhang (Atmospheric Environment, 2023)

Identification of table grapes in the natural environment based on an improved Yolov5 and localization of picking points - Yanjun Zhu; Shuangshuang Li; Wensheng Du; Yuanpeng Du; Ping Liu; Xiang Li (Precision Agriculture, 2023)

Effects and mechanisms of natural products on Alzheimer’s disease - Zhijun Yang; Dan-Dan Zhou; Si-Yu Huang; Ai-Ping Fang; Hua-Bin Li; Hui-Lian Zhu (Critical Reviews in Food Science and Nutrition, 2023)

Heavy metals immobilization of ternary geopolymer based on nickel slag, lithium slag and metakaolin - Jinyuan Fan; Jiahao Yan; Mengya Zhou; Yuan Xu; Yuwei Lu; Ping Duan; Yingcan Zhu; Zuhua Zhang; Wengui Li; Aiguo Wang; Daosheng Sun (Journal of Hazardous Materials, 2023)

Green organic-inorganic coatings for flexible polyurethane foams: Evaluation of the effects on flame retardancy, antibacterial activity, and ideal mechanical properties - Ping Li; Xu-Chen Jiang; Wan-Meng Song; Li-Yao Zhang; Ying-Jun Xu; Yun Liu; Ping Zhu (Journal of Cleaner Production, 2023)

Probing the formation of soluble humins in catalytic dehydration of fructose to 5-hydroxymethylfurfural over HZSM-5 catalyst - Linzhen Li; Yexin Hu; Hui Li; Ping Hu; Zhidan Xue; Di Wu; Changwei Hu; Liangfang Zhu (Fuel, 2023)

Environmental controls on transpiration of Schima superba trees with different tree sizes under ten years’ climate fluctuations in south subtropics, China - Yanqiong Li; Liwei Zhu; Lei Ouyang; Xiuhua Zhao; Ping Zhao (Forest Ecology and Management, 2023)

Baicalein sensitizes triple negative breast cancer MDA-MB-231 cells to doxorubicin via autophagy-mediated down-regulation of CDK1 - Fang Hua; Yi-Yi Xiao; Xin-Hui Qu; Shan-Shan Li; Kun Zhang; Chao Zhou; Jian-Le He; Ye Zhu; Yu-Ying Wan; Li-Ping Jiang; Fang-Fang Tou; Xiao-Jian Han (Molecular and Cellular Biochemistry, 2023)

CircBLNK regulates tumor proliferation and apoptosis by miR-578/ING5 axis in non-small cell lung cancer - Ping Li; Liuyi Zou; Zuojun Luo; Yuhua Lu; Shuang Yu; Yujun Zhu; Yong Xie (Molecular & Cellular Toxicology, 2023)

Novel biphasic mechanism of the canonical Wnt signalling component PYGO2 promotes cardiomyocyte differentiation from hUC-MSCs - Yan Shi; Bin Qin; Xiongwei Fan; Yongqing Li; Yuequn Wang; Wuzhou Yuan; Zhigang Jiang; Ping Zhu; Jimei Chen; Yu Chen; Fang Li; Yongqi Wan; et al. (Cell and Tissue Research, 2023)
Human umbilical cord–derived mesenchymal stem cells (hUC-MSCs) are used to regenerate the myocardium during cardiac repair after myocardial infarction. However, the regulatory mechanism underlying their ability to form mesodermal cells and differentiate into cardiomyocytes remains unclear. Here, we established a human-derived MSCs line isolated from healthy umbilical cords and established a cell model of the natural state to examine the differentiation of hUC-MSCs into cardiomyocytes. Quantitative RT-PCR, western blotting, immunofluorescence, flow cytometry, RNA Seq, and inhibitors of canonical Wnt signalling were used to detect the germ-layer markers T and MIXL1 ; the markers of cardiac progenitor cells MESP1 , GATA4 , and NKX2.5 and the cardiomyocyte-marker cTnT to identify the molecular mechanism associated with PYGO2, a key component of the canonical Wnt signalling pathway that regulates the formation of cardiomyocyte-like cells. We demonstrated that PYGO2 promotes the formation of mesodermal-like cells and their differentiation into cardiomyocytes through the hUC-MSC-dependent canonical Wnt signalling by promoting the early-stage entry of β-catenin into the nucleus. Surprisingly, PYGO2 did not alter the expression of the canonical-Wnt, NOTCH, or BMP signalling pathways during the middle–late stages. In contrast, PI3K-Akt signalling promoted hUC-MSCs formation and their differentiation into cardiomyocyte-like cells. To the best of our knowledge, this is the first study to demonstrate that PYGO2 uses a biphasic mechanism to promote cardiomyocyte formation from hUC-MSCs.

Bisabolane-type sesquiterpenoids with potential anti-inflammatory and anti-HIV activities from the stems and leaves of Morinda citrifolia - Ying-Ying Zhao; Yu-Jie Li; Xiao-Mei Yu; Qin-Ting Su; Li-Wen Wang; Yu-Shu Zhu; Yan-Hui Fu; Guang-Ying Chen; Yan-Ping Liu (Natural Product Research, 2023)

TRIM7 inhibits encephalomyocarditis virus replication by activating interferon-β signaling pathway - Minjing Li; Junfang Yan; Huixin Zhu; Chengyi Guo; Xiaolin Jiang; Yanni Gao; Xing Liu; Ping Jiang; Juan Bai (Veterinary Microbiology, 2023)

The roles of red mud as desulfurization and denitrification in flue gas: A review - Shuai Liu; Zewei Liu; Hengxi Zhu; Zixuan Wang; Junjiang Guo; Xiaoyue Zhang; Hongxin Yu; Xiangdong Yue; Ping Ning; Bin Li (Journal of Environmental Chemical Engineering, 2023)

A transcriptional atlas of the silk gland in Antheraea pernyi revealed by IsoSeq - Jianping Duan; Shanshan Li; Zhengtian Zhang; Lunguang Yao; Xinfeng Yang; Sanyuan Ma; Nini Duan; Jiazhen Wang; Xuwei Zhu; Ping Zhao (Journal of Asia-Pacific Entomology, 2023)

Orientated inhibition of humin formation in efficient production of levulinic acid from cellulose with high substrate loading: Synergistic role of additives - Ping Hu; Yexin Hu; Hui Li; Linzhen Li; Zhidan Xue; Di Wu; Juan Zhao; Changwei Hu; Liangfang Zhu (Carbohydrate Polymers, 2023)

Hippocampus: Molecular, Cellular, and Circuit Features in Anxiety - Hu-Jiang Shi; Shuang Wang; Xin-Ping Wang; Rui-Xin Zhang; Li-Juan Zhu (Neuroscience Bulletin, 2023)

Exogenous Ethylene Promotes the Germination of Cotton Seeds Under Salt Stress - Haipeng Li; Hongchun Sun; Wenchao Ping; Liantao Liu; Yongjiang Zhang; Ke Zhang; Zhiying Bai; Anchang Li; Jijie Zhu; Cundong Li (Journal of Plant Growth Regulation, 2023)

Changes of spring wind erosion based on wind erosion climate factor in the black soil region of Northeast China - Ping Yan; Sheng-tai Ji; Xiu-fen Li; Hai-xia Zhu; Liang-liang Wang; Mo Zhai; Ping Wang; Hui-ying Zhao (Journal of Mountain Science, 2023)

Incidence and Risk Factors for Dysphagia Following Cerebellar Stroke: a Retrospective Cohort Study - Li Huang; Yunlu Wang; Jikang Sun; Lequn Zhu; Jimin Liu; Yuwei Wu; Chunlei Shan; Juntao Yan; Ping Wan (The Cerebellum, 2023)
The cerebellum is known to play a supportive role in swallowing-related functions; however, wide discrepancies about the incidence rate of swallowing disorders following cerebellar strokes exist within the literature. This study aimed to investigate the incidence rate of dysphagia and the factors which may affect the presence of dysphagia and clinical recovery in individuals diagnosed with cerebellar stroke. A retrospective chart audit of 1651 post-stroke patients (1049 males and 602 females) admitted with a cerebellar stroke to a comprehensive tertiary hospital in China was conducted. Data on demographics, medical, along with swallowing function assessment were collected. Differences between dysphagic and non-dysphagic groups were evaluated using t -tests and Pearson’s chi-square test. Univariate logistic regression analysis was performed to establish factors associated with the presence of dysphagia. A total of 11.45% of participants were identified with dysphagia during inpatient admission. Individuals with mixed types of stroke, multiple lesions in the cerebellum, and ages older than 85 years old were more likely to develop dysphagia. Moreover, the prognosis of dysphagia following a cerebellar stroke was associated with lesions in different parts of the cerebellum. The cumulative recovery rates from the best to worse were the right hemisphere group, the cerebellum vermis or peduncle group, and both the hemisphere group and the left hemisphere group, respectively.

Transcatheter closure of perimembranous ventricular septal defect using a novel fully bioabsorbable occluder: multicenter randomized controlled trial - Shouzheng Wang; Zefu Li; Yunbing Wang; Tianli Zhao; Xuming Mo; Taibing Fan; Jianhua Li; Tao You; Rundi Deng; Wenbin Ouyang; Weiwei Wang; Chuangnian Zhang; et al. (Science Bulletin, 2023)

Authentication, chemical profiles analysis, and quality evaluation of corn silk via DNA barcoding and UPLC-LTQ/Orbitrap MS chemical profiling - Ping Li; Ying Huang; Hongyu Zhu; Jiaxin Chen; Guangxi Ren; Dan Jiang; Chunsheng Liu (Food Research International, 2023)

Distribution characteristics and environmental effects of non-methane hydrocarbons in the East China Sea - Wen-Zhu Qiao; Ying-Cui Wu; Ping Wang; Jian Wang; Li-Min Zhou; Si-Tong Li; Hong-Hai Zhang (Continental Shelf Research, 2023)

Intelligent shielding material based on VO2 with tunable near-field and far-field electromagnetic response - Si-Yuan Liao; Xiao-Yun Wang; Hai-Peng Huang; Yu-Ying Shi; Qiao-Feng Wang; You-Gen Hu; Peng-Li Zhu; Rong Sun; Ching-Ping Wong; Yan-Jun Wan (Chemical Engineering Journal, 2023)

Rational design of an in-build quasi-solid-state electrolyte for high-performance lithium-ion batteries with the silicon-based anode - Enyou Zhao; Shiqiang Luo; Anyi Hu; Zhu Liao; Chenxi Huang; Orita Akihiro; Ping Jiang; Li Yang (Chemical Engineering Journal, 2023)

Experimental Study of Similar Simulated Material Proportioning for Small Scale Models - Yongjian Zhu; Peng Li; Ping Wang; Heng Ren; Chengcheng Mei; Mingxing Wei (Geotechnical and Geological Engineering, 2023)

Stochastic multi-criteria decision making framework based on SMAA-VIKOR for reservoir flood control operation - Chengjing Xu; Ping-an Zhong; Feilin Zhu; Lingjie Li; Qingwen Lu; Luhua Yang (Hydrological Sciences Journal, 2023)

Undescribed phloroglucinol derivatives with antiviral activities from Dryopteris atrata (Wall. Ex Kunze) Ching - Ji-hui Zhang; Jin-lin Chen; Wei-bin Xu; Yi-ping Xia; Hao-yue Zhu; Jing-hao Wang; Yao-lan Li; Guo-cai Wang; Yu-bo Zhang; Neng-hua Chen (Phytochemistry, 2023)

Single-cell transcriptomic analysis reveals the developmental trajectory and transcriptional regulatory networks of pigment glands in Gossypium bickii - Yue Sun; Yifei Han; Kuang Sheng; Ping Yang; Yuefen Cao; Huazu Li; Qian-Hao Zhu; Jinhong Chen; Shuijin Zhu; Tianlun Zhao (Molecular Plant, 2023)

Water transport in continental subduction zones: Constraints from eclogite from the Dabie orogen, east-central China - Zhi-Min Wang; Ren-Xu Chen; Yong-Fei Zheng; Shuning Li; Lin Zhu; Bing Gong; Xiang-Ping Zha; Wan-Cai Li (Journal of Asian Earth Sciences, 2023)

Integrative analyses of transcriptome and metabolome reveal comprehensive mechanisms of Epigallocatechin-3-gallate (EGCG) biosynthesis in response to ecological factors in tea plant (Camellia sinensis) - Ping Xiang; Qiufang Zhu; Luhuan zhang; Puzhen Xu; Lijia Liu; Yuanyuan Li; Bosi Cheng; Xingjian Wang; Jianghong Liu; Yutao Shi; Liangyu Wu; Jinke Lin (Food Research International, 2023)

Polycyclic aromatic hydrocarbon exposure burden: Individual and mixture analyses of associations with chronic obstructive pulmonary disease risk - Kun Peng; Zhao Li; Tian-Rui Gao; Jia Lv; Wen-Jing Wang; Ping Zhan; Wen-Cong Yao; Hui Zhao; Hua Wang; De-Xiang Xu; Yichao Huang; Zhu-Xia Tan (Environmental Research, 2023)

In-situ Ni-oxidation-assisted coupling reduction of NiO and CO2 to synthesize core-shell Ni@octahedral carbon with energy storage properties - Ao Yu; Yinan Zhao; Longtao Zhu; Wenhao Yang; Ping Peng; Fang-Fang Li (Chemical Engineering Journal, 2023)

The ability of pre-magnetized zero-valent iron for peroxymonosulfate activation to remove ofloxacin - Yang Wu; Jing-ying Zhu; Jia-wen Bai; Li-feng Lin; Chang-ping Yu (Chemical Engineering Journal, 2023)

Generating waxy rice starch with target type of amylopectin fine structure and gelatinization temperature by waxy gene editing - Yuhao Fu; Yonghuan Hua; Tingting Luo; Chunyan Liu; Baoli Zhang; Xingyu Zhang; Yiping Liu; Zizhong Zhu; Yang Tao; Zhongyan Zhu; Ping Li; Jun Zhu (Carbohydrate Polymers, 2023)

Changes in the Microbiota and their Roles in Patients with Type 2 Diabetes Mellitus - Qiao-ling He; Hui-chao Wang; Yu-ke Ma; Rui-lin Yang; Zhi-feng Dai; Jing-nan Yang; Yao Xu; Dan-dan Wei; Li-ping Zhu; Xu-hong Lin (Current Microbiology, 2023)

Single-cell HER2 quantification via instant signal amplification in microdroplets - Xiaoxian Liu; Yifan Zhu; Caoxin Li; Yanyun Fang; Jinna Chen; Fei Xu; Yanqing Lu; Perry Ping Shum; Ying Liu; Guanghui Wang (Analytica Chimica Acta, 2023)

Interactions between Cr(VI) and the hydrochar: The electron transfer routes, adsorption mechanisms, and the accelerating effects of wood vinegar - Zirui Wang; Nan Lu; Xu Cao; Qingzi Li; Shangyu Gong; Ping Lu; Ke Zhu; Jiunian Guan; Til Feike (Science of The Total Environment, 2023)

Cascading effects of Pb on the environmental and symbiotic microbiota and tadpoles' physiology based on field data and laboratory validation - Wei Zhu; Yan Lv; Qun-De Zhang; Li-Ming Chang; Qi-Heng Chen; Bin Wang; Jian-Ping Jiang (Science of The Total Environment, 2023)

Multi-condition optimisation design of a hydrofoil based on deep belief network - Guojun Zhu; Jianjun Feng; Ping Li; Zhaoning Wang; Guangkuan Wu; Xingqi Luo (Ocean Engineering, 2023)

Accelerated Fe(III)/Fe(II) cycle for rapid elimination of Rhodamine B by a novel Mo2C co-catalytic Fe2+/H2O2 system - Hao Cheng; Xinyan Li; Chao Huang; Jian Zhu; Ping Wang; Heng Cao; Chongling Feng; Dingxun Ling; Hao Liu; Min Cheng (Journal of Cleaner Production, 2023)

Tracking and dating incipient melting of a new grouplet of primitive achondrites - Yun Jiang; Ye Li; Jia Liu; Qing Wang; Li-Ping Qin; Ke Zhu; Shiyong Liao; Zongjun Yin; Yongbo Peng; Piers Koefoed; Weibiao Hsu (Geochimica et Cosmochimica Acta, 2023)

Internal erosion of debris-flow deposits triggered by seepage - Xiangang Jiang; Anders Wörman; Xiaoqing Chen; Zhanyuan Zhu; Zuyin Zou; Weimin Xiao; Ping Li; Guojun Liu; Diyin Kang (Engineering Geology, 2023)

Correction to: Protective Effects of Chinese Herbal Medicine Rhizoma drynariae in Rats After Traumatic Brain Injury and Identification of Active Compound - Wenzhu Wang; Haigang Li; Jintao Yu; Michael Hong; Jing Zhou; Lin Zhu; Yang Wang; Min Luo; Zian Xia; Zeng-Jin Yang; Tao Tang; Ping Ren; et al. (Molecular Neurobiology, 2023)

Aerobic glycolysis in colon cancer is repressed by naringin via the HIF1A pathway - Guangtao Pan; Ping Zhang; Aiying Chen; Yu Deng; Zhen Zhang; Han Lu; Aoxun Zhu; Cong Zhou; Yanran Wu; Sen Li (Journal of Zhejiang University-SCIENCE B, 2023)

Transcriptomic analysis provides new insights into the secondary follicle growth in spotted scat (Scatophagus argus) - Mou-Yan Jiang; Yi-Fan Zhou; Hao Liu; You-Xing Peng; Yuan-Qing Huang; Si-Ping Deng; Yang Huang; Gang Shi; Chun-Hua Zhu; Guang-Li Li; Dong-Neng Jiang (Frontiers in Marine Science, 2023)
Spotted scat ( Scatophagus argus ) is an important mariculture fish that is of great economic significance in East and Southeast Asia. To date, there are no studies on ovary development and regulation in S. argus . Herein, the ovary transcriptome profiles of S. argus at different stages were constructed, and the genes and pathways potentially involved in secondary follicle growth were identified. A total of 25,426 genes were detected by sequencing the mRNAs from the ovary libraries at stage III (n=3) and IV (n=3). Notably, 2950 and 716 genes were up-regulated and down-regulated in the stage IV ovary, respectively, compared to the stage III ovary. The differentially expressed genes (DEGs) were found to be mostly involved in regulating steroidogenesis, vitellogenesis, lipid metabolism, and meiosis. Up-regulation of steroid hormone synthesis pathway genes ( fshr , cyp17a1 , and foxl2 ) and insulin-like growth factor pathway genes ( igf1r , ifg2r , igfbp1 , igfbp3 , and igfbp7 ) in the ovary at stage IV was possibly the reason for the increased serum estrogen. Moreover, ppara , ppard , fabp3 , and lpl were up-regulated in the stage IV ovary and were potentially involved in the lipid droplet formation in the oocyte. Many DEGs were involved in the cellular cycle, meiosis, and cAMP or cGMP synthesis and hydrolysis, indicating that meiosis was restarted at stage IV ovary. In addition, numerous TGF-beta signal pathway genes were up-regulated in the stage IV ovary. This ovary transcript dataset forms a baseline for investigating functional genes associated with oogenesis in S. argus .

Recovery iron from cyanide tailings by anaerobic roasting-persulfate leaching: effect of roasting temperature - Ping Dong; Yonghui Song; Lei Wu; Jin Bao; Ning Yin; Rongyan Zhu; Yifan Li (Environmental Science and Pollution Research, 2023)

Impacts of PFOAC8, GenXC6, and their mixtures on zebrafish developmental toxicity and gene expression provide insight about tumor-related disease - Huinian Liu; Yu Chen; Wenli Hu; Yuan Luo; Ping Zhu; Shiqi You; Yunxuan Li; Zhaobiao Jiang; Xiushan Wu; Xin Li (Science of The Total Environment, 2023)

Two new tetrahydroisoquinoline alkaloids from Portulaca oleracea - Kai-Jun Tang; Yu Chen; Jing Li; Xu Tao; Lu-Ping Yang; Tian-Yun Jin; Jia-Shun Zhu; Yu Zhao; Tao Shen; Xiao-Ning Wang; Dong-Mei Ren; Lan Xiang (Phytochemistry Letters, 2023)

Effects and molecular mechanism of flagellar gene flgK on the motility, adhesion/invasion, and desiccation resistance of Cronobacter sakazakii - Ping Li; Wenyue Zong; Zhengyang Zhang; Wen Lv; Xuemeng Ji; Dongdong Zhu; Xinjun Du; Shuo Wang (Food Research International, 2023)

Different sulfide to arsenic ratios driving arsenic speciation and microbial community interactions in two alkaline hot springs - Chun Qing; Alan Nicol; Ping Li; Britta Planer-Friedrich; Changguo Yuan; Zhu Kou (Environmental Research, 2023)

Cobalt single atom anchored on N-doped carbon nanoboxes as typical single-atom catalysts (SACs) for boosting the overall water splitting - Tong Li; Siyuan Ren; Cheng Zhang; Lingxia Qiao; Jiang Wu; Ping He; Jia Lin; Yongsheng Liu; Zaiguo Fu; Qunzhi Zhu; Weiguo Pan; Baofeng Wang; et al. (Chemical Engineering Journal, 2023)

Smog chamber study of secondary organic aerosol formation from gas- and particle-phase naphthalene ozonolysis - Jixing Liu; Shuping Zhu; Teng Guo; Bin Jia; Li Xu; Jun Chen; Ping Cheng (Atmospheric Environment, 2023)

Reduction of gross N Transformations to Moisture Changes in a Wetland Ecosystem: The Case of Marshland Conversion to Cropland - Ping Li; Man Lang; Wei Wei; Sixi Zhu (Wetlands, 2023)

Bi/Te control on gold mineralizing processes in the North China Craton: Insights from the Wulong gold deposit - Haoxuan Feng; Ping Shen; Rixiang Zhu; Andrew G. Tomkins; Joël Brugger; Ge Ma; Changhao Li; Yang Wu (Mineralium Deposita, 2023)

Chinese consensus guidelines for therapeutic drug monitoring of polymyxin B, endorsed by the Infection and Chemotherapy Committee of the Shanghai Medical Association and the Therapeutic Drug Monitoring Committee of the Chinese Pharmacological Society - Xiaofen Liu; Chenrong Huang; Phillip J. Bergen; Jian Li; Jingjing Zhang; Yijian Chen; Yongchuan Chen; Beining Guo; Fupin Hu; Jinfang Hu; Linlin Hu; Xin Li; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

Effects of bepridil on early cardiac development of zebrafish - Ya-Lan Wei; Yu-Qing Lei; Zhou-Jie Ye; Xu-Dong Zhuang; Li-Ping Zhu; Xin-Rui Wang; Hua Cao (Cell and Tissue Research, 2023)

Pyrrolizidine-producing weeds in tea gardens as an indicator of alkaloids in tea - Weiting Jiao; Luyao Wang; Lei Zhu; Tingting Shen; Taozhong Shi; Ping Zhang; Chen Wang; Hongping Chen; Xiangwei Wu; Tianyuan Yang; Qing X. Li; Rimao Hua (Food Additives & Contaminants Part B-Surveillance, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Climate-driven sapwood-specific hydraulic conductivity and the Huber value but not leaf-specific hydraulic conductivity on a global scale - Li-Wei Zhu; Ping Zhao (Science of The Total Environment, 2023)

Biomineralization and AHLs-guided quorum sensing enhanced phosphorus recovery in the alternating aerobic/anaerobic biofilm system under metal ion stress - Hao Zhang; Shuang-Shuang Zhang; Wei Zhang; Liang Zhu; Yi-Ping Li; Yang Pan (Journal of Environmental Management, 2023)

Confined Fe single atomic sites on (100) plane of anatase TiO2 nanofibers boost white LED driven Fenton-like norfloxacin degradation - Zhilin Ji; Rongsheng Cai; Wanneng Ye; Ping Lu; Chung-Li Dong; Yu-Cheng Huang; Xilin She; Denys S. Butenko; Yiming Liu; Yukun Zhu; Dongjiang Yang (Journal of Cleaner Production, 2023)

Enhanced stability and combustion performance of AlH3 in combination with commonly used oxidizers - Ming-Hui Yu; Su-Lan Yang; Wu-Xi Xie; Zhao-Yang Zhu; He-Ping Li; Qi-Long Yan (Fuel, 2023)

3-MCPD exposure enhances ovarian fibrosis and reduces oocyte quality in mice - Quan-Kuo He; Yan-Ping Li; Zhi-Ran Xu; Wen-Bo Wei; Feng-Xin Qiao; Ming-Xin Sun; Yue-Cen Liu; Yan-Zhu Chen; Hai-Long Wang; Zhong-Quan Qi; Yu Liu (Environmental Pollution, 2023)

Regulating electronic structure by Mn doping for nickel cobalt hydroxide nanosheets/carbon nanotube to promote oxygen evolution reaction and oxidation of urea and hydrazine - Kaili Wu; Chenyang Cao; Keren Li; Chaojie Lyu; Jiarun Cheng; Hongyu Li; Pengfei Hu; Jiwen Wu; Woon-Ming Lau; Xixi Zhu; Ping Qian; Jinlong Zheng (Chemical Engineering Journal, 2023)

Rational construction and understanding the effect of metal cation substitution of three novel ternary Zn-Co–Ni-LDHs from 2D to 3D and its enhanced adsorption properties for MO - Zhu Jie; Jiang Yichen; Li Ping; Li Yang; Tian Huiyuan; Du Xiuhong; Wang Zehua; Duan Xianying; Li Chunguang; Cui Jiehu (Environmental Science and Pollution Research, 2023)

Correction to: Gpx4, Selenov, and Txnrd3 Are Three Most Testis-Abundant Selenogenes Resistant to Dietary Selenium Concentrations and Actively Expressed During Reproductive Ages in Rats - Aiping Liu; Fengna Li; Ping Xu; Yanmei Chen; Xiongshun Liang; Shijie Zheng; Huicui Meng; Yumei Zhu; Junluan Mo; Chunmei Gong; Ji-Chang Zhou (Biological Trace Element Research, 2023)

Gpx4, Selenov, and Txnrd3 Are Three Most Testis-Abundant Selenogenes Resistant to Dietary Selenium Concentrations and Actively Expressed During Reproductive Ages in Rats - Aiping Liu; Fengna Li; Ping Xu; Yanmei Chen; Xiongshun Liang; Shijie Zheng; Huicui Meng; Yumei Zhu; Junluan Mo; Chunmei Gong; Ji-Chang Zhou (Biological Trace Element Research, 2023)

Identification and expression profiling of receptor‐interacting serine/threonine‐protein kinase 2 in Siberian sturgeon ( Acipenser baerii ) - Lu Lu; Shaotong Dai; Hao Zhu; Xin Zhang; Zhiqiong Li; Xiaoli Huang; Ping Ouyang; Yi Geng; Defang Chen (Journal of Fish Biology, 2023)
Receptor‐interacting serine/threonine‐protein kinase 2 (RIPK2) is an adaptor protein of the pattern recognition receptors NOD1 and NOD2 involved in regulating inflammatory response and resisting pathogenic microbial infection. In this study, Acipenser baerii RIPK2 ( AbRIPK2 ) was identified. The open reading frame of AbRIPK2 was 1815 bp encoding 604 amino acids. AbRIPK2 possessed the typical N‐terminal kinase domain (KD) and C‐terminal caspase recruitment domain (CARD). The phylogenetic tree analysis revealed that AbRIPK2 shared a relatively high identity with bony fish. Real‐time fluorescence quantitative PCR (qRT‐PCR) results indicated that AbRIPK2 was highly expressed in the gill, followed by muscle, liver and heart. AbRIPK2 was significantly induced in the spleen and valvular intestine after Streptococcus iniae and Aeromonas hydrophila infection. AbRIPK2 was significantly upregulated after peptidoglycan (PGN) treatment in the splenic leukocytes. This study indicated that AbRIPK2 played a potential role in resisting the pathogenic infection of Siberian sturgeon by responding to bacteria.

Cryo-EM structures reveal the dynamic transformation of human alpha-2-macroglobulin working as a protease inhibitor - Xiaoxing Huang; Youwang Wang; Cong Yu; Hui Zhang; Qiang Ru; Xinxin Li; Kai Song; Min Zhou; Ping Zhu (Science China Life Sciences, 2022)

Inhibition of Microglial NLRP3 with MCC950 Attenuates Microglial Morphology and NLRP3/Caspase-1/IL-1β Signaling In Stress-induced Mice - Qing Liu; Man-Man Zhang; Min-Xia Guo; Qiu-Ping Zhang; Na-Zhi Li; Jie Cheng; Shi-Le Wang; Guang-Hui Xu; Cheng-Fu Li; Ji-Xiao Zhu; Li-Tao Yi (Journal of Neuroimmune Pharmacology, 2022)

Application of regional citrate anticoagulation in patients at high risk of bleeding during intermittent hemodialysis: a prospective multicenter randomized controlled trial - Xiaoyan Tang; Dezheng Chen; Ling Zhang; Ping Fu; Yanxia Chen; Zhou Xiao; Xiangcheng Xiao; Weisheng Peng; Li Cheng; Yanmin Zhang; Hongbo Li; Kehui Li; et al. (Journal of Zhejiang University-SCIENCE B, 2022)

Flocculation of Chlorella vulgaris–induced algal blooms: critical conditions and mechanisms - Ping Zhang; Sihan Zhu; Chao Xiong; Bin Yan; Zhikang Wang; Kai Li; Irumva Olivier; Han Wang (Environmental Science and Pollution Research, 2022)

Study on the Effectiveness and Mechanism of Mercapto-Modified Attapulgite for Remediation of Cadmium-Contaminated Paddy Soil - Guangxi He; Xiaping Zhu; Yan An; Yuying Chen; Cheng Fu; Ningfei Lei; Ying Zeng; Junya Li; Zepeng Wang; Ping Zhao (Water, Air, & Soil Pollution, 2022)

Stem Cell-Derived Exosomes: A New Method for Reversing Skin Aging - Jin-Yan Wu; Sai-Nan Wu; Li-Ping Zhang; Xian-Sheng Zhao; Yue Li; Qu-Yang Yang; Ruo-Yue Yuan; Jian-Lan Liu; Hong-Ju Mao; Ning-Wen Zhu (Tissue Engineering and Regenerative Medicine, 2022)

Effect of posaconazole on the concentration of intravenous and oral cyclosporine in patients undergoing hematopoietic stem cell transplantation - Li-E Zhu; Hui-Ping Huang; Yi-Peng Cai; Yan Wang; Bao-Hua Xu; Mao-Bai Liu; Xue-Mei Wu (European Journal of Clinical Pharmacology, 2022)

Method for reconstructing seismic data using a projection onto a convex set and a complicated curvelet transform - Jie Zhu; Ping Li; Jucipar Zeather (Arabian Journal of Geosciences, 2022)

Overexpression of PYGO1 promotes early cardiac lineage development in human umbilical cord mesenchymal stromal/stem cells by activating the Wnt/β-catenin pathway - Jie Shen; Xiushan Wu; Ping Zhu; Jian Zhuang; Bin Qin; Fang Sun; Wuzhou Yuan; Xiongwei Fan; Zhigang Jiang; Fang Li; Yongqing Li; Yuequn Wang; et al. (Human Cell, 2022)

Oxytocin Receptor in Cerebellar Purkinje Cells Does Not Engage in Autism-Related Behaviors - Li-Ping Shen; Wei Li; Ling-Zhu Pei; Jun Yin; Shu-Tao Xie; Hong-Zhao Li; Chao Yan; Jian-Jun Wang; Qipeng Zhang; Xiao-Yang Zhang; Jing-Ning Zhu (The Cerebellum, 2022)

Long-term changes in zooplankton in the Changjiang estuary from the 1960s to 2020 - Ping Du; Wen-Jian Ye; Bang-Ping Deng; Ming Mao; Yuan-Li Zhu; Fang-Ping Cheng; Zhi-Bing Jiang; Lu Shou; Quan-Zhen Chen (Frontiers in Marine Science, 2022)
The Changjiang estuary (CJE) is a large estuary that is affected by multiple anthropogenic stressors and climate change. The long-term trend of zooplankton in the CJE is an important indicator of the ecological response to stressors. We applied the Mann–Kendall trend analysis and Pettitt test to detect the trend and breakpoints of the biomass of the large mesozooplankton (LMZ; 505–20 000 μm) in four seasons, abundance of main LMZ taxa in summer from the 1960s to 2020, and abundance of dominant species in summer from 2000 to 2020 in the CJE. Results showed that LMZ biomass increased significantly during spring and summer, and the breakpoints both occurred in the 1980s. After the breakpoint, the mean biomass increased from 142.88 to 429.42 mg/m 3 in spring and from 296.28 to 723.92 mg/m 3 in summer. After 2000, the abundance of Copepoda in summer increased by more than 10 times compared to the 1960s. Under the conditions of warming and increased dinoflagellate abundance in the CJE, the abundance of the warm-water and omnivorous small calanoid copepod Paracalanus aculeatus increased significantly. Meanwhile, the significant decrease in the abundance of the temperate brackish species Labidocera euchaeta was probably mainly related to warming. The rapid changes in LMZ biomass during the late 1980s and mid-1990s is probably the result of a combination of enhanced bottom–up support, reduced top–down pressure, and promotion of temperature. This study provides scientific evidence and insights into the adaptive management of the Changjiang Basin.

Administration of mesenchymal stem cells in diabetic kidney disease: mechanisms, signaling pathways, and preclinical evidence - Yuexin Zhu; Manyu Luo; Xue Bai; Yan Lou; Ping Nie; Shan Jiang; Jicui Li; Bing Li; Ping Luo (Molecular and Cellular Biochemistry, 2022)

Precise ages of gold mineralization and pre-gold hydrothermal activity in the Baiyun gold deposit, northeastern China: in situ U–Pb dating of hydrothermal xenotime and rutile - Haoxuan Feng; Ping Shen; Rixiang Zhu; Jian-Wei Zi; David I. Groves; Changhao Li; Yang Wu; Ge Ma; Taiyang Li (Mineralium Deposita, 2022)

Recombinant jurkat cells (HMGN2-T cells) secrete cytokines and inhibit the growth of tumor cells - Huanhuan Li; Xueqiang Wu; Dingfang Bu; Lihua Wang; Xueju Xu; Yingchao Wang; Yufeng Liu; Ping Zhu (Journal of Molecular Histology, 2022)

The α5-nAChR/PD-L1 axis facilitates lung adenocarcinoma cell migration and invasion - Ping Zhu; Guiyu Kang; Yang Jiao; Chengzhi Gui; Huiping Fan; Xiangying Li; Yanfei Jia; Lulu Zhang; Xiaoli Ma (Human Cell, 2022)

Rhodoflexus caldus gen. nov., sp. nov., a new member of the phylum Bacteroidota isolated from a hot spring sediment - Ze-Tao Liu; Lan Liu; Wen-Dong Xian; Zheng-Han Lian; Jun-Yi Dai; Bao-Zhu Fang; Meng-Meng Li; Ai-Ping Lv; Zhen-Hao Luo; Jian-Yu Jiao; Wen-Jun Li (Antonie van Leeuwenhoek, 2022)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Mycorrhizal fungi alleviate acidification‐induced phosphorus limitation: Evidence from a decade‐long field experiment of simulated acid deposition in a tropical forest in south China - Yuanliu Hu; Ji Chen; Dafeng Hui; Ying‐Ping Wang; Jianling Li; Jingwen Chen; Guoyin Chen; Yiren Zhu; Leiyi Zhang; Deqiang Zhang; Qi Deng (Global Change Biology, 2022)
South China has been experiencing very high rate of acid deposition and severe soil acidification in recent decades, which has been proposed to exacerbate the regional ecosystem phosphorus (P) limitation. We conducted a 10‐year field experiment of simulated acid deposition to examine how acidification impacts seasonal changes of different soil P fractions in a tropical forest with highly acidic soils in south China. As expected, acid addition significantly increased occluded P pool but reduced the other more labile P pools in the dry season. In the wet season, however, acid addition did not change microbial P, soluble P and labile organic P pools. Acid addition significantly increased exchangeable Al 3+ and Fe 3+ and the activation of Fe oxides in both seasons. Different from the decline of microbial abundance in the dry season, acid addition increased ectomycorrhizal fungi and its ratio to arbuscular mycorrhiza fungi in the wet season, which significantly stimulated phosphomonoesterase activities and likely promoted the dissolution of occluded P. Our results suggest that, even in already highly acidic soils, the acidification‐induced P limitation could be alleviated by stimulating ectomycorrhizal fungi and phosphomonoesterase activities. The differential responses and microbial controls of seasonal soil P transformation revealed here should be implemented into ecosystem biogeochemical model for predicting plant productivity under future acid deposition scenarios.

Community Structure of Benthic Macrofauna and the Ecological Quality of Mangrove Wetlands in Hainan, China - Ping Li; Jingli Liu; Jiankun Bai; Yifan Tong; Yuchen Meng; Xiaoping Diao; Ke Pan; Xiaoshan Zhu; Guanghui Lin (Frontiers in Marine Science, 2022)
Few studies have systematically assessed the ecological status of mangrove wetlands following the stress of anthropogenic activities in China. This study investigated the spatial and seasonal distribution of benthic macroinvertebrate communities and assessed the ecological quality of mangrove habitats on an island scale in Hainan, China (containing the third largest mangrove area of China and the highest mangrove species richness). For the benthic macrofauna community structure, a total of 102 macrobenthic taxa belonging to 50 families were identified, with Crustaceans, Molluscs, Polychaetes, and Oligochaeta having relative abundances of 52.3%, 36.1%, 10.8%, and 0.8%, respectively. Decapoda and Gastropoda dominated the benthic community abundance. Non-metric multidimensional scaling and an analysis of similarities revealed significantly different macroinvertebrate assemblages among the regions during the two seasons. The South mangroves had the lowest macrofauna species numbers, biodiversity, richness, and abundance. The macrofaunal species richness, Shannon index, Margalef index, abundance, and biomass markedly affected by region and season. As indicated by the biotic indices AMBI (AZTI’s Marine Biotic Index) and M-AMBI, more than half of the mangrove habitats on Hainan Island were slightly to heavily disturbed and had poor to moderate ecological quality. Our results recommend long-term monitoring for evaluating the quality status of mangrove wetlands and avoiding extensive land-use conversion of mangroves. Holistic approaches considering ecological characteristics and combining information on both floral and faunal functionality would contribute to the effective management and conservation of mangroves in disturbed areas.

Monascuslactams A–D, cytotoxic γ-lactams from marine fungus Monascus albidus BB3 - Qi Guo; Xiao-Ming Dai; Wen-Jian Lan; Liu-Ping Chen; Chi-Keung Lam; Gong-Kan Feng; Rong Deng; Xiao-Feng Zhu; Hou-Jin Li (Natural Product Research, 2022)

The study of schizogenous formation of secretory ducts in Ferula ferulaeoides (Steud.) Korov. - Meng-meng Liu; Yuan-yuan Zhao; Ying Ma; Shuang-shuang Liu; Jia-qi Yao; Ya-ping Chi; Hui-fang Li; Kai Liao; Yun Zhu (Protoplasma, 2022)

Mutation of Beclin1 acetylation site at K414 alleviates high glucose-induced podocyte impairment in the early stage of diabetic nephropathy by inhibiting hyperactivated autophagy - Jun Xu; Yujie Deng; Yingying Ke; Yunxia Zhu; Ping Wang; Qing Yu; Chengqian Li; Bimin Shi (Molecular Biology Reports, 2022)

The Effects of Ground and Treadmill Running on Energy Metabolism and Muscle Contractile Properties: A Randomized Cross-Over Study - Yuan Zhou; Jian-gang Chen; Xiao-long Li; Xin-liang Pan; Yi-zheng Zhou; Zheng-ao Li; Zhi-cheng Liang; Jia-min Long; Ming-ze Qin; Jing Zhang; Bing Shi; Bing-jun Wan; et al. (Journal of Science in Sport and Exercise, 2022)
Purpose This study aimed to compare the effects of ground and treadmill running on energy metabolism and muscle contractile properties, providing a basis for the general public to choose running venues. Methods Ten male college students (age, 20.10 ± 1.53 years; height, 176.20 ± 5.49 cm; weight, 72.14 ± 8.25 kg; body fat percent, 12.41% ± 4.65%) were recruited in this study. Energy expenditure (EE) was measured using the accelerometer (GT9X) combined with specific estimation equations. Average heart rate (HR) was measured using a heart rate band (Polar). Muscle contractile properties were assessed by measuring muscle displacement (Dm) and contraction velocity (Vc) using tensiomyography (TMG-S1). Blood glucose (Glu) and lactate (Lac) were measured by portable devices (eB-G and Lactate Scout). The running speed was 9 km/h and the duration was 25 min. Two-way ANOVA (protocol × time) was used to analyze the effect of running protocols on energy metabolism and muscle contractile properties. Results EE of treadmill running was significantly higher than EE of ground running (protocol main effect, P < 0.001), and HR of treadmill running was significantly higher than that of ground running in the first testing time (protocol simple effect, P = 0.026; protocol × time interaction P = 0.043). The decrease in Dm of the rectus femoris after treadmill running was significantly higher than that of ground running (protocol main effect, P = 0.009). The interaction of different running protocols and testing times on Lac was significant ( P = 0.025), but all results of the simple effects analysis were not statistically significant ( P > 0.05). Conclusion Our study found a difference in energy expenditure between treadmill and ground running at 9 km/h with duration of 25 min. In addition, treadmills are more likely to cause a decrease in muscle displacement distance of the rectus femoris measured after exercise than ground running. Future studies are needed to further investigate whether the differences are induced by internal metabolism or the environmental conditions of running.

Chemical constituents of Viscum coloratum (Kom.) Nakai and their cytotoxic activities - Ying-Ying Chen; Jiang-Ping Hou; Ling Huang; Afsar Khan; Fei-Fei Xing; Xiao-Han Zhang; De-Feng Han; Shi-Li Yan; Gui-Dong Cao; Qi-Yang Jiao; Dejie Liu; Xuwei Zhu; et al. (Natural Product Research, 2022)

The study on dynamic shear modulus and damping ratio of marine soils based on dynamic triaxial test - Yuying Li; Ping Li; Sheng Zhu (Marine Georesources & Geotechnology, 2022)

Fine mapping of powdery mildew resistance gene MlWE74 derived from wild emmer wheat (Triticum turgidum ssp. dicoccoides) in an NBS-LRR gene cluster - Keyu Zhu; Miaomiao Li; Haibin Wu; Deyun Zhang; Lingli Dong; Qiuhong Wu; Yongxing Chen; Jingzhong Xie; Ping Lu; Guanghao Guo; Huaizhi Zhang; Panpan Zhang; et al. (Theoretical and Applied Genetics, 2022)

Dynamics of nitrogen and phosphorus profile and its driving forces in a subtropical deep reservoir - Cunli Li; Ping Zhang; Guangwei Zhu; Chao Chen; Yucheng Wang; Mengyuan Zhu; Hai Xu; Cuiling Jiang; Wei Zou; Pengcheng Shi; Qing Zheng (Environmental Science and Pollution Research, 2022)

The impact of environmental regulations on export trade at provincial level in China: evidence from panel quantile regression - Ouyang Qiang; Wang Tian-tian; Deng Ying; Li Zhu-ping; Atif Jahanger (Environmental Science and Pollution Research, 2022)

The Predictability of Ocean Environments that Contributed to the 2020/21 Extreme Cold Events in China: 2020/21 La Niña and 2020 Arctic Sea Ice Loss - Fei Zheng; Ji-Ping Liu; Xiang-Hui Fang; Mi-Rong Song; Chao-Yuan Yang; Yuan Yuan; Ke-Xin Li; Ji Wang; Jiang Zhu (Advances in Atmospheric Sciences, 2022)
Several consecutive extreme cold events impacted China during the first half of winter 2020/21, breaking the low-temperature records in many cities. How to make accurate climate predictions of extreme cold events is still an urgent issue. The synergistic effect of the warm Arctic and cold tropical Pacific has been demonstrated to intensify the intrusions of cold air from polar regions into middle-high latitudes, further influencing the cold conditions in China. However, climate models failed to predict these two ocean environments at expected lead times. Most seasonal climate forecasts only predicted the 2020/21 La Niña after the signal had already become apparent and significantly underestimated the observed Arctic sea ice loss in autumn 2020 with a 1–2 month advancement. In this work, the corresponding physical factors that may help improve the accuracy of seasonal climate predictions are further explored. For the 2020/21 La Niña prediction, through sensitivity experiments involving different atmospheric–oceanic initial conditions, the predominant southeasterly wind anomalies over the equatorial Pacific in spring of 2020 are diagnosed to play an irreplaceable role in triggering this cold event. A reasonable inclusion of atmospheric surface winds into the initialization will help the model predict La Niña development from the early spring of 2020. For predicting the Arctic sea ice loss in autumn 2020, an anomalously cyclonic circulation from the central Arctic Ocean predicted by the model, which swept abnormally hot air over Siberia into the Arctic Ocean, is recognized as an important contributor to successfully predicting the minimum Arctic sea ice extent.

Antifungal sesquiterpenes with post-harvest anthracnose control effect on bananas from the fungus Fusarium lateritium - Junjie Zhu; Ping Xiong; Ziyang Li; Jiazhong Li; Longsheng Lin; Xing Fu; Yuxuan Huang; Yahong Xiong; Chunyuan Li (Natural Product Research, 2022)

Experiment on the energy damage development process of water-saturated limestone under varied loading rates - Peng Li; Yongjian Zhu; Ping Wang; Heng Ren; Mingxing Wei; Xizhi Wang (Arabian Journal of Geosciences, 2022)

MoOpy2 is essential for fungal development, pathogenicity, and autophagy in Magnaporthe oryzae - Ying‐Ying Cai; Jing‐Yi Wang; Xi‐Yu Wu; Shuang Liang; Xue‐Ming Zhu; Lin Li; Jian‐Ping Lu; Xiao‐Hong Liu; Fu‐Cheng Lin (Environmental Microbiology, 2022)
Summary The development and pathogenicity of the fungus Magnaporthe oryzae , the causal agent of destructive rice blast disease, require it to perceive external environmental signals. Opy2, an overproduction‐induced pheromone‐resistant protein 2, is a crucial protein for sensing external signals in Saccharomyces cerevisiae . However, the biological functions of the homologue of Opy2 in M. oryzae are unclear. In this study, we identified that MoOPY2 is involved in fungal development, pathogenicity, and autophagy in M. oryzae . Deletion of MoOPY2 resulted in pleiotropic defects in hyphal growth, conidiation, germ tube extension, appressorium formation, appressorium turgor generation, and invasive growth, therefore leading to attenuated pathogenicity. Furthermore, MoOpy2 participates in the Osm1 MAPK pathway and the Mps1 MAPK pathway by interacting with the adaptor protein Mst50. The interaction sites of Mst50 and MoOpy2 colocalized with the autophagic marker protein MoAtg8 in the preautophagosomal structure sites (PAS). Notably, the Δ Moopy2 mutant caused cumulative MoAtg8 lipidation and rapid GFP‐MoAtg8 degradation in response to nitrogen starvation, showing that MoOpy2 is involved in the negative regulation of autophagy activity. Taken together, our study revealed that MoOpy2 of M. oryzae plays an essential role in the orchestration of fungal development, appressorium penetration, autophagy and pathogenesis.

Endosomal sorting complexes required for transport‐0 ( ESCRT ‐0) are essential for fungal development, pathogenicity, autophagy and ER ‐phagy in Magnaporthe oryzae - Li‐Xiao Sun; Hui Qian; Meng‐Yu Liu; Ming‐Hua Wu; Yun‐Yun Wei; Xue‐Ming Zhu; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2022)
Summary Magnaporthe oryzae is an important plant pathogen that causes rice blast. Hse1 and Vps27 are components of ESCRT‐0 involved in the multivesicular body (MVB) sorting pathway and biogenesis. To date, the biological functions of ESCRT‐0 in M. oryzae have not been determined. In this study, we identified and characterized Hse1 and Vps27 in M. oryzae . Disruption of MoHse1 and MoVps27 caused pleiotropic defects in growth, conidiation, sexual development and pathogenicity, thereby resulting in loss of virulence in rice and barley leaves. Disruption of MoHse1 and MoVps27 triggered increased lipidation of MoAtg8 and degradation of GFP‐MoAtg8, indicating that ESCRT‐0 is involved in the regulation of autophagy. ESCRT‐0 was determined to interact with coat protein complex II (COPII), a regulator functioning in homeostasis of the endoplasmic reticulum (ER homeostasis), and disruption of MoHse1 and MoVps27 also blocked activation of the unfolded protein response (UPR) and autophagy of the endoplasmic reticulum (ER‐phagy). Overall, our results indicate that ESCRT‐0 plays critical roles in regulating fungal development, virulence, autophagy and ER‐phagy in M. oryzae .

Four new prenylflavonol glycosides from the leaves of Cyclocarya paliurus - Zi-Jun Ye; Hui-Hui Sun; Zu-Hui Chen; Jian-Ping Wu; Jing Li; Hui Zhu; Lu-Lu Huang; Xi-Wen Chang; Sai-Yu Ou; Wen-Xuan Wang; Xiao-Ai He; Gang-Zhi Zhu; et al. (Natural Product Research, 2022)

A comparison of the reproducibility of regional precipitation properties simulated respectively by weather generators and stochastic simulation methods - Luhua Yang; Ping-an Zhong; Feilin Zhu; Yufei Ma; Han Wang; Jieyu Li; Chengjing Xu (Stochastic Environmental Research and Risk Assessment, 2022)

Oxidative degradation/mineralization of dimethyl phthalate (DMP) from plastic industrial wastewater using ferrate(VI)/TiO2 under ultraviolet irradiation - Ping Wang; Yi Ding; Liting Zhu; Yunhao Zhang; Sijie Zhou; Linbei Xie; Ao Li (Environmental Science and Pollution Research, 2022)

Implication of exogenous abscisic acid (ABA) application on phytoremediation: plants grown in co-contaminated soil - Lang Cheng; Lei Pu; Ai Li; Xiaping Zhu; Ping Zhao; Xiangning Xu; Ningfei Lei; Jinsong Chen (Environmental Science and Pollution Research, 2022)

C-dot doping for enhanced catalytic performance of TiO2/5A for toluene degradation in non-thermal plasma-catalyst system - Jixing Liu; Yanyan Ji; Shuping Zhu; Teng Guo; Li Xu; Junguo Dong; Ping Cheng (Environmental Science and Pollution Research, 2022)

Identification of New Transcription Factors that Can Promote Pluripotent Reprogramming - Ping Huang; Jieying Zhu; Yu Liu; Guihuan Liu; Ran Zhang; Dongwei Li; Duanqing Pei; Ping Zhu (Stem Cell Reviews and Reports, 2021)
Background Four transcription factors, Oct4, Sox2, Klf4, and c-Myc (the Yamanka factors), can reprogram somatic cells to induced pluripotent stem cells (iPSCs). Many studies have provided a number of alternative combinations to the non-Yamanaka factors. However, it is clear that many additional transcription factors that can generate iPSCs remain to be discovered. Methods The chromatin accessibility and transcriptional level of human embryonic stem cells and human urine cells were compared by Assay for Transposase-Accessible Chromatin with high-throughput sequencing (ATAC-seq) and RNA sequencing (RNA-seq) to identify potential reprogramming factors. Selected transcription factors were employed to reprogram urine cells, and the reprogramming efficiency was measured. Urine-derived iPSCs were detected for pluripotency by Immunofluorescence, quantitative polymerase chain reaction, RNA sequencing and teratoma formation test. Finally, we assessed the differentiation potential of the new iPSCs to cardiomyocytes in vitro. Results ATAC-seq and RNA-seq datasets predicted TEAD2, TEAD4 and ZIC3 as potential factors involved in urine cell reprogramming. Transfection of TEAD2, TEAD4 and ZIC3 (in the presence of Yamanaka factors) significantly improved the reprogramming efficiency of urine cells. We confirmed that the newly generated iPSCs possessed pluripotency characteristics similar to normal H1 embryonic stem cells. We also confirmed that the new iPSCs could differentiate to functional cardiomyocytes. Conclusions In conclusion, TEAD2, TEAD4 and ZIC3 can increase the efficiency of reprogramming human urine cells into iPSCs, and provides a new stem cell sources for the clinical application and modeling of cardiovascular disease. Graphical abstract

Cytotoxic triterpenoid glycosides from leaves of Cyclocarya paliurus - Hui-Hui Sun; Wen-Yan Lv; Jie Tan; Yu-Cheng Tang; Hui Zhu; Jian-Bo Qu; Jing Li; Jian-Ping Wu; Xi-Wen Chang; Zhi-Chun Yang; Wen-Xuan Wang; Zu-Hui Chen; et al. (Natural Product Research, 2021)

Geo-structures and deformation-failure characteristics of rockslide areas near the Baige landslide scar in the Jinsha River tectonic suture zone - Shi-lin Zhang; Yue-ping Yin; Xie-wen Hu; Wen-pei Wang; Zong-liang Li; Xin-ming Wu; Gang Luo; Sai-nan Zhu (Landslides, 2021)

Resource utilization of organic spent adsorbent to prepare three-dimensional sulfate-functionalized layered double oxide for superior removal of azo dye - Lingjie Zhang; Siyin Zheng; Peng Li; Zhongbang Zhu; Youqin Zou; Ping Zhang (Environmental Science and Pollution Research, 2021)

Deep profile soil moisture distribution characteristics for different micro-topographies on the semi-arid Loess Plateau, China - Qing-ping Gou; Qing-ke Zhu; Yi-xuan Li; Xiang-lei Tian; Peng-xiang Wang; Yun-ling Xin; Shu-yuan Luo (Journal of Mountain Science, 2021)

Detoxification of aflatoxin B 1 in broiler chickens by a triple-action feed additive - Hongwei Guo; Juan Chang; Ping Wang; Qingqiang Yin; Chaoqi Liu; Silu Li; Qun Zhu; Mingfan Yang; Xiaofei Hu (Food Additives & Contaminants: Part A, 2021)

The effects of plant–soil feedback on invasion resistance are soil context dependent - Pengdong Chen; Qiaoqiao Huang; Yanhui Zhuge; Chongwei Li; Ping Zhu; Yuping Hou (Oecologia, 2021)

A comparative study of peroxydisulfate and peroxymonosulfate activation by a transition metal–H2O2 system - Yanli Zhu; Yuan Liu; Ping Li; Yue Zhang; Gang Wang; Youxian Zhang (Environmental Science and Pollution Research, 2021)

Alpha-Lipoic Acid Attenuates Cadmium- and Lead-Induced Neurotoxicity by Inhibiting Both Endoplasmic-Reticulum Stress and Activation of Fas/FasL and Mitochondrial Apoptotic Pathways in Rat Cerebral Cortex - Yan Yuan; Shi Wen Zhao; Shuang Quan Wen; Qiao Ping Zhu; Li Wang; Hui Zou; Jian Hong Gu; Xue Zhong Liu; Jian Chun Bian; Zong Ping Liu (Neurotoxicity Research, 2021)

Phase field model for hydraulic fracture propagation in porous medium and numerical simulation analysis of hydraulic fracture propagation in a layered reservoir - Liang-Ping Yi; Chang-Xin Yang; Rui Chen; Jing-Yi Zhu; Xiao-Hua Zhu; Zhao-Zhong Yang; Xiao-Gang Li (Arabian Journal of Geosciences, 2021)

Cloud-Based Multidimensional Parallel Dynamic Programming Algorithm for a Cascade Hydropower System - Yufei Ma; Ping-an Zhong; Bin Xu; Feilin Zhu; Jieyu Li; Han Wang; Qingwen Lu (Water Resources Management, 2021)

Citrus NIP5;1 aquaporin regulates cell membrane water permeability and alters PIPs plasma membrane localization - Mingfei Zhang; Ruilian Liu; Hai Liu; Hongbin Yang; Xin Li; Ping Wang; Feng Zhu; Rangwei Xu; Shaowu Xue; Yunjiang Cheng (Plant Molecular Biology, 2021)

Characteristics of RNA alternative splicing and its potential roles in ginsenoside biosynthesis in a single plant of ginseng, Panax ginseng C.A. Meyer - Yilai Han; Lei Zhu; Li Li; Yanfang Wang; Mingzhu Zhao; Kangyu Wang; Chunyu Sun; Jing Chen; Lingyu Liu; Ping Chen; Jun Lei; Yi Wang; et al. (Molecular Genetics and Genomics, 2021)

Investigation of potential safety hazards during medical waste disposal in SARS-CoV-2 testing laboratory - Jun Lv; Jin Yang; Juan Xue; Ping Zhu; Lanfang Liu; Shan Li (Environmental Science and Pollution Research, 2021)
This study aims to investigate the potential safety hazards and provide reference for improving the medical waste disposal procedure in SARS-CoV-2 testing laboratory. Our SARS-CoV-2 testing group detected the RNA residue on the surface of medical waste with Droplet Digital PCR, and held a meeting to discuss the risks in the laboratory medical waste disposal process. After effective autoclaving, SARS-CoV-2 contaminated on the surface of medical waste bags was killed, but the average concentration of viral RNA residues was still 0.85 copies/cm 2 . It would not pose a health risk, but might contaminate the laboratory and affect the test results. When the sterilized medical waste bags were transferred directly by the operators without hand disinfection, re-contamination would happen, which might cause the virus to leak out of the laboratory. Furthermore, we found that sterilization effect monitoring and cooperation among operators were also very important. In summary, we investigated and analyzed the potential safety hazards during the medical waste disposal process in SARS-CoV-2 testing laboratory, and provided reasonable suggestions to ensure the safety of medical waste disposal.

Estimation of mountain block recharge on the northern Tianshan Mountains using numerical modeling - Jian-hua Ping; Ya-qiang Zhu; Xue-mei Mei; Wei Leng; Sheng Li; Ji-chang Zhao (Journal of Mountain Science, 2021)

Nutrigenomics reveals potential genetic underpinning of diverse taste preference of Chinese men - Zhouhai Zhu; Junpu Mei; Silong Sun; Sheming Lu; Meng Li; Ying Guan; Ying Chen; Yuqiong Xu; Tao Zhang; Fengxue Shi; Xuemei Li; Mingming Miao; et al. (Genes & Genomics, 2021)

Bjerkandera adusta M1 inhibits the growth of Fusarium oxysporum f. sp. conglutinans and fusarium wilt incidence in Brassica napus L. - Xiao Feng; Su-Ping Li; Yi-Fan Lu; Jing-Jie Zhang; Yun-Yun Zhu; Yong Li; Hong-Jun Yang; Xin-Hua He (Journal of Plant Pathology, 2021)

The highly conserved rps12 gene in ferns provides strong evidence for decreased substitution rates in the inverted repeat region - Jingyao Ping; Aimin Li; Peipei Feng; Ming Zhu; Yingjuan Su; Ting Wang (Plant Systematics and Evolution, 2021)

Dissipation behavior, residue dynamics, and dietary risk assessment of forchlorfenuron in postharvest kiwifruits during simulated cold chain logistics and store shelf life - Difeng Zhu; Li Ping; Renyun Qian; Chao Chen; Yawen Hong; Zhenxuan Tong; Xiaochun Yang (Environmental Science and Pollution Research, 2021)

Thermaurantiacus tibetensis gen. nov., sp. nov., a novel moderately thermophilic bacterium isolated from hot spring microbial mat in Tibet - Yu-Zhen Ming; Lan Liu; Ai-Ping Lv; Wen-Dong Xian; Ze-Tao Liu; Meng-Meng Li; Jian-Yu Jiao; Bao-Zhu Fang; Wen-Jun Li (Antonie van Leeuwenhoek, 2021)

Association of FMO3 rs1736557 polymorphism with clopidogrel response in Chinese patients with coronary artery disease - Kong-Xiang Zhu; Pei-Yuan Song; He-Li; Mu-Peng Li; Yin-xiao Du; Qi-lin Ma; Li-Ming Peng; Xiao-Ping Chen (European Journal of Clinical Pharmacology, 2021)

Exploring Brain Dynamic Functional Connectivity Using Improved Principal Components Analysis Based on Template Matching - Zhenghao Liu; Yuan Liu; Ping Zhao; Wen Li; Zhiyuan Zhu; Xiaotong Wen; Xia Wu (Brain Topography, 2021)

SIMS U-Pb geochronology for the Jurassic Yanliao Biota from Bawanggou section, Qinglong (northern Hebei Province, China) - Zhiqiang Yu; Huaiyu He; Gang Li; Chenglong Deng; Haibing Wang; Xinxin Zhang; Qing Yang; Xiao-Ping Xia; Zhonghe Zhou; Rixiang Zhu (International Geology Review, 2021)

The role of MYB proto-oncogene like 2 in tamoxifen resistance in breast cancer - Xia Li; Xi Zhang; Cong-Cong Wu; Ping-Ping Li; Yi-Mou Fu; Li-Hua Xie; Shuang-Shuang Sun; Ying-Ying Zhou; Bao-Ling Zhu (Journal of Molecular Histology, 2021)

The reproductive regulation of LPXRFa and its receptor in the hypothalamo-pituitary-gonadal axis of the spotted scat (Scatophagus argus) - Yi Zhai; Si-Ping Deng; Jian-Ye Liu; Dong-Neng Jiang; Yang Huang; Chun-Hua Zhu; Guang-Li Li; Ming-Hui Li (Fish Physiology and Biochemistry, 2021)

Improved Oral Bioavailability and Hypolipidemic Effect of Syringic Acid via a Self-microemulsifying Drug Delivery System - Congyong Sun; Wenjing Li; Huiyun Zhang; Michael Adu-Frimpong; Ping Ma; Yuan Zhu; Wenwen Deng; Jiangnan Yu; Ximing Xu (AAPS PharmSciTech, 2021)

Reactive oxygen species altering the metabolite profile of the marine-derived fungus Dichotomomyces cejpii F31-1 - Sharpkate Shaker; Ting-Ting Sun; Liang-Yue Wang; Wen-Zhe Ma; Dong-Lan Wu; Yong-Wei Guo; Jun Dong; Yan-Xiu Chen; Long-Ping Zhu; De-Po Yang; Hou-Jin Li; Wen-Jian Lan (Natural Product Research, 2021)

Transcriptome and ionome analysis of nitrogen, phosphorus and potassium interactions in sorghum seedlings - Zhenxing Zhu; Dan Li; Ping Wang; Jinhong Li; Xiaochun Lu (Theoretical and Experimental Plant Physiology, 2020)

Possible effects of leaf tissue characteristics of oilseed rape Brassica napus on probing and feeding behaviors of cabbage aphids Brevicoryne brassicae - Zhong-Ping Hao; Hai-Xia Zhan; Ling-Ling Gao; Fang Huang; Li-Ni Zhu; Shu-Min Hou (Arthropod-Plant Interactions, 2020)

Dietary lipid concentrations influence growth, body composition, morphology of the liver and mid-intestine, and antioxidant status of marbled eel (Anguilla marmorata) - Shi-Jun Chen; Peng Liu; You-Ming Jia; Hong-Ping Liao; Shao-Xuan Zhu; Li-Liu Zhou; Xue-Ming Dan; Li Liu; Jia-Hao Li; Su-Bi Zheng; Jun-Jiang Yang; Lian Gan (Aquaculture International, 2020)

Model test of the stability degradation of a prestressed anchored rock slope system in a corrosive environment - Cong Li; Rong-tang Zhang; Jie-bing Zhu; Zhi-jun Liu; Bo Lu; Bin Wang; Yu-zhou Jiang; Jie-sheng Liu; Ping Zeng (Journal of Mountain Science, 2020)

Experimental study on mechanical characteristics of unloaded damaged white sandstone before peak - Heng Ren; Yongjian Zhu; Ping Wang; Weijian Yu; Peng Li; Yuqun Zhang (Arabian Journal of Geosciences, 2020)

Identification and fine mapping of spot blotch (Bipolaris sorokiniana) resistance gene Sb4 in wheat - Panpan Zhang; Guanghao Guo; Qiuhong Wu; Yongxing Chen; Jingzhong Xie; Ping Lu; Beibei Li; Lingli Dong; Miaomiao Li; Rongge Wang; Chengguo Yuan; Huaizhi Zhang; et al. (Theoretical and Applied Genetics, 2020)

Impacts of climate anomalies on the interannual and interdecadal variability of autumn and winter haze in North China: A review - Jing Wang; Yanju Liu; Yihui Ding; Ping Wu; Zhiwei Zhu; Ying Xu; Qiaoping Li; Yingxian Zhang; Jinhai He; Julian X. L. Wang; Li Qi (International Journal of Climatology, 2020)
From the perspectives of remote sensing and climatic factors like surface meteorological parameters, large‐scale atmospheric circulations, and external forcing factors (EFFs), the authors synthesize and review spatiotemporal variations of PM 2.5 over North China and how climate anomalies affect autumn and winter haze variability in North China according to recent studies. This review focuses on both interannual and interdecadal timescales. It is shown that circulations play an important role in influencing haze variability. Atmospheric circulations, which would be modulated by EFFs like sea surface temperature, sea ice, and snowpack, can affect the climate variability in haze over North China via modulation of surface‐layer parameters that are closely connected with the haze phenomenon. Therefore, EFFs are deemed significant factors impacting the climate variability of haze over North China, serving as paramount precursory signals for haze prediction. Furthermore, this paper suggests potential future research directions for haze variability studies in North China on the basis of summarizing and concluding the associated processes/mechanisms on how climatic factors affect haze variability, which could provide reference for treating and forecasting in situ hazy conditions.

High-level soluble expression of human Cu,Zn superoxide dismutase with high activity in Escherichia coli - Jin-Ling Yang; Xing-Lun Li; Feng-Lin Jiang; Ting Gong; Jing-Jing Chen; Tian-Jiao Chen; Ping Zhu (World Journal of Microbiology and Biotechnology, 2020)

Altered Energy Metabolism During Early Optic Nerve Crush Injury: Implications of Warburg-Like Aerobic Glycolysis in Facilitating Retinal Ganglion Cell Survival - Jingyi Zhu; Ping Li; Yuan-Guo Zhou; Jian Ye (Neuroscience Bulletin, 2020)
Neurons, especially axons, are metabolically demanding and energetically vulnerable during injury. However, the exact energy budget alterations that occur early after axon injury and the effects of these changes on neuronal survival remain unknown. Using a classic mouse model of optic nerve-crush injury, we found that traumatized optic nerves and retinas harbor the potential to mobilize two primary energetic machineries, glycolysis and oxidative phosphorylation, to satisfy the robustly increased adenosine triphosphate (ATP) demand. Further exploration of metabolic activation showed that mitochondrial oxidative phosphorylation was amplified over other pathways, which may lead to decreased retinal ganglion cell (RGC) survival despite its supplement to ATP production. Gene set enrichment analysis of a microarray (GSE32309) identified significant activation of oxidative phosphorylation in injured retinas from wild-type mice compared to those from mice with deletion of phosphatase and tensin homolog (PTEN), while PTEN-/- mice had more robust RGC survival. Therefore, we speculated that the oxidation-favoring metabolic pattern after optic nerve-crush injury could be adverse for RGC survival. After redirecting metabolic flux toward glycolysis (magnifying the Warburg effect) using the drug meclizine, we successfully increased RGC survival. Thus, we provide novel insights into a potential bioenergetics-based strategy for neuroprotection.

The bHLH gene family and its response to saline stress in Jilin ginseng, Panax ginseng C.A. Meyer - Lei Zhu; Mingzhu Zhao; Mengyao Chen; Li Li; Yue Jiang; Sizhang Liu; Yang Jiang; Kangyu Wang; Yanfang Wang; Chunyu Sun; Jing Chen; Ping Chen; et al. (Molecular Genetics and Genomics, 2020)

Rainfall manipulation experiments as simulated by terrestrial biosphere models: Where do we stand? - Athanasios Paschalis; Simone Fatichi; Jakob Zscheischler; Philippe Ciais; Michael Bahn; Lena Boysen; Jinfeng Chang; Martin De Kauwe; Marc Estiarte; Daniel Goll; Paul J. Hanson; Anna B. Harper; et al. (Global Change Biology, 2020)
Changes in rainfall amounts and patterns have been observed and are expected to continue in the near future with potentially significant ecological and societal consequences. Modelling vegetation responses to changes in rainfall is thus crucial to project water and carbon cycles in the future. In this study, we present the results of a new model‐data intercomparison project, where we tested the ability of 10 terrestrial biosphere models to reproduce the observed sensitivity of ecosystem productivity to rainfall changes at 10 sites across the globe, in nine of which, rainfall exclusion and/or irrigation experiments had been performed. The key results are as follows: (a) Inter‐model variation is generally large and model agreement varies with timescales. In severely water‐limited sites, models only agree on the interannual variability of evapotranspiration and to a smaller extent on gross primary productivity. In more mesic sites, model agreement for both water and carbon fluxes is typically higher on fine (daily–monthly) timescales and reduces on longer (seasonal–annual) scales. (b) Models on average overestimate the relationship between ecosystem productivity and mean rainfall amounts across sites (in space) and have a low capacity in reproducing the temporal (interannual) sensitivity of vegetation productivity to annual rainfall at a given site, even though observation uncertainty is comparable to inter‐model variability. (c) Most models reproduced the sign of the observed patterns in productivity changes in rainfall manipulation experiments but had a low capacity in reproducing the observed magnitude of productivity changes. Models better reproduced the observed productivity responses due to rainfall exclusion than addition. (d) All models attribute ecosystem productivity changes to the intensity of vegetation stress and peak leaf area, whereas the impact of the change in growing season length is negligible. The relative contribution of the peak leaf area and vegetation stress intensity was highly variable among models.

Tenuazonic acid-induced change in volatile emission from rose plants and its chemometrical analysis - Fa-zhong Yang; Yun-xian Li; Min Tang; Guo-lei Zhu; Shi-ping Zhou; Bin Yang (Journal of Plant Diseases and Protection, 2020)

Roles of PTBP1 in alternative splicing, glycolysis, and oncogensis - Wei Zhu; Bo-lun Zhou; Li-juan Rong; Li Ye; Hong-juan Xu; Yao Zhou; Xue-jun Yan; Wei-dong Liu; Bin Zhu; Lei Wang; Xing-jun Jiang; Cai-ping Ren (Journal of Zhejiang University-SCIENCE B, 2020)

Soil types differentiated their responses of aggregate stability to hydrological stresses at the riparian zones of the Three Gorges Reservoir - Yiguo Ran; Shengjun Wu; Kai Zhu; Wenjuan Li; Zhimei Liu; Ping Huang (Journal of Soils and Sediments, 2020)

Reduction of the Criteria System for Identifying Effective Reservoirs in the Joint Operation of a Flood Control System - Jieyu Li; Ping-an Zhong; Feilin Zhu; Juan Chen; Minzhi Yang; Jisi Fu; Weifeng Liu (Water Resources Management, 2020)

Expression and Function of Mas-Related G Protein-Coupled Receptor D and Its Ligand Alamandine in Retina - Ping Zhu; Amrisha Verma; Tuhina Prasad; Qiuhong Li (Molecular Neurobiology, 2020)

Identification of rs11615992 as a novel regulatory SNP for human P2RX7 by allele-specific expression - Tao Peng; Li Zhong; Jing Gao; Zhu Wan; Wei-Ping Fu; Chang Sun (Molecular Genetics and Genomics, 2020)

Comparative transcriptome analysis of male and female gonads reveals sex-biased genes in spotted scat (Scatophagus argus) - Fei-Xiang He; Dong-Neng Jiang; Yuan-Qing Huang; Umar Farouk Mustapha; Wei Yang; Xue-Fan Cui; Chang-Xu Tian; Hua-Pu Chen; Hong-Juan Shi; Si-Ping Deng; Guang-Li Li; Chun-Hua Zhu (Fish Physiology and Biochemistry, 2019)

Thermus caldilimi sp. nov., a thermophilic bacterium isolated from a geothermal area - Meng-Meng Li; Wen-Dong Xian; Xiao-Tong Zhang; Yi-Rui Yin; En-Min Zhou; Yi-Ping Ding; Lan Liu; Bao-Zhu Fang; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

Accumulation and Depuration of Nonylphenol and Its Effect on the Expressions of Vitellogenin and Vitellogenin Receptor in Freshwater Prawn Macrobrachium rosenbergii - Hui Guo; Luan-luan Chen; Guang-li Li; Si-ping Deng; Chun-hua Zhu (Bulletin of Environmental Contamination and Toxicology, 2019)

Development, Optimization, and Evaluation In Vitro/In Vivo of Oral Liquid System for Synchronized Sustained Release of Levodopa/Benserazide - Yang Qu; Wen-Long Lai; Yuan-Rong Xin; Fei-Qin Zhu; Yuan Zhu; Li Wang; Yue-ping Ding; Ying Xu; Hong-Fei Liu (AAPS PharmSciTech, 2019)

A new abietane diterpenoid glycoside from ajuga ovalifolia var. calantha - Fan Yang; Hong-Ping Chen; Xiao-Fei Shen; Hu-Lan Chen; Yin Chen; Li-Xia Wang; Hai Zhang; Wen-Ji Zhao; Mei Zhang; Yu-Zhu Tan (Natural Product Research, 2019)

c-Myc induced the regulation of long non-coding RNA RHPN1-AS1 on breast cancer cell proliferation via inhibiting P53 - Pei Zhu; Yan Li; Ping Li; Yuying Zhang; Xiaowei Wang (Molecular Genetics and Genomics, 2019)

Influence of Different Propulsion Speeds on the Characteristics of Mine Pressure in the Fully Mechanized Caving Face During Rotary Stage - Liang Li; Xue He; Yong-qiang Chen; Ya-chun Li; Chen-hao Shi; Yu-ping Zhu (Geotechnical and Geological Engineering, 2019)

Comparative effects of some extraction solvents on the antimicrobial activity of Eucalyptus camaldulensis leaf, bud, capsule and seed crude extracts - Alyaa Nasr; Xinxin Zhou; Shi-Ping Huang; Yuan Wang; Xiaoning Li; Guo-Ping Zhu (Natural Product Research, 2019)

High-altitude and long-range transport of aerosols causing regional severe haze during extreme dust storms explains why afforestation does not prevent storms - Ping Guo; Shaocai Yu; Liqiang Wang; Pengfei Li; Zhen Li; Khalid Mehmood; Xue Chen; Weiping Liu; Yannian Zhu; Xing Yu; Kiran Alapaty; Eric Lichtfouse; et al. (Environmental Chemistry Letters, 2019)

Three-dimensional identification of hydrological drought and multivariate drought risk probability assessment in the Luanhe River basin, China - Xu Chen; Fa-wen Li; Jian-zhu Li; Ping Feng (Theoretical and Applied Climatology, 2019)

Evaluation of TIGGE Daily Accumulated Precipitation Forecasts over the Qu River Basin, China - Li Liu; Chao Gao; Qian Zhu; Yue-Ping Xu (Journal of Meteorological Research, 2019)

F‐box proteins MoFwd1, MoCdc4 and MoFbx15 regulate development and pathogenicity in the rice blast fungus Magnaporthe oryzae - Huan‐Bin Shi; Nan Chen; Xue‐Ming Zhu; Shuang Liang; Lin Li; Jiao‐Yu Wang; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2019)
Summary The Skp1‐Cul1‐F‐box‐protein (SCF) ubiquitin ligases are important parts of the ubiquitin system controlling many cellular biological processes in eukaryotes. However, the roles of SCF ubiquitin ligases remain unclear in phytopathogenic Magnaporthe oryzae . Here, we cloned 24 F‐box proteins and confirmed that 17 proteins could interact with MoSkp1, showing their potential to participate in SCF complexes. To determine their functions, null mutants of 21 F‐box‐containing genes were created. Among them, the F‐box proteins MoFwd1, MoCdc4 and MoFbx15 were found to be required for growth, development and full virulence. Fluorescent‐microscopy observations demonstrated that both MoFbx15 and MoCdc4 were localized to the nucleus, compared with MoFwd1, which was distributed in the cytosol. MoCdc4 and MoFwd1 bound to MoSkp1 via the F‐box domain, the deletion of which abrogated their function. Race tube and qRT‐PCR assays confirmed that MoFwd1 was involved in circadian rhythm by regulating transcription and protein stability of the core circadian clock regulator MoFRQ . Moreover, MoFWD1 also orchestrates conidial germination by influencing conidial amino acids pools and oxidative stress release. Overall, our results indicate that SCF ubiquitin ligases play indispensable roles in development and pathogenicity in M. oryzae .

Improving the simulation of East Asian summer monsoon with mesoscale enhancement in an AGCM - Zhongxian Li; Ping He; Jieshun Zhu; Haishan Chen; Gang Zeng; Weitao Deng (Climate Dynamics, 2019)

Lateral Organ Boundaries Domain 19 (LBD19) negative regulate callus formation in Arabidopsis - Siqi Liu; Bo Wang; Xiaojing Li; Jingxian Pan; Xuexue Qian; Yahui Yu; Ping Xu; Jian Zhu; Xiaofeng Xu (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Potential effects of exploiting the Yunfu pyrite mine (southern China) on soil: evidence from analyzing trace elements in surface soil - Zhi-hua Tang; Ting-ping Ouyang; Ming-kun Li; Ning-sheng Huang; Yao-qiu Kuang; Qiao Hu; Zhao-yu Zhu (Environmental Monitoring and Assessment, 2019)

Synthesis and antitumor activity of cyclic octapeptide, samoamide A, and its derivatives - Fei Ge; Chi Zhang; Longbao Zhu; Wanzhen Li; Ping Song; Yugui Tao; Guocheng Du (Medicinal Chemistry Research, 2019)

Sediment transport in the Luanhe River delta: grain size trend analysis - Xiaoxiao Yu; Tiegang Li; Dongqi Gu; Aiping Feng; Shihao Liu; Ping Li; Guoqiang Xu; Wenwen Yan; Zhiwei Zhang; Zhengtao Zhu (Journal of Oceanology and Limnology, 2019)

Gene structure, recombinant expression and function characterization of Siniperca chuatsi Fsrp‐3 - Jianhua Wang; Jia Cheng; Yulong Li; Huiling Yan; Ping Wu; Xin Zhu; Li Liu; Lin Chen; Wuying Chu; Jianshe Zhang (Journal of Fish Biology, 2019)
A full‐length complementary (c)DNA sequence encoding follistatin‐related protein 3 ( fsrp‐3 ) was determined from skeletal muscle in Chinese mandarin fish Siniperca chuatsi , its molecular structure was characterised and its function suggested. The putative structure of S. chuatsi Fsrp‐3 contains an N‐terminal domain and two follistatin domains. Quantitative reverse‐transcription (qRT)‐PCR assays revealed that fsrp‐3 messenger (m)RNA was differentially expressed among assayed tissues and was highly expressed in heart and intestine. fsrp‐3 mRNA exhibited increasing expression from the larval to the juvenile stage (500 g). To investigate the potential function of S. chuatsi fsrp‐3 in muscle growth, we constructed a Fsrp‐3 prokaryotic expression system and injected the purified Fsrp‐3 fusion protein into the dorsal muscle. Fsrp‐3 administration significantly influenced cross‐section area, satellite cell activation frequency and nuclear density of S. chuatsi muscle fibres. Following Fsrp‐3 treatment, the expression of myogenic regulatory factors was up‐regulated and decline in the expression of myostatin was observed. The study revealed that Fsrp‐3 may affect muscle growth by regulating myogenic regulatory factor expression and antagonizing myostatin function to initiate satellite cell activation and differentiation in S. chuatsi .

Polymorphism analyses of 19 STRs in Labrador Retriever population from China and its heterozygosity comparisons with other retriever breeds - Meng-Lei Wang; Xiao-Ye Jin; Xin Xiong; Jin-Long Yang; Jian-Ping Li; Qi Wang; Bo-Feng Zhu; Ya-Jun Deng (Molecular Biology Reports, 2019)

Enhanced water solubility, antioxidant activity, and oral absorption of hesperetin by D-α-tocopheryl polyethylene glycol 1000 succinate and phosphatidylcholine - Su-Fang Gu; Li-Ying Wang; Ying-Jie Tian; Zhu-Xian Zhou; Jian-Bin Tang; Xiang-Rui Liu; Hai-Ping Jiang; You-Qing Shen (Journal of Zhejiang University-SCIENCE B, 2019)

Clinical application of cross microsurgical vasovasostomy in scrotum for atypical obstructive azoospermia - Zhong-Yan Liang; Feng-Bin Zhang; Le-Jun Li; Jing-Ping Li; Jing-Gen Wu; Chong Chen; Yi-Min Zhu (Journal of Zhejiang University-SCIENCE B, 2019)

Dynamics of maize straw residue 13C incorporation into aggregates of a Mollisol as affected by long-term fertilization - Ming Li; Yang Wang; Fan Ding; Yingde Xu; Ping Zhu; Xueli Ding; Jingkuan Wang (Journal of Soils and Sediments, 2019)

Habitat selection of wintering cranes (Gruidae) in typical lake wetland in the lower reaches of the Yangtze River, China - Cheng Wang; Bin Dong; Ming Zhu; Hui Huang; Yu-huang Cui; Xiang Gao; Li-ping Liu (Environmental Science and Pollution Research, 2019)

Landslide integrated characteristics and susceptibility assessment in Rongxian county of Guangxi, China - Li-ping Liao; Ying-yan Zhu; Yan-lin Zhao; Hai-tao Wen; Yun-chuan Yang; Li-hua Chen; Shao-kun Ma; Ying-zi Xu (Journal of Mountain Science, 2019)

Microsatellite records for volume 11, issue 1 - Da-Qing Chen; Zaijie Dong; Min Fang; Jianjun Fu; Xiang-Yang Jia; Bingjie Jiang; Jingmiao Li; Qingqing Li; Suhui Liao; Ping Liu; Yulin Liu; Guocheng Shu; et al. (Conservation Genetics Resources, 2019)

Long noncoding RNA UCA1 promotes the proliferation of hypoxic human pulmonary artery smooth muscle cells - Tian-Tian Zhu; Rui-Li Sun; Ya-Ling Yin; Jin-Ping Quan; Ping Song; Jian Xu; Ming-Xiang Zhang; Peng Li (Pflügers Archiv - European Journal of Physiology, 2019)

Coexpression of FOXK1 and vimentin promotes EMT, migration, and invasion in gastric cancer cells - Hui Zhang; Xiaosheng Wu; Yizhi Xiao; Liqing Wu; Ying Peng; Weimei Tang; Guangnan Liu; Yong Sun; Jing Wang; Huiqiong Zhu; Mengwei Liu; Wenjing Zhang; et al. (Journal of Molecular Medicine, 2019)

HERV-W env regulates calcium influx via activating TRPC3 channel together with depressing DISC1 in human neuroblastoma cells - Yatang Chen; Qiujin Yan; Ping Zhou; Shan Li; Fan Zhu (Journal of NeuroVirology, 2019)

Daedaleanols A and B, two new sesquiterpenes from cultures of the basidiomycete Daedalea incana - Ying Huang; Shuai-Bing Zhang; He-Ping Chen; Zhen-Zhu Zhao; Zheng-Hui Li; Tao Feng; Ji-Kai Liu (Natural Product Research, 2019)

Macrolide sesquiterpene pyridine alkaloids from the stems of Tripterygium regelii - Dongsheng Fan; Ting Li; Zhiyuan Zheng; Guo-Yuan Zhu; Xiaojun Yao; Zhi-Hong Jiang; Li-Ping Bai (Journal of Natural Medicines, 2019)

Laminar Distribution of Neurochemically-Identified Interneurons and Cellular Co-expression of Molecular Markers in Epileptic Human Cortex - Qiyu Zhu; Wei Ke; Quansheng He; Xiongfei Wang; Rui Zheng; Tianfu Li; Guoming Luan; Yue-Sheng Long; Wei-Ping Liao; Yousheng Shu (Neuroscience Bulletin, 2018)

Increased productivity of l-2-aminobutyric acid and total turnover number of NAD+/NADH in a one-pot system through enhanced thermostability of l-threonine deaminase - Ying Wang; Guo-Si Li; Pei Qiao; Ling Lin; Hai-Long Xue; Li Zhu; Mian-Bin Wu; Jian-Ping Lin; Li-Rong Yang (Biotechnology Letters, 2018)

Development and characterization of 27 SNP markers in the Mauremys mutica transcriptome - Zhang Xin-Cheng; Zhao Jian; Li Wei; Liu Yi-Hui; Wei Cheng-Qing; Wang Ya-Kun; Ye Zhao-Yang; Zhu Xin-Ping (Conservation Genetics Resources, 2018)

Molecular insights into brown rust resistance and potential epidemic based on the Bru1 gene in sugarcane varieties and new elite clones - Zhu Li; Ya-Chun Su; Qing Yu; Yun Chen; Shi-Wu Gao; Yong-Gang Zhang; You-Xiong Que; Li-Ping Xu (Euphytica, 2018)

Solvent effects on quantitative analysis of brominated flame retardants with Soxhlet extraction - Yin Zhong; Dan Li; Xifen Zhu; Weilin Huang; Ping’an Peng (Environmental Geochemistry and Health, 2018)

Comparison of gene co-networks reveals the molecular mechanisms of the rice (Oryza sativa L.) response to Rhizoctonia solani AG1 IA infection - Jinfeng Zhang; Wenjuan Zhao; Rong Fu; Chenglin Fu; Lingxia Wang; Huainian Liu; Shuangcheng Li; Qiming Deng; Shiquan Wang; Jun Zhu; Yueyang Liang; Ping Li; et al. (Functional & Integrative Genomics, 2018)

Thimet oligopeptidase and prolyl endopeptidase of spotted scat Scatophagus argus: characterization, tissue distribution, expression at different ovarian stages and down-regulation by estradiol - Si-ping Deng; Dong-neng Jiang; Jian-ye Liu; Zhi-qi Liang; Hua-pu Chen; Tian-li Wu; Chun-hua Zhu; Guang-li Li (Fisheries Science, 2018)

Soil infiltration processes of different underlying surfaces in the permafrost region on the Tibetan Plateau - Guo-jie Hu; Li-ming Tian; Lin Zhao; Xiao-dong Wu; Ren Li; Tong-hua Wu; Xiao-fan Zhu; Er-ji Du; Zhi-wei Wang; Jun-ming Hao; Wang-ping Li; Song-he Wang (Hydrological Sciences Journal, 2018)

The role of HMGB1 in BMSC transplantation for treating MODS in rats - Guanghui Xiu; Jie Sun; Xiuling Li; Hua Jin; Yichao Zhu; Xia Zhou; Ping Liu; Xinghua Pan; Jian Li; Bin Ling (Cell and Tissue Research, 2018)

CFTR prevents neuronal apoptosis following cerebral ischemia reperfusion via regulating mitochondrial oxidative stress - Ya-Ping Zhang; Yong Zhang; Zhi-Bin Xiao; Yan-Bo Zhang; Jing Zhang; Zhi-Qiang Li; Yao-Bin Zhu (Journal of Molecular Medicine, 2018)

Climatology of tracked persistent maxima of 500-hPa geopotential height - Ping Liu; Yuejian Zhu; Qin Zhang; Jon Gottschalck; Minghua Zhang; Christopher Melhauser; Wei Li; Hong Guan; Xiaqiong Zhou; Dingchen Hou; Malaquias Peña; Guoxiong Wu; et al. (Climate Dynamics, 2018)

Inhibition of KLF7-Targeting MicroRNA 146b Promotes Sciatic Nerve Regeneration - Wen-Yuan Li; Wei-Ting Zhang; Yong-Xia Cheng; Yan-Cui Liu; Feng-Guo Zhai; Ping Sun; Hui-Ting Li; Ling-Xiao Deng; Xiao-Feng Zhu; Ying Wang (Neuroscience Bulletin, 2018)

Diversity effect of capsaicin on different types of skeletal muscle - Gan Zhou; Lina Wang; Yaqiong Xu; Kelin Yang; Lv Luo; Leshan Wang; Yongxiang Li; Jiawen Wang; Gang Shu; Songbo Wang; Ping Gao; Xiaotong Zhu; et al. (Molecular and Cellular Biochemistry, 2018)

The complete mitochondrial genome of Kele pig (Sus scrofa) using next-generation deep sequencing - Ya Tan; Kai-zhi Shi; Jing Wang; Chun-lin Du; Chun-ping Zhao; Xiong Zhang; Li Zhu; Yi-shun Shang (Conservation Genetics Resources, 2018)

OsPKS2 is required for rice male fertility by participating in pollen wall formation - Ting Zou; Mingxing Liu; Qiao Xiao; Tao Wang; Dan Chen; Tao Luo; Guoqiang Yuan; Qiao Li; Jun Zhu; Yueyang Liang; Qiming Deng; Shiquan Wang; et al. (Plant Cell Reports, 2018)

Recent advances in enhanced enzyme activity, thermostability and secretion by N-glycosylation regulation in yeast - Fei Ge; Longbao Zhu; Anna Aang; Ping Song; Wanzhen Li; Yugui Tao; Guocheng Du (Biotechnology Letters, 2018)

Tau-Induced Ca2+/Calmodulin-Dependent Protein Kinase-IV Activation Aggravates Nuclear Tau Hyperphosphorylation - Yu-Ping Wei; Jin-Wang Ye; Xiong Wang; Li-Ping Zhu; Qing-Hua Hu; Qun Wang; Dan Ke; Qing Tian; Jian-Zhi Wang (Neuroscience Bulletin, 2018)

Species-based classification reveals spatial processes of phytoplankton meta-communities better than functional group approaches: a case study from three freshwater lake regions in China - Li-Juan Xiao; Yiqiu Zhu; Yang Yang; Qiuqi Lin; Bo-Ping Han; Judit Padisák (Hydrobiologia, 2018)

A Semi-analytical Model for Pressure-Dependent Permeability of Tight Sandstone Reservoirs - Su-Yang Zhu; Zhi-Min Du; Chuan-Liang Li; Alireza Salmachi; Xiao-Long Peng; Chao-Wen Wang; Ping Yue; Peng Deng (Transport in Porous Media, 2018)

The complete mitogenome of Pelochelys cantorii (Guangning) and the comparative analysis of different habitats - Xin-cheng Zhang; Wei Li; Jian Zhao; Hai-gang Chen; Xin-ping Zhu (Conservation Genetics Resources, 2018)

A study of variation characteristics of Gobi broadband emissivity based on field observational experiments in northwestern China - Zhi-yuan Zheng; Zhi-gang Wei; Zhi-ping Wen; Wen-jie Dong; Zhen-chao Li; Xiao-hang Wen; Xian Zhu; Chen Chen; Shan-shan Hu (Theoretical and Applied Climatology, 2018)

Mfn2-Mediated Preservation of Mitochondrial Function Contributes to the Protective Effects of BHAPI in Response to Ischemia - Xiao-Li Chen; Guo-Ping Zhang; Sheng-Long Guo; Jia-Qi Ding; Jia-Ji Lin; Qian Yang; Zhu-Yi Li (Journal of Molecular Neuroscience, 2017)

Effect of hydrogen-rich water on vase life and quality in cut lily and rose flowers - Peng-Ju Ren; Xin Jin; Wei-Biao Liao; Meng Wang; Li-Juan Niu; Xue-Ping Li; Xiao-Ting Xu; Yong-Chao Zhu (Horticulture, Environment, and Biotechnology, 2017)

QTL mapping of agronomically important traits in sorghum (Sorghum bicolor L.) - Chunming Bai; Chunyu Wang; Ping Wang; Zhenxing Zhu; Ling Cong; Dan Li; Yifei Liu; Wenjing Zheng; Xiaochun Lu (Euphytica, 2017)

Kinetics of Antioxidant-Producing Maillard Reaction in the Mixture of Ribose and Sea Cucumber ( Stichopus japonicus ) Gut Hydrolysates - Jia-Run Han; Zhi-Mo Zhu; Hai-Tao Wu; Na Sun; Yue Tang; Cui-Ping Yu; Chen-Chen Zhao; Zheng-Yu Zhang; Ao-Ting Li; Jia-Nan Yan (Journal of Aquatic Food Product Technology, 2017)

Toxicity comparison of different active fractions extracted from radix Sophorae tonkinensis in zebrafish - Hong-cui Liu; Xiao-yu Zhu; Jiang-hua Chen; Sheng-ya Guo; Chun-qi Li; Zhong-ping Deng (Journal of Zhejiang University-SCIENCE B, 2017)

Protective effect of dihydropteridine reductase against oxidative stress is abolished with A278C mutation - Yan-ting Gu; Yan-chun Wang; Hao-jun Zhang; Ting-ting Zhao; Si-fan Sun; Hua Wang; Bin Zhu; Ping Li (Journal of Zhejiang University-SCIENCE B, 2017)

A live gI/gE-deleted pseudorabies virus (PRV) protects weaned piglets against lethal variant PRV challenge - Yue Yin; Zhiwen Xu; Xiaowan Liu; Ping Li; Fan Yang; Jun Zhao; Yi Fan; Xiangang Sun; Ling Zhu (Virus Genes, 2017)

Isolation and characterisation of the epothilone gene cluster with flanks from high alkalotolerant strain Sorangium cellulosum (So0157-2) - Zhi-Feng Li; Li-Ping Zhu; Jing-yan Gu; Raghvendra Pratap Singh; Yue-Zhong Li (World Journal of Microbiology and Biotechnology, 2017)

HMGB1 attenuates TGF-β-induced epithelial–mesenchymal transition of FaDu hypopharyngeal carcinoma cells through regulation of RAGE expression - Yanmei Li; Ping Wang; Jia Zhao; Haonan Li; Dahai Liu; Wei Zhu (Molecular and Cellular Biochemistry, 2017)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

Environmental change and raw material selection strategies at Taoshan: a terminal Late Pleistocene to Holocene site in north‐eastern China - Shi‐Xia Yang; Yu‐Xiu Zhang; You‐Qian Li; Chao Zhao; Xiao‐Qiang Li; Jian‐Ping Yue; Ya‐Mei Hou; Cheng‐Long Deng; Ri‐Xiang Zhu; Michael D. Petraglia (Journal of Quaternary Science, 2017)
The Lesser Khingan Mountains of north‐eastern China are heavily forested, making archaeological site identification difficult owing to poor ground surface visibility. Nevertheless, several prehistoric archaeological site discoveries have been made in recent years and a limited number of excavations have been initiated. One of the most important sites to emerge is Taoshan, which has yielded stratified stone tool assemblages dating from the Last Glacial Maximum (LGM) to the mid‐Holocene. Pollen profiles indicate significant changes in vegetation, fluctuating from steppe conditions during the LGM to forested conditions in the Bølling–Allerød interstadial (B–A) and the mid‐Holocene. The stone tool assemblages from Taoshan were primarily produced from varieties of volcanic tuff, rhyolite, hornfels and agate. Geological prospecting and petrological analyses were performed to document procurement sources and changes in raw material exploitation strategies. During the LGM, the predominant raw material was vitric tuff, available from a source ca. 5–10 km from Taoshan. In the B–A and mid‐Holocene layers, emphasis was on the exploitation of raw materials in gravel bars, although stone tool reduction techniques and raw material preferences changed considerably during this time interval. Diachronic changes in raw materials and exploitation strategies correspond to changes in vegetation and human adaptations.

LecRK-VII.1, a Lectin Receptor-Like Kinase, Mediates the Regulation of Salt Stress and Jasmonic Acid Response in Arabidopsis - Cheng Zhang; Jinyan Li; Xinhong Guo; Baode Zhu; Wenjun Xiao; Ping Wang; Miao Jiang; Shuai Hu; Xiutao Lu; Zhuang He; Ping Chen (Journal of Plant Growth Regulation, 2017)

Isolation and characterization of regulators involved in PHOT1-mediated inhibition of hypocotyl phototropism in Arabidopsis - Qing-Ping Zhao; Xiang Zhao; Zi-Yi Zhu; Xi-ning Guo; Nan-Nan Li; Xiao Zhang (Biologia, 2017)

Repellence of the main components from the essential oil of Glycosmis lucida Wall. ex Huang against two stored product insects - Shan-Shan Guo; Wen-Juan Zhang; Kai Yang; Jun-Yu Liang; Chun-Xue You; Cheng-Fang Wang; Yin-Ping Li; Zhu-Feng Geng; Zhi-Wei Deng; Shu-Shan Du (Natural Product Research, 2017)

Effects of melanocortin-4 receptor agonists and antagonists on expression of genes related to reproduction in spotted scat, Scatophagus argus - Dong-Neng Jiang; Jian-Tao Li; Ya-Xiong Tao; Hua-Pu Chen; Si-Ping Deng; Chun-Hua Zhu; Guang-Li Li (Journal of Comparative Physiology B, 2017)

Solanerioside A, an unusual 14,15-dinor-cyclophytane glucoside from the leaves of Solanum erianthum - Shi-yi Peng; Hang Li; De-po Yang; Bai Bai; Long-ping Zhu; Qin Liu; Juan Shen; Zhi-min Zhao (Natural Product Research, 2017)

NMR solution structure study of one saturated sulphur-containing amides from Glycosmis lucida - Zhu-Feng Geng; Kai Yang; Yin-Ping Li; Shan-Shan Guo; Chun-Xue You; Wen-Juan Zhang; Zhe Zhang; Shu-Shan Du (Natural Product Research, 2017)

Sap flow-based transpiration in Phyllostachys pubescens: applicability of the TDP methodology, age effect and rhizome role - Zhao Xiu-hua; Zhao Ping; Zhang Zhen-zhen; Zhu Li-wei; Niu Jun-feng; Ni Guang-yan; Hu Yan-ting; Ouyang Lei (Trees, 2017)

Cd Content in Sugarcane and Its Relationship with Soil Factors - Hui-Ping Ou; Liu-Qiang Zhou; Xi-Hui Liu; Jin-Sheng Huang; Yan Zeng; Ru-Lin Xie; Xiao-Hui Zhu; Hong-Wei Tan; Yang-Rui Li (Sugar Tech, 2017)

An UDP-Glucosyltransferase Gene from Barley Confers Disease Resistance to Fusarium Head Blight - Li-Ping Xing; Li-Qiang He; Jin Xiao; Qi-Guang Chen; Ming-Hao Li; Yi Shang; Yan-Fei Zhu; Pei-Du Chen; Ai-Zhong Cao; Xiu-E Wang (Plant Molecular Biology Reporter, 2017)

The critical role of ABCG1 and PPARγ/LXRα signaling in TLR4 mediates inflammatory responses and lipid accumulation in vascular smooth muscle cells - Xiaojie Cao; Lili Zhang; Chunhai Chen; Qingsong Wang; Lu Guo; Qinlong Ma; Ping Deng; Gang Zhu; Binghu Li; Yan Pi; Chunyan Long; Lei Zhang; et al. (Cell and Tissue Research, 2017)

Neoproterozoic alkaline intrusive complex in the northwestern Yangtze Block, Micang Mountains region, South China: petrogenesis and tectonic significance - Bao-Ping Gan; Shao-Cong Lai; Jiang-Feng Qin; Ren-Zhi Zhu; Shao-Wei Zhao; Tong Li (International Geology Review, 2017)

Thermal effects on development and adult longevity of endoparasitoid Chelonus murakatae Munakata (Hymenoptera: Braconidae) - Sundas Rana Qureshi; Wei-Li Quan; Rui-Qi Zhou; Fen Zhu; Xiao-Ping Wang (Environmental Science and Pollution Research, 2017)

Leptin receptor overlapping transcript: characterization, tissue distribution and changes in gene expression in response to eyestalk ablation in the Pacific white shrimp Litopenaeus vannamei - Si-Ping Deng; Hua-Pu Chen; Chun-Hua Zhu; Man Ye; Guang-Li Li (Fisheries Science, 2017)

Fine mapping of the Rsv1-h gene in the soybean cultivar Suweon 97 that confers resistance to two Chinese strains of the soybean mosaic virus - Fang-Fang Ma; Xiao-Yi Wu; Yun-Xia Chen; Ying-Na Liu; Zhu-Qing Shao; Ping Wu; Mian Wu; Cheng-Chen Liu; Wen-Ping Wu; Jia-Yin Yang; De-Xiao Li; Jian-Qun Chen; et al. (Theoretical and Applied Genetics, 2016)

NF-κB is involved in the LPS-mediated proliferation and apoptosis of MAC-T epithelial cells as part of the subacute ruminal acidosis response in cows - Wen-Jie Fan; He-Ping Li; He-Shui Zhu; Shi-Ping Sui; Pei-Ge Chen; Yue Deng; Tong-Ming Sui; Yue-Ying Wang (Biotechnology Letters, 2016)

Risk assessment of dietary exposure to aluminium in the Chinese population - Ning Ma; Zhao-Ping Liu; Da-Jin Yang; Jiang Liang; Jiang-Hui Zhu; Hai-Bin Xu; Feng-Qin Li; Ning Li (Food Additives & Contaminants: Part A, 2016)

Surgical treatment of hepato-pancreato-biliary disease in China: the Tongji experience - Binhao Zhang; Wei Dong; Hongping Luo; Xuanru Zhu; Lin Chen; Changhai Li; Peng Zhu; Wei Zhang; Shuai Xiang; Wanguang Zhang; Zhiyong Huang; Xiao-Ping Chen (Science China Life Sciences, 2016)

Characterization and expression analysis of cDNAs encoding abscisic acid 8′-hydroxylase during mulberry fruit maturation and under stress conditions - Yuxiang Cai; Panpan Zhu; Changying Liu; Aichun Zhao; Jian Yu; Chuanhong Wang; Zhengang Li; Ping Huang; Maode Yu (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Hydrogen peroxide is involved in abscisic acid-induced adventitious rooting in cucumber (Cucumis sativus L.) under drought stress - Xue-Ping Li; Qing-Qing Xu; Wei-Biao Liao; Zhan-Jun Ma; Xiao-Ting Xu; Meng Wang; Peng-Ju Ren; Li-Juan Niu; Xin Jin; Yong-Chao Zhu (Journal of Plant Biology, 2016)

Protective Effects of Chinese Herbal Medicine Rhizoma drynariae in Rats After Traumatic Brain Injury and Identification of Active Compound - Wenzhu Wang; Haigang Li; Jintao Yu; Michael Hong; Jing Zhou; Lin Zhu; Yang Wang; Min Luo; Zian Xia; Zeng-Jin Yang; Tao Tang; Ping Ren; et al. (Molecular Neurobiology, 2016)

Trade‐offs and evolution of thermal adaptation in the Irish potato famine pathogen Phytophthora infestans - Li‐Na Yang; Wen Zhu; E‐Jiao Wu; Ce Yang; Peter H. Thrall; Jeremy J. Burdon; Li‐Ping Jin; Li‐Ping Shang; Jiasui Zhan (Molecular Ecology, 2016)
Temperature is one of the most important environmental parameters with crucial impacts on nearly all biological processes. Due to anthropogenic activity, average air temperatures are expected to increase by a few degrees in coming decades, accompanied by an increased occurrence of extreme temperature events. Such global trends are likely to have various major impacts on human society through their influence on natural ecosystems, food production and biotic interactions, including diseases. In this study, we used a combination of statistical genetics, experimental evolution and common garden experiments to investigate the evolutionary potential for thermal adaptation in the potato late blight pathogen, Phytophthora infestans , and infer its likely response to changing temperatures. We found a trade‐off associated with thermal adaptation to heterogeneous environments in P. infestans, with the degree of the trade‐off peaking approximately at the pathogen's optimum growth temperature. A genetic trade‐off in thermal adaptation was also evidenced by the negative association between a strain's growth rate and its thermal range for growth, and warm climates selecting for a low pathogen growth rate. We also found a mirror effect of phenotypic plasticity and genetic adaptation on growth rate. At below the optimum, phenotypic plasticity enhances pathogen's growth rate but nature selects for slower growing genotypes when temperature increases. At above the optimum, phenotypic plasticity reduces pathogen's growth rate but natural selection favours for faster growing genotypes when temperature increases further. We conclude from these findings that the growth rate of P. infestans will only be marginally affected by global warming.

Two new glycosides isolated from Sapindus mukorossi fruits: effects on cell apoptosis and caspase-3 activation in human lung carcinoma cells - Xuan-Ming Zhang; De-Po Yang; Zhi-Yong Xie; Qing Li; Long-Ping Zhu; Zhi-Min Zhao (Natural Product Research, 2016)

Cognitive-enhancing effects of hydrolysate of polygalasaponin in SAMP8 mice - Pan Xu; Shu-ping Xu; Ke-zhu Wang; Cong Lu; Hong-xia Zhang; Rui-le Pan; Chang Qi; Yan-yan Yang; Ying-hui Li; Xin-min Liu (Journal of Zhejiang University-SCIENCE B, 2016)

High throughput transformation of a Sorghum cDNA library for rice improvement - Kezhou Qin; Ping Qiu; Jianyu Wen; Yingguo Zhu; Nengwu Li; Shaoqing Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Seasonal variation of pheophorbide a and flavonoid in different organs of two Carpinus species and its correlation with immunosuppressive activity - Qianqian Sheng; Xianying Fang; Zunling Zhu; Wei Xiao; Zhenzhong Wang; Gang Ding; Linguo Zhao; Yujian Li; Ping Yu; Zhibin Ding; Qinru Sun (In Vitro Cellular & Developmental Biology - Animal, 2016)

Genetic polymorphism analyses of a novel panel of 19 X-STR loci in the Chinese Uygur ethnic minority - Yu-xin Guo; Jian-gang Chen; Yan Wang; Jiang-wei Yan; Jing Chen; Tian-hua Yao; Li-ping Zhang; Guang Yang; Hao-tian Meng; Yu-dang Zhang; Ting Mei; Yao-shun Liu; et al. (Journal of Zhejiang University-SCIENCE B, 2016)

Expression, purification and characterization of a thermostable leucine dehydrogenase from the halophilic thermophile Laceyella sacchari - Wenjun Zhu; Yan Li; Honghua Jia; Ping Wei; Hua Zhou; Min Jiang (Biotechnology Letters, 2016)

Elevated expression of NLRP3 in patients with immune thrombocytopenia - Jianlin Qiao; Yun Liu; Xiaoqian Li; Yuan Xia; Yulu Wu; Depeng Li; Hongchun Li; Ping Ma; Feng Zhu; Zhenyu Li; Kailin Xu; Lingyu Zeng (Immunologic Research, 2016)

PD-1/PD-L1 signal pathway participates in HCV F protein-induced T cell dysfunction in chronic HCV infection - Wen Xiao; Long Feng Jiang; Xiao Zhao Deng; Dan Yan Zhu; Jia Ping Pei; Mao Lei Xu; Bing Jun Li; Chang Jun Wang; Jing Hai Zhang; Qi Zhang; Zhen Xian Zhou; Wei Liang Ding; et al. (Immunologic Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Source Apportionment Coupled with Gas/Particle Partitioning Theory and Risk Assessment of Polycyclic Aromatic Hydrocarbons Associated with Size-Segregated Airborne Particulate Matter - Yunbo Zhai; Ping Li; Yun Zhu; Bibo Xu; Chuan Peng; Tengfei Wang; Caiting Li; Guangming Zeng (Water, Air, & Soil Pollution, 2016)

Effects of sialidase NEU1 siRNA on proliferation, apoptosis, and invasion in human ovarian cancer - Li-rong Ren; Li-ping Zhang; Shu-ying Huang; Yuan-fang Zhu; Wen-juan Li; Shan-yu Fang; Li Shen; Yan-ling Gao (Molecular and Cellular Biochemistry, 2016)

CD147 promotes IKK/IκB/NF-κB pathway to resist TNF-induced apoptosis in rheumatoid arthritis synovial fibroblasts - Yue Zhai; Bo Wu; Jia Li; Xi-ying Yao; Ping Zhu; Zhi-nan Chen (Journal of Molecular Medicine, 2016)

Clinical, biochemical, neuroimaging and molecular findings of X-linked Adrenoleukodystrophy patients in South China - Min-yan Jiang; Yan-na Cai; Cui-li Liang; Min-zhi Peng; Hui-ying Sheng; Li-ping Fan; Rui-zhu Lin; Hua Jiang; Yonglan Huang; Li Liu (Metabolic Brain Disease, 2015)

HPLC simultaneous determination of arbutin, chlorogenic acid and 6′- O -caffeoylarbutin in different parts of Vaccinium dunalianum Wight - Xu-Lu Luo; Na Li; Min Xu; Hong-Tao Zhu; Peng He; Yong Ding; Ping Zhao; Ying-Jun Zhang (Natural Product Research, 2015)

cDNA cloning, expression, and immunolocalization of gonad-inhibiting hormone (GIH) in Litopenaeus vannamei - Guang-li Li; Si-ping Deng; Shu-na Jiang; Man Ye; Hua-pu Chen; Siuming F. Chan; Chun-hua Zhu (Genes & Genomics, 2015)

Characterization of 19 polymorphic microsatellite markers for Asian yellow pond turtle (Mauremys mutica) - Jian Zhao; Ping Wen; Wei Li; Dandan Zhang; Xinping Zhu (Conservation Genetics Resources, 2015)

Prestack forward modeling of tight reservoirs based on the Xu–White model - Chao Zhu; Qing-Xin Guo; Qing-Shun Gong; Zhan-Guo Liu; Sen-Ming Li; Ge-Ping Huang (Applied Geophysics, 2015)

Molecular characteristics and evolutionary analysis of a very virulent infectious bursal disease virus - Zan Li; XiaoLe Qi; XianGang Ren; Lei Cui; XiaoMei Wang; Ping Zhu (Science China Life Sciences, 2015)
Infectious bursal disease virus (IBDV) poses a significant threat to the poultry industry. Viral protein 2 (VP2), the major structural protein of IBDV, has been subjected to frequent mutations that have imparted tremendous genetic diversity to the virus. To determine how amino acid mutations may affect the virulence of IBDV, we built a structural model of VP2 of a very virulent strain of IBDV identified in China, vvIBDV Gx, and performed a molecular dynamics simulation of the interaction between virulence sites. The study showed that the amino acid substitutions that distinguish vvIBDV from attenuated IBDV (H253Q and T284A) favor a hydrophobic and flexible conformation of β-barrel loops in VP2, which could promote interactions between the virus and potential IBDV-specific receptors. Population sequence analysis revealed that the IBDV strains prevalent in East Asia show a significant signal of positive selection at virulence sites 253 and 284. In addition, a signal of co-evolution between sites 253 and 284 was identified. These results suggest that changes in the virulence of IBDV may result from both the interaction and the co-evolution of multiple amino acid substitutions at virulence sites.

GRY79 encoding a putative metallo-β-lactamase-trihelix chimera is involved in chloroplast development at early seedling stage of rice - Chunmei Wan; Chunmei Li; Xiaozhi Ma; Yang Wang; Changhui Sun; Rui Huang; Ping Zhong; Zhiyan Gao; Dan Chen; Zhengjun Xu; Jianqing Zhu; Xiaoling Gao; et al. (Plant Cell Reports, 2015)

Cutaneous Chromoblastomycosis Caused by Veronaea botryosa in a Patient with Pemphigus Vulgaris and Review of Published Reports - Cheng-Yao Zhu; Yan-Ping Yang; Ping Sheng; Wen Li; Wen-Ming Huang; Yi-Ming Fan (Mycopathologia, 2015)

Kinetic changes of regulatory B10 cells in collagen-induced arthritis could be regulated by cytokines IFN-γ and TGF-β1 - Zhaohui Zheng; Tao Liu; Xueyi Li; Jin Ding; Yuan Feng; Jinlin Miao; Xing Luo; Zhenbiao Wu; Ping Zhu (Inflammation Research, 2015)

Foxl2 of the Hong Kong catfish (Clarias fuscus): cDNA cloning, tissue distribution and changes in gene expression towards methyltestosterone, estradiol and letrozole exposure of the fries during gonadal differentiation - Si-ping Deng; Chun-hua Zhu; Jing Sun; Wen-da Wang; Tian-li Wu; Hua-pu Chen; Shang-li Shi; Guang-li Li (Genes & Genomics, 2015)

A new bibenzyl derivative with nuclear factor-kappaB inhibitory activity from Schefflera arboricola (Araliaceae) - Hang Li; Zi-Zhe Cai; Long-Ping Zhu; Xin-Jun Xu; Shao-Rui Chen; De-Po Yang; Zhi-Min Zhao (Natural Product Research, 2015)

Characterization of mineralogy and surface zeta potential of atmospheric dust fall in northwest China - Fa-Qin Dong; Wu Chen; Qun-Wei Dai; Yue-Quan Deng; Ping He; Xiao-Chun He; Jun Tang; Li-Zhu Liu; Hua He (Mineralogy and Petrology, 2015)

Characterization of 26 deletion CNVs reveals the frequent occurrence of micro-mutations within the breakpoint-flanking regions and frequent repair of double-strand breaks by templated insertions derived from remote genomic regions - Ye Wang; Peiqiang Su; Bin Hu; Wenjuan Zhu; Qibin Li; Ping Yuan; Jiangchao Li; Xinyuan Guan; Fucheng Li; Xiangyi Jing; Ru Li; Yongling Zhang; et al. (Human Genetics, 2015)

Simulation of stable water isotopic composition in the atmosphere using an isotopic Atmospheric Water Balance Model - Xin‐Ping Zhang; Hua‐De Guan; Xin‐Zhu Zhang; Hua‐Wu Wu; Guang Li; Yi‐Min Huang (International Journal of Climatology, 2015)
In this article, we present a simplified isotopic Atmospheric Water Balance Model ( iAWBM ), to simulate spatial distribution and temporal variations of δ 18 O in atmospheric vapour and in precipitation, and the correlations of δ 18 O in precipitation with precipitation amount and with temperature. This method overcomes deficiencies of the Global Network of Isotopes in Precipitation ( GNIP ) due to its limitation in space and time resolution and those of the isotope‐enabled General Circulation Models ( iGCM s) due to its complexity. The simulated results reproduce well the latitude effect, continent effect and seasonality of δ 18 O in global precipitation. The simulation suggests that the precipitation amount effect occurs mainly in the low‐mid latitude oceans and monsoon areas, and the simulated temperature effect occurs mainly in the mid‐high latitude continents. However, the simulation results also indicate some temperature effect in some low‐latitude areas where the precipitation amount effect is strong. The modelled precipitation isotopic composition is compared to 3‐year observations in Changsha, China (2010–2012). The simulations reproduce the observed seasonal variations of δ 18 O in precipitation. The basic characteristics that stable isotopes in precipitation are depleted during the rainy season and enriched during the dry season, and the observed amount effect is well simulated under daily time scale. The simulated weighted average δ 18 O (−6.58‰) in precipitation during the prevailing winter monsoon season (October–March) is almost the same as the observed δ 18 O in the same period (−6.56‰), but the simulated δ 18 O (−9.58‰) during the prevailing summer monsoon season (April–September) is lower than the observed δ 18 O (−7.66‰). The simulation result also shows temporal variations of vapour isotopic composition in the atmosphere, and the proportional contributions from horizontal vapour exchange, precipitation and evaporation.

Erratum to: Elevated Cerebral Cortical CD24 Levels in Patients and Mice with Traumatic Brain Injury: A Potential Negative Role in Nuclear Factor Kappa B/Inflammatory Factor Pathway - Wei Li; Hai-Ping Ling; Wan-Chun You; Huan-Dong Liu; Qing Sun; Meng-Liang Zhou; Wei Shen; Jin-Bing Zhao; Lin Zhu; Chun-Hua Hang (Molecular Neurobiology, 2015)

System‐wide characterization of bZIP transcription factor proteins involved in infection‐related morphogenesis of M agnaporthe oryzae - Wei Tang; Yanyan Ru; Li Hong; Qian Zhu; Rongfang Zuo; Xianxian Guo; Jingzhen Wang; Haifeng Zhang; Xiaobo Zheng; Ping Wang; Zhengguang Zhang (Environmental Microbiology, 2015)
Summary The basic leucine zipper ( bZIP ) domain‐containing transcription factors ( TFs ) function as key regulators of cellular growth and differentiation in eukaryotic organisms including fungi. We have previously identified MoAp 1 and MoAtf 1 as bZIP TFs in M agnaporthe oryzae and demonstrated that they regulate the oxidative stress response and are critical in conidiogenesis and pathogenicity. Studies of bZIP proteins could provide a novel strategy for controlling rice blast, but a systematic examination of the bZIP proteins has not been carried out. Here, we identified 19 additional bZIP TFs and characterized their functions. We found that the majority of these TFs exhibit active functions, most notably, in conidiogenesis. We showed that MoHac 1 regulates the endoplasmic reticulum stress response through a conserved unfolded protein response pathway, MoMetR controls amino acid metabolism to govern growth and differentiation, and MoBzip 10 governs appressorium function and invasive hyphal growth. Moreover, MoBzip 5 participates in appressorium formation through a pathway distinct from that MoBzip 10, and MoMeaB appears to exert a regulatory role through nutrient uptake and nitrogen utilization. Collectively, our results provide insights into shared and specific functions associated with each of these TFs and link the regulatory roles to the fungal growth, conidiation, appressorium formation, host penetration and pathogenicity.

Synthesis and in vitro antiproliferative activity of novel benzisoselenazolone derivatives - Li-na Xuan; Peng Wang; Kai Zhang; Yan-ping Shi; Yu-ming Liu; Tao Zhu; Bao-quan Chen (Medicinal Chemistry Research, 2015)

Genetic analysis and chromosome mapping of a thermo-sensitive genic male sterile gene in wheat - Zhen-Gang Ru; Li-Ping Zhang; Tie-Zhu Hu; Hong-Yu Liu; Qing-Kai Yang; Man-Li Weng; Bin Wang; Chang-Ping Zhao (Euphytica, 2015)

Effects of desipramine treatment on stress-induced up-regulation of norepinephrine transporter expression in rat brains - Yan Fan; Ping Chen; Ying Li; Gregory A. Ordway; Meng-Yang Zhu (Psychopharmacology, 2015)

Genome-wide discovery of novel and conserved microRNAs in white shrimp (Litopenaeus vannamei) - Qian-Yun Xi; Yuan-Yan Xiong; Yuan-Mei Wang; Xiao Cheng; Qi-En Qi; Gang Shu; Song-Bo Wang; Li-Na Wang; Ping Gao; Xiao-Tong Zhu; Qing-Yan Jiang; Yong-Liang Zhang; et al. (Molecular Biology Reports, 2015)

Neuropeptide trefoil factor 3 attenuates naloxone-precipitated withdrawal in morphine-dependent mice - Ping Wu; Hai-Shui Shi; Yi-Xiao Luo; Ruo-Xi Zhang; Jia-Li Li; Jie Shi; Lin Lu; Wei-Li Zhu (Psychopharmacology, 2014)

Myocardial infarction worsens glomerular injury and microalbuminuria in rats with pre-existing renal impairment accompanied by the activation of ER stress and inflammation - Zhifeng Dong; Penglong Wu; Yongguang Li; Yuan shen; Ping Xin; Shuai Li; Zhihua Wang; Xiaoyan Dai; Wei Zhu; Meng Wei (Molecular Biology Reports, 2014)

Upregulation of HIF-1α Via Activation of ERK and PI3K Pathway Mediated Protective Response to Microwave-Induced Mitochondrial Injury in Neuron-Like Cells - Li Zhao; Yue-Feng Yang; Ya-Bing Gao; Shui-Ming Wang; Li-Feng Wang; Hong-Yan Zuo; Ji Dong; Xin-Ping Xu; Zhen-Tao Su; Hong-Mei Zhou; Ling-Ling Zhu; Rui-Yun Peng (Molecular Neurobiology, 2014)

Gene expression pattern of insect fat body cells from in vitro challenge to cell line establishment - Huan Zhang; Qian Meng; Ping Tang; Xuan Li; Wei Zhu; Guiling Zhou; Ruihao Shu; Jihong Zhang; Qilian Qin (In Vitro Cellular & Developmental Biology - Animal, 2014)

The rescuable function and mechanism of resveratrol on As2O3-induced hERG K+ channel deficiency - Xin Zhao; Kai-ping Zhang; Ting Huang; Cai-Chuan Yan; Li-Rong Liu; Qi-Lei Zhu; Feng-Feng Guo; Chen Liu; Bao-Xin Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Isolation and characterization of LEAFY COTYLEDON 1-LIKE gene related to embryogenic competence in Citrus sinensis - Shi-ping Zhu; Jun Wang; Jun-li Ye; An-Dan Zhu; Wen-wu Guo; Xiu-xin Deng (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

IL-17A promotes ventricular remodeling after myocardial infarction - Su-Feng Zhou; Jing Yuan; Meng-Yang Liao; Ni Xia; Ting-Ting Tang; Jing-Jing Li; Jiao Jiao; Wen-Yong Dong; Shao-Fang Nie; Zheng-Feng Zhu; Wen-Cai Zhang; Bing-Jie Lv; et al. (Journal of Molecular Medicine, 2014)

Recycling of sediment into the mantle source of K-rich mafic rocks: Sr–Nd–Hf–O isotopic evidence from the Fushui complex in the Qinling orogen - Hao Wang; Yuan-Bao Wu; Chao-Ran Li; Tian-Yu Zhao; Zheng-Wei Qin; Liu-Qin Zhu; Shan Gao; Jian-Ping Zheng; Xiao-Ming Liu; Lian Zhou; Yang Zhang; Sai-Hong Yang (Contributions to Mineralogy and Petrology, 2014)

New natural hosts of Tomato yellow leaf curl virus identified in and near tomato-growing greenhouses in eastern China - Gang Li; Li-ming Zhao; Xiang Wang; Ying Gao; Guo-zhen Sun; Xiao-ping Zhu (Journal of General Plant Pathology, 2014)

Differential role of Rac in the basolateral amygdala and cornu ammonis 1 in the reconsolidation of auditory and contextual Pavlovian fear memory in rats - Ping Wu; Zeng-Bo Ding; Shi-Qiu Meng; Hao-Wei Shen; Shi-Chao Sun; Yi-Xiao Luo; Jian-Feng Liu; Lin Lu; Wei-Li Zhu; Jie Shi (Psychopharmacology, 2014)

Increased DNase I activity in diabetes might be associated with injury of pancreas - Bin Zhu; Yuewen Gong; Pengmin Chen; Haojun Zhang; Tingting Zhao; Ping Li (Molecular and Cellular Biochemistry, 2014)

Advances in preimplantation genetic diagnosis/screening - LiYing Yan; Yuan Wei; Jin Huang; XiaoHui Zhu; XiaoDan Shi; Xi Xia; Jie Yan; CuiLing Lu; Ying Lian; Rong Li; Ping Liu; Jie Qiao (Science China Life Sciences, 2014)

Bimodal voltage dependence of TRPA1: mutations of a key pore helix residue reveal strong intrinsic voltage-dependent inactivation - Xia Wan; Yungang Lu; Xueqin Chen; Jian Xiong; Yuanda Zhou; Ping Li; Bingqing Xia; Min Li; Michael X. Zhu; Zhaobing Gao (Pflügers Archiv - European Journal of Physiology, 2014)

Molecular cloning and dimorphic expression of growth hormone (gh) in female and male spotted scat Scatophagus argus - Si-Ping Deng; Bo Wu; Chun-Hua Zhu; Guang-Li Li (Fisheries Science, 2014)

6′- O -Caffeoylarbutin inhibits melanogenesis in zebrafish - Min Xu; Qiao-Cong Lao; Ping Zhao; Xiao-Yu Zhu; Hong-Tao Zhu; Xu-Lu Luo; Chong-Ren Yang; Jian-Hui He; Chun-Qi Li; Ying-Jun Zhang (Natural Product Research, 2014)

Removal of Pb(II), Cu(II), and Zn(II) from Aqueous Solutions by Amorphous Tin(IV) Hydrogen Phosphate Immobilized on Silica - Chun-Shui Zhu; Xian Dong; Li-Ping Wang (Water, Air, & Soil Pollution, 2014)

High-level soluble expression of the hemA gene from Rhodobacter capsulatus and comparative study of its enzymatic properties - Jia-wei Lou; Li Zhu; Mian-bin Wu; Li-rong Yang; Jian-ping Lin; Pei-lin Cen (Journal of Zhejiang University-SCIENCE B, 2014)

Adsorption of soluble oil from water to graphene - Na Wang; Yuchang Zhang; Fuzhen Zhu; Jingyi Li; Shuaishuai Liu; Ping Na (Environmental Science and Pollution Research, 2014)

The suitability of Ostrinia furnacalis (Lepidoptera: Crambidae) eggs for Trichogramma dendrolimi (Hymenoptera: Trichogrammatidae) can be changed by T. ostriniae - Ping Zhu; Yan-Feng Zhang; Qiong-Ting Song; Fan Zhang; Yuan-Xi Li (Applied Entomology and Zoology, 2014)

Bacillus thuringiensis subsp. sichuansis strain MC28 produces a novel crystal protein with activity against Culex quinquefasciatus larvae - Peng Guan; Xiaojuan Dai; Jun Zhu; Qiao Li; Shuangcheng Li; Shiquan Wang; Ping Li; Aiping Zheng (World Journal of Microbiology and Biotechnology, 2014)

Exposure to diethylhexyl phthalate (DEHP) results in a heritable modification of imprint genes DNA methylation in mouse oocytes - Lan Li; Teng Zhang; Xun-Si Qin; Wei Ge; Hua-Gang Ma; Li-Lan Sun; Zhu-Mei Hou; Hong Chen; Ping Chen; Guo-Qing Qin; Wei Shen; Xi-Feng Zhang (Molecular Biology Reports, 2014)

Elevated Cerebral Cortical CD24 Levels in Patients and Mice with Traumatic Brain Injury: A Potential Negative Role in Nuclear Factor Kappa B/Inflammatory Factor Pathway - Wei Li; Hai-Ping Ling; Wan-Chun You; Huan-Dong Liu; Qing Sun; Meng-Liang Zhou; Wei Shen; Jin-Bing Zhao; Lin Zhu; Chun-Hua Hang (Molecular Neurobiology, 2014)

Morphological and molecular evidence for a new species of Rhodotus from tropical and subtropical Yunnan, China - Li-Ping Tang; Yan-Jia Hao; Qing Cai; Bau Tolgor; Zhu L. Yang (Mycological Progress, 2014)

Identification of Rhizoctonia solani AG1-IB as a causal agent of leaf blight in Cynanchum paniculatum in China - Ai Xin Liu; Zhe Li; Zhi Min Wang; Yuan Cun Liang; Xiao Ping Zhu (Journal of General Plant Pathology, 2014)

Early Carboniferous intra-oceanic arc and back-arc basin system in the West Junggar, NW China - Ping Shen; Hongdi Pan; Wenjiao Xiao; Xian-hua Li; Huawu Dai; Heping Zhu (International Geology Review, 2013)

Regulation of Autophagy and Ubiquitinated Protein Accumulation by bFGF Promotes Functional Recovery and Neural Protection in a Rat Model of Spinal Cord Injury - Hong-Yu Zhang; Zhou-Guang Wang; Fen-Zan Wu; Xiao-Xia Kong; Jie Yang; Bei-Bei Lin; Shi-Ping Zhu; Li Lin; Chao-Shi Gan; Xiao-Bing Fu; Xiao-Kun Li; Hua-Zi Xu; et al. (Molecular Neurobiology, 2013)

The Characterization of Childhood Occipital Epilepsy of Gastaut: A Study of Seven Patients - Xiao Mei Shu; Gui Ping Zhang; Bing Zhu Yang; Juan Li (Cell Biochemistry and Biophysics, 2013)

Interaction Between AT1 Receptor and NF-κB in Hypothalamic Paraventricular Nucleus Contributes to Oxidative Stress and Sympathoexcitation by Modulating Neurotransmitters in Heart Failure - Xiao-Jing Yu; Yu-Ping Suo; Jie Qi; Qing Yang; Hui-Hua Li; Dong-Mei Zhang; Qiu-Yue Yi; Jian Zhang; Guo-Qing Zhu; Zhiming Zhu; Yu-Ming Kang (Cardiovascular Toxicology, 2013)

IgG-Fc N-glycosylation at Asn297 and IgA O-glycosylation in the hinge region in health and disease - Jing Xue; Li-Ping Zhu; Qiang Wei (Glycoconjugate Journal, 2013)

Antioxidant response and histopathological changes in brain tissue of pigeon exposed to avermectin - Ming Li; Tian-Zi You; Wen-Jun Zhu; Jian-Ping Qu; Ci Liu; Bing Zhao; Shi-Wen Xu; Shu Li (Ecotoxicology, 2013)

The first complete genomic characterization of an Amur virus isolate from China - Yu Zhang; Bo-Hua Liu; Fang Lin; Yong-Guo Zhang; Bing-Yin Si; Xiao-Ping Kang; Yi Hu; Jing Li; Xiao-Yan Wu; Yu-Chang Li; Qing-Yu Zhu; Yin-Hui Yang (Archives of Virology, 2013)

Absolute Quantification of E1, Ubiquitin-Like Proteins and Nedd8–MLN4924 Adduct by Mass Spectrometry - Xiaofeng Yang; James E. Brownell; Qing Xu; Fengying Zhu; Jingya Ma; Huay-Keng Loke; Neil Rollins; Teresa A. Soucy; James J. Minissale; Michael P. Thomas; William D. Mallender; Lawrence R. Dick; et al. (Cell Biochemistry and Biophysics, 2013)

Paracoccus siganidrum sp. nov., isolated from fish gastrointestinal tract - Ying Liu; Qing-yi Xie; Kui Hong; Lei Li; Ya-mei Zhao; Yi-li Tang; Jun-ying An; Ping-ping Zhu; Chun-hou Xu (Antonie van Leeuwenhoek, 2013)

Finer resolution observation and monitoring of global land cover: first mapping results with Landsat TM and ETM+ data - Peng Gong; Jie Wang; Le Yu; Yongchao Zhao; Yuanyuan Zhao; Lu Liang; Zhenguo Niu; Xiaomeng Huang; Haohuan Fu; Shuang Liu; Congcong Li; Xueyan Li; et al. (International Journal of Remote Sensing, 2013)

Biochemical characterization of NADP+-dependent isocitrate dehydrogenase from Microcystis aeruginosa PCC7806 - Ming-Ming Jin; Peng Wang; Xue Li; Xiao-Yu Zhao; Lei Xu; Ping Song; Guo-Ping Zhu (Molecular Biology Reports, 2013)

Crystal structure and activating effect on RyRs of AhV_TL-I, a glycosylated thrombin-like enzyme from Agkistrodon halys snake venom - Fuxing Zeng; Bing Shen; Zhongliang Zhu; Ping Zhang; Yonghua Ji; Liwen Niu; Xu Li; Maikun Teng (Archives of Toxicology, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Geothermal regime and hydrocarbon kitchen evolution in the Jianghan Basin - ZongXing Li; Ming Xu; Ping Zhao; ZhanXue Sun; ChuanQing Zhu (Science China Earth Sciences, 2013)

The confirmation of three repeated sequence elements in the 3′ untranslated region of Chikungunya virus - Yu Zhang; Bing-Yin Si; Xiao-Ping Kang; Yi Hu; Jing Li; Xiao-Yan Wu; Yu-Chang Li; Yin-Hui Yang; Qing-Yu Zhu (Virus Genes, 2013)

Tetramethylpyrazine induces G0/G1 cell cycle arrest and stimulates mitochondrial-mediated and caspase-dependent apoptosis through modulating ERK/p53 signaling in hepatic stellate cells in vitro - Feng Zhang; De-Song Kong; Zi-Li Zhang; Na Lei; Xiao-Jing Zhu; Xiao-Ping Zhang; Li Chen; Yin Lu; Shi-Zhong Zheng (Apoptosis, 2013)

An Arabidopsis mutant atcsr-2 exhibits high cadmium stress sensitivity involved in the restriction of H2S emission - Ya-wei Li; Ze-hua Gong; Yao Mu; Yi-xian Zhang; Zeng-jie Qiao; Li-ping Zhang; Zhu-ping Jin; Hua Li; Yan-xi Pei (Journal of Zhejiang University-SCIENCE B, 2012)

Quaternary palaeoenvironmental oscillations drove the evolution of the Eurasian Carassius auratus complex (Cypriniformes, Cyprinidae) - Yun Gao; Shu‐Yan Wang; Jing Luo; Robert W. Murphy; Rui Du; Shi‐Fang Wu; Chun‐Ling Zhu; Yan Li; Andrei D. Poyarkov; Sang Ngoc Nguyen; Peng‐Tao Luan; Ya‐Ping Zhang (Journal of Biogeography, 2012)
Aim We sought to reconstruct the spatio‐temporal genetic diversification in goldfish of the Carassius auratus complex, which is widely distributed in Eurasia, to test whether vicariance events or human‐mediated translocations best explained lineage divergence and genogeographical history. Location East Asia and the Oriental islands including Japan, the Ryukyus and Taiwan, and Europe, including Russia and the Czech Republic. Methods We reconstructed the matrilineal history of Eurasian goldfish using 1876 sequences from the partial mitochondrial DNA control region (426 bp) and 191 complete sequences of cytochrome b (1140 bp) from 67 localities representing most of the range of the species. Divergence times were estimated using a Bayesian Markov chain Monte Carlo approach based either on molecular clock data or on the fossil record. Genetic structure and the historical demography of populations were analysed using partial correlation tests and analyses of molecular variance. Results Three lineages had high levels of regional specificity. Lineages A and B from the main islands of Japan differed greatly from lineage C, which occurred on the mainland, Taiwan and the Ryukyus. Lineages A and B had late Pliocene origins. Six geographically constrained sublineages within lineage C had near‐simultaneous mid‐Pleistocene divergences. Main conclusions Genetic structure in the C. auratus complex appears to have been driven by palaeoenvironmental perturbations rather than human translocations. The disappearance of a land bridge in the Tsushima Strait around 3.0 Ma is responsible for the separation of Japanese and continental lineages; the estimated divergence time is 2.75–2.32 Ma. Fujian, China and Vietnam appear to have provided important refugia for the C. auratus complex during glaciation. After warm, moist summer monsoons intensified during the mid‐Pleistocene, goldfish are likely to have dispersed north‐eastwards to recolonize the Ryukyus via Taiwan and northwards to recolonize mainland China.

Genome characterization of a novel porcine bocavirus - Wan-zhu Yang; Jie-mei Yu; Jin-song Li; Wei-xia Cheng; Can-ping Huang; Zhao-jun Duan (Archives of Virology, 2012)

Participation of Gab1 and Gab2 in IL-22-mediated keratinocyte proliferation, migration, and differentiation - Xiaofang Zhu; Zhongliang Li; Wenyan Pan; Lu Qin; Guoqiang Zhu; Yuehai Ke; Jie Wu; Ping Bo; Songshu Meng (Molecular and Cellular Biochemistry, 2012)

Genome-wide Identification and Characterization of a Dehydrin Gene Family in Poplar (Populus trichocarpa) - Chang-Cai Liu; Chun-Ming Li; Bao-Guang Liu; Su-Jie Ge; Xiu-Mei Dong; Wei Li; Hang-Yong Zhu; Bai-Chen Wang; Chuan-Ping Yang (Plant Molecular Biology Reporter, 2012)

The key role of PGC-1α in mitochondrial biogenesis and the proliferation of pulmonary artery vascular smooth muscle cells at an early stage of hypoxic exposure - Jingjing Rao; Jing Li; Yun Liu; Ping Lu; Xiaojiao Sun; P. K. Sugumaran; Daling Zhu (Molecular and Cellular Biochemistry, 2012)

H. pylori related proinflammatory cytokines contribute to the induction of miR-146a in human gastric epithelial cells - Na Li; Xiang Xu; Bin Xiao; En-Dong Zhu; Bo-sheng Li; Zhen Liu; Bin Tang; Quan-Ming Zou; Hua-Ping Liang; Xu-Hu Mao (Molecular Biology Reports, 2012)

Co-expression and Synergism Analysis of Vip3Aa29 and Cyt2Aa3 Insecticidal Proteins from Bacillus thuringiensis - Xiumei Yu; Tao Liu; Zhiguang Sun; Peng Guan; Jun Zhu; Shiquan Wang; Shuangcheng Li; Qiming Deng; Lingxia Wang; Aiping Zheng; Ping Li (Current Microbiology, 2012)

Genetic Overlap in the Quantitative Resistance of Rice at the Seedling and Adult Stages to Xanthomonas oryzae pv. oryzae - Yong-Li Zhou; Xue-Wen Xie; Mei-Rong Xu; Jin-Ping Zang; Ling-Hua Zhu; Jian-Long Xu; Zhi-Kang Li (Journal of Plant Biology, 2012)

Cutaneous Protothecosis in Patient with Diabetes Mellitus and Review of Published Case Reports - Qiang-Qiang Zhang; Li Li; Li-Ping Zhu; Ying Zhao; Yun-Ru Wang; Jun-hao Zhu; Min Zhu (Mycopathologia, 2012)

Genetic polymorphism analysis of killer cell immunoglobulin-like receptor genes in the Chinese Uygur population - Hong-dan Wang; Bo-feng Zhu; Chun-mei Shen; Guo-lian Yuan; Guang Yang; Juan-ning Guo; Jiang-wei Yan; Hai-xia Qin; Jian-xin Guo; Li-ping Zhang; Xiao-qin Jia; Rudolf Lucas (Molecular Biology Reports, 2012)

Phylogenetic relationships of Chinese Adiantum based on five plastid markers - Jin-Mei Lu; Jun Wen; Sue Lutz; Yi-Ping Wang; De-Zhu Li (Journal of Plant Research, 2012)

Analysis of indica- and japonica-specific markers of Oryza sativa and their applications - Xiao-Jun Dai; Yuan-Zhu Yang; Liang Zhou; Li-Jun Ou; Man-Zhong Liang; Wen-Jia Li; Gong-Ping Kang; Liang-Bi Chen (Plant Systematics and Evolution, 2012)

Characterization of the expression profiles of calpastatin (CAST) gene in chicken - Zeng-Rong Zhang; Xiao-Song Jiang; Hua-Rui Du; Qing Zhu; Xiao-Cheng Li; Chao-Wu Yang; Yi-Ping Liu (Molecular Biology Reports, 2012)

Molecular characterization of two recombinant potato virus Y isolates from China - Biao Wang; Jin-Lei Jia; Xiao-Qiang Wang; Zhen-Yu Wang; Bing-Hui Yang; Xiang-Dong Li; Xiao-Ping Zhu (Archives of Virology, 2012)

A Novel PrP Partner HS-1 Associated Protein X-1 (HAX-1) Protected the Cultured Cells Against the Challenge of H2O2 - Yuan-Yuan Jing; Xiao-Li Li; Qi Shi; Zhao-Yun Wang; Yan Guo; Ming-Ming Pan; Chan Tian; Shu-Ying Zhu; Cao Chen; Han-Shi Gong; Jun Han; Chen Gao; et al. (Journal of Molecular Neuroscience, 2011)

Identification and expression analysis of two growth hormone receptors in zanzibar tilapia (Oreochromis hornorum) - Feng-Ying Gao; Mai-Xin Lu; Xing Ye; Zhang-Han Huang; Huan Wang; Hua-Ping Zhu; Li-Ping Yang (Fish Physiology and Biochemistry, 2011)

Pseudonocardia bannaensis sp. nov., a novel actinomycete isolated from the surface-sterilized roots of Artemisia annua L. - Guo-Zhen Zhao; Jie Li; Wen-Yong Zhu; Xiu-Ping Li; Shou-Zheng Tian; Li-Xing Zhao; Li-Hua Xu; Wen-Jun Li (Antonie van Leeuwenhoek, 2011)

Reduced expression of netrin-1 is associated with fetal growth restriction - Wang Qian-hua; Zhong Shao-ping; Zhu Jian-wen; Yang Yun; Zou Li (Molecular and Cellular Biochemistry, 2011)

Twenty-four polymorphic microsatellite markers from spotted barbell (Hemibarbus maculates) - Jun-Jie Zhu; Shi-Li Liu; Ke-Yi Ma; Jia-Le Li; Qing-Ping Lian (Conservation Genetics Resources, 2011)

Interference competition and group size effect in sika deer (Cervus nippon) at salt licks - Xiaoge Ping; Chunwang Li; Zhigang Jiang; Wuhua Liu; Huanbing Zhu (acta ethologica, 2011)

Investigation of the microRNAs in safflower seed, leaf, and petal by high-throughput sequencing - Haiyan Li; Yuanyuan Dong; Yepeng Sun; Erle Zhu; Jing Yang; Xiuming Liu; Ping Xue; Yanshuang Xiao; Shulin Yang; Jinyu Wu; Xiaokun Li (Planta, 2011)

In Situ Monitoring the Photolysis of Fluoranthene Adsorbed on Mangrove Leaves Using Fiber-Optic Fluorimetry - Li Chen; Ping Wang; Jianbin Liu; Beibei Liu; Yong Zhang; Shuzhen Zhang; Yongguan Zhu (Journal of Fluorescence, 2011)

Abnormal expression and dysfunction of novel SGLT2 mutations identified in familial renal glucosuria patients - Lei Yu; Ji-Cheng Lv; Xu-jie Zhou; Li Zhu; Ping Hou; Hong Zhang (Human Genetics, 2011)

Isolation and Identification of a Pathogen of Silkworm Bombyx mori - Heng-Ping Tao; Zhong-Yuan Shen; Feng Zhu; Xiao-Fang Xu; Xu-Dong Tang; Li Xu (Current Microbiology, 2011)

Characterization of Vegetative Insecticidal Protein vip Genes of Bacillus thuringiensis from Sichuan Basin in China - Xiumei Yu; Aiping Zheng; Jun Zhu; Shiquan Wang; Lingxia Wang; Qiming Deng; Shuangcheng Li; Huainian Liu; Ping Li (Current Microbiology, 2011)

Bacillus zhanjiangensis sp. nov., isolated from an oyster in South China Sea - Yi-Guang Chen; Song-Ping Hu; Shu-Kun Tang; Jian-Wu He; Jian-Qing Xiao; Hong-Yi Zhu; Wen-Jun Li (Antonie van Leeuwenhoek, 2011)

Studies on reproductive characteristics of an interspecific chimera between Brassica juncea and Brassica oleracea - Yan Wang; Qi Cheng; Xue-Yun Zhu; Li-Ping Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Single-step chromatography for simultaneous purification of C-phycocyanin and allophycocyanin with high purity and recovery from Spirulina (Arthrospira) platensis - Shi-Gan Yan; Li-Ping Zhu; Hai-Nan Su; Xi-Ying Zhang; Xiu-Lan Chen; Bai-Cheng Zhou; Yu-Zhong Zhang (Journal of Applied Phycology, 2011)

Population genetic analysis of 15 autosomal STR loci in the Russian population of northeastern Inner-Mongolia, China - Bo-feng Zhu; Guang Yang; Chun-mei Shen; Hai-xia Qin; Shuan-liang Fan; Li-bin Deng; Feng Chen; Li-ping Chen; Hong-dan Wang; Zhen-yuan Wang; Rudolf Lucas; Zhen-min Lian (Molecular Biology Reports, 2010)

Involvement of Hepatopoietin Cn in the development of human hepatocellular carcinoma - Bu-Dong Zhu; Xiao-Li Li; Yong Liu; Jing Chang; Yang Liu; Dong-Dong Zhang; Qiang Wang; Jun Ren; Chun-Ping Cui (Clinical & Experimental Metastasis, 2010)

Amino acid sequence analysis and identification of mutations under positive selection in hemagglutinin of 2009 influenza A (H1N1) isolates - Xiaofan Ding; Lifang Jiang; Changwen Ke; Zhan Yang; Chunliang Lei; Kaiyuan Cao; Jun Xu; Lin Xu; Xingfen Yang; Yonghui Zhang; Ping Huang; Weijun Huang; et al. (Virus Genes, 2010)

Chromosomal localization of rDNA genes and genomic organization of 5S rDNA in Oreochromis mossambicus, O. urolepis hornorum and their hybrid - Hua Ping Zhu; Mai Xin Lu; Feng Ying Gao; Zhang Han Huang; Li Ping Yang; Jian Fang Gui (Journal of Genetics, 2010)

Induction and origin of adventitious roots from chimeras of Brassica juncea and Brassica oleracea - Xue-Yun Zhu; Shi-Jie Chai; Li-Ping Chen; Ming-Fang Zhang; Jing-Quan Yu (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Isolation of high quality RNA and construction of a suppression subtractive hybridization library from ramie (Boehmeria nivea L. Gaud.) - Xu-xia Wang; Bo Wang; Li-jun Liu; Xiao-ping Cui; Jin-yu Yang; Hui Wang; Hui Jiang; Bei-bei Luo; Zhu Long; Wen-xiang Dou; Na Zhang; Ding-xiang Peng (Molecular Biology Reports, 2010)

Water and sediment chemistry of Lake Pumayum Co, South Tibet, China: implications for interpreting sediment carbonate - Jianting Ju; Li-ping Zhu; Junbo Wang; Manping Xie; Xiaolin Zhen; Yong Wang; Ping Peng (Journal of Paleolimnology, 2010)

Distributions of HLA-A and -B alleles and haplotypes in the Yi ethnic minority of Yunnan, China: relationship to other populations - Bo-feng Zhu; Guang Yang; Chun-mei Shen; Hai-xia Qin; Shun-zhi Liu; Ya-jun Deng; Shuan-liang Fan; Li-bin Deng; Feng Chen; Ping Zhang; Jie Fang; Li-ping Chen; et al. (Journal of Zhejiang University-SCIENCE B, 2010)

A new dinorclerone diterpenoid glycoside from Tinospora sinensis - Lang-Ping Dong; Chang-Xiang Chen; Wei Ni; Bai-Bo Xie; Jun-Zhu Li; Hai-Yang Liu (Natural Product Research, 2010)

Involvement of the ornithine decarboxylase/polyamine system in precondition-induced cardioprotection through an interaction with PKC in rat hearts - Ya-Jun Zhao; Wei-Hua Zhang; Chang-Qing Xu; Hong-Zhu Li; Li-Na Wang; Hong Li; Yi-Hua Sun; Yan Lin; Li-Ping Han; Li Zhang; Yie Tian; Rui Wang; et al. (Molecular and Cellular Biochemistry, 2009)

Vegetation recovery monitoring over the waste dump in Haizhou opencast coalmine area, China, during 1975–2000 using NDVI and VF index - Wei Su; Zhong-Ping Sun; Dao-Liang Li; Raaj Ramsankaran; Xiang Zhu; Xiang-Yun Guo (Journal of the Indian Society of Remote Sensing, 2009)

Correlation Analysis Between Bone Mineral Density and Serum Element Contents of Postmenopausal Women in Xi’an Urban Area - Shun-Zhi Liu; Hong Yan; Peng Xu; Jian-Ping Li; Gui-Hua Zhuang; Bo-Feng Zhu; She-Min Lu (Biological Trace Element Research, 2009)

LeY oligosaccharide upregulates DAG/PKC signaling pathway in the human endometrial cells - Yali Li; Keli Ma; Ping Sun; Shuai Liu; Huamin Qin; Zhengmei Zhu; Xiaoqi Wang; Qiu Yan (Molecular and Cellular Biochemistry, 2009)

A new compound from Lygodium japonicum (Thunb.) Sw. - Linxia Zhu; Guogang Zhang; Shengchao Wang; Li Li; Ping Li; Shihua Wu; Xiaoqiu Wang; Lijuan Chen; Chunyuan Pan; Wenzhen Mi (Natural Product Research, 2009)

Could nested PCR be applicable for the study of microbial diversity? - Zhen-Yu Fan; Xiao-Ran Li; Dan-Ping Mao; Gen-Feng Zhu; Sheng-Yue Wang; Zhe-Xue Quan (World Journal of Microbiology and Biotechnology, 2009)

Liquid-based cytology aids in primary fallopian tube cancer diagnosis - Zhuo Ren; Yun-ping Zhang; Hui-xia Yang; Li-rong Zhu (Journal of Zhejiang University-SCIENCE B, 2009)

Prediction of shelled shrimp weight by machine vision - Peng-min Pan; Jian-ping Li; Gu-lai Lv; Hui Yang; Song-ming Zhu; Jian-zhong Lou (Journal of Zhejiang University-SCIENCE B, 2009)

A new screening method based on yeast-expressed human dipeptidyl peptidase IV and discovery of novel inhibitors - Chen-Xi Hu; Hui Huang; Li Zhang; You Huang; Zhu-Fang Shen; Ke-Di Cheng; Guan-Hua Du; Ping Zhu (Biotechnology Letters, 2009)

Cloning and Characterization of Two Novel Crystal Protein Genes, cry54Aa1 and cry30Fa1, from Bacillus thuringiensis Strain BtMC28 - Furong Tan; Jun Zhu; Jie Tang; Xueming Tang; Shiquan Wang; Aiping Zheng; Ping Li (Current Microbiology, 2009)

No spatial memory deficit exists in Kunming mice that recently recovered from motor defects following 3-nitropropionic acid intoxication - Xiao-Min Li; Bing-Gen Zhu; Jian-Bo Ni; Chun-Yan Cao; Jie-Ping Zhang; Xu-Dong Zhao; Rong-Shen Zhu (Neuroscience Bulletin, 2009)

A new ecdysteroside from Lygodium japonicum (Thunb.) Sw. - Linxia Zhu; Guogang Zhang; Lijuan Chen; Shengchao Wang; Ping Li; Li Li (Journal of Natural Medicines, 2009)

A new arylbenzofuran from the aerial parts of alfalfa - Shengchao Wang; Guogang Zhang; Jin Guan; Linxia Zhu; Lijuan Chen; Chunyuan Pan; Ping Li; Li Li (Journal of Natural Medicines, 2009)

Limestone Dissolution Induced by Fungal Mycelia, Acidic Materials, and Carbonic Anhydrase from Fungi - Wei Li; Peng-Peng Zhou; Li-Ping Jia; Long-Jiang Yu; Xue-Li Li; Min Zhu (Mycopathologia, 2009)

Evaluation of antimicrobial activity of certain Chinese plants used in folkloric medicine - Airong Li; Yue Zhu; Xingbing He; Xingjun Tian; Liang Xu; Wu Ni; Ping Jiang (World Journal of Microbiology and Biotechnology, 2008)

Proteiomic patterns for endometrial cancer using SELDI-TOF-MS - Li-rong Zhu; Wen-ying Zhang; Li Yu; Yan-hua Zheng; Jun Hu; Qin-ping LIAO (Journal of Zhejiang University-SCIENCE B, 2008)

Phylogenetic diversity of culturable fungi associated with the Hawaiian Sponges Suberites zeteki and Gelliodes fibrosa - Guangyi Wang; Quanzi Li; Ping Zhu (Antonie van Leeuwenhoek, 2008)

The complete genomic sequence of Tobacco vein banding mosaic virus and its similarities with other potyviruses - Xiao-Qing Yu; Yu-Fei Lan; Hong-Yan Wang; Jin-Liang Liu; Xiao-Ping Zhu; Jari P. T. Valkonen; Xiang-Dong Li (Virus Genes, 2007)

Induction and origin of adventitious shoots from chimeras of Brassica juncea and Brassica oleracea - Xue-Yun Zhu; Man Zhao; Sheng Ma; Ya-Ming Ge; Ming-Fang Zhang; Li-Ping Chen (Plant Cell Reports, 2007)

Genes expression analyses of sea-island cotton (Gossypium barbadense L.) during fiber development - Li-Li Tu; Xian-Long Zhang; Shao-Guang Liang; Di-Qiu Liu; Long-Fu Zhu; Fan-Chang Zeng; Yi-Chun Nie; Xiao-Ping Guo; Feng-Lin Deng; Jia-Fu Tan; Li Xu (Plant Cell Reports, 2007)

Response of soil respiration to simulated N deposition in a disturbed and a rehabilitated tropical forest in southern China - Jiangming Mo; Wei Zhang; Weixing Zhu; Yunting Fang; Dejun Li; Ping Zhao (Plant and Soil, 2007)

A Honglian CMS line of rice displays aberrant F0 of F0F1-ATPase - Hong Zhang; Shaoqing Li; Ping Yi; Cuixiang Wan; Zuyu Chen; Yingguo Zhu (Plant Cell Reports, 2007)

Fibrarecisin, a novel triterpenoid from Fibraurea recisa with antitumor activity - Jiao-Long Fu; Chang-Heng Tan; Li-Ping Lin; Ji Huang; Da-Yuan Zhu (Natural Product Research, 2007)

Hydrogen peroxide-induced chlorophyll a bleaching in the cytochrome b 6 f complex: a simple and effective assay for stability of the complex in detergent solutions - Xiao-Bo Chen; Xiao-Hui Zhao; Yi Zhu; Yan-Dao Gong; Liang-Bi Li; Jian-Ping Zhang; Ting-Yun Kuang (Photosynthesis Research, 2007)

Phenolic constituents from the rhizomes of Gastrodia elata - Xiao-Dong Yang; Jie Zhu; Rong Yang; Jing-Ping Liu; Liang Li; Hong-Bin Zhang (Natural Product Research, 2007)

Determination of Trace Mercury by Solid Substrate-Room Temperature Phosphorimetry Quenching Method Based on Catalytic Effect of Hg2+on Formation of the Ion Association Complex [Sn(XO)6]4+·[(Fin)4] - Jia-Ming Liu; Ruo-Hong Wu; De-Chang Li; Ping Zhou; Min-Min Zheng; Xiao-Yi Zeng; Dong-Xia Liu; Xiao-Mei Huang; Guo-Hui Zhu (Journal of Fluorescence, 2006)

Artificial synthesis of interspecific chimeras between tuber mustard (Brassica juncea) and cabbage (Brassica oleracea) and cytological analysis - Li-Ping Chen; Ya-Ming Ge; Xue-Yun Zhu (Plant Cell Reports, 2006)

Effects of Cold Shock on Microtubule Organization and Cell Cycle in Gynogenetically Activated Eggs of Olive Flounder (Paralichthys olivaceus) - Xiang-Ping Zhu; Feng You; Pei-Jun Zhang; Yong-Li Xu; Jian-He Xu (Marine Biotechnology, 2006)

Identification and expression analysis of alternatively spliced isoforms of human interleukin-23 receptor gene in normal lymphoid cells and selected tumor cells - Xiang-Yue Zhang; Hai-Jing Zhang; Yun Zhang; Ying-Jie Fu; Jie He; Li-Ping Zhu; Shu-Hui Wang; Li Liu (Immunogenetics, 2006)

Study on the expression and mutation of human telomeric repeat binding factor (hTRF1) in 10 malignant hematopoietic cell lines - Jie Sun; He Huang; Yuan-yuan Zhu; Jian-ping Lan; Jing-yuan Li; Xiao-yu Lai; Jian Yu (Journal of Zhejiang University-SCIENCE B, 2005)

Novel CACNA1S mutation causes autosomal dominant hypokalemic periodic paralysis in a Chinese family - Qiufen Wang; Mugen Liu; Chunsheng Xu; Zhaohui Tang; Yuhua Liao; Rong Du; Wei Li; Xiaoyan Wu; Xu Wang; Ping Liu; Xianqin Zhang; Jianfang Zhu; et al. (Journal of Molecular Medicine, 2005)

Mapping of quantitative trait loci (QTLs) for rice protein and fat content using doubled haploid lines - Zhong-Li Hu; Ping Li; Ming-Quan Zhou; Zhi-Hong Zhang; Ling-Xia Wang; Li-Huang Zhu; Ying-Guo Zhu (Euphytica, 2004)

1400-year cold/warm fluctuations reflected by environmental magnetism of a lake sediment core from the Chen Co, southern Tibet, China - Li-ping Zhu; Ping-zhong Zhang; Wei-lan Xia; Bing-yuan Li; Ling Chen (Journal of Paleolimnology, 2003)

Identification of quantitative trait loci (QTLs) for the characters of vascular bundles in peduncle related to indica-japonica differentiation in rice (Oryza sativa L.) - Zhi-Hong Zhang; Ping Li; Ling-Xia Wang; Chang-Jun Tan; Zhong-Li Hu; Ying-Guo Zhu; Li-Huang Zhu (Euphytica, 2002)

Chemical element transfer of weathering granite regolith in the Three Gorges Dam region of Yangtze River - Zhang Li-ping; Zhu Da-kui; Yang Da-yuan (Journal of Geographical Sciences, 2002)

Research on system of flood disaster control and reduction supported by gis in medium and small basins - You-peng Xu; Jin-kang Du; Li-feng Zhang; Xiao-ping Ge; Bu-zhu Peng (Chinese Geographical Science, 2002)

“Greatest lake period” and its palaeo-environment on the Tibetan Plateau - Li Bing-yuan; Zhu Li-ping (Journal of Geographical Sciences, 2001)

A numerical study of second-order turbulent moments in the stably stratified nocturnal boundary layer - Zhu Ping; Xu Xiaojing; Li Xingsheng (Advances in Atmospheric Sciences, 1992)